battery

Graphite-based negative electrodes with a tailored electrolyte composition enhance lithium-ion battery performance in low-temperature conditions, addressing discharge capacity and reaction potential issues, resulting in improved discharge capacity, voltage, safety, and reliability.

JP2025016365APending Publication Date: 2025-01-31SEMICON ENERGY LAB CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024113181
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-21
Filing Date
2024-07-16
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face challenges in maintaining sufficient charge and discharge characteristics in low-temperature environments below 0°C, with limitations in discharge capacity and reaction potential in low-temperature conditions.

Method used

The use of graphite as a negative electrode active material, combined with a specific electrolyte composition including lithium salt, potassium salt, fluoroethylene carbonate, and fluoroalkyl carbonate, along with a carbon-based separator, enhances battery performance in low-temperature conditions.

Benefits of technology

The solution provides lithium-ion batteries with improved discharge capacity, high rechargeable voltage, safety, reliability, and reduced deterioration, enabling stable operation in low-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016365000001_ABST
    Figure 2025016365000001_ABST
Patent Text Reader

Abstract

To provide a battery having an excellent charging and discharging characteristic even under a low temperature environment.SOLUTION: A battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The electrolyte and the separator are provided between the positive electrode and the negative electrode. The negative electrode includes a carbon material. The electrolyte includes a lithium salt, a potassium salt, a fluoride cyclic carbonate, a fluoride chain carbonate, and at least one type of anions. In the above, the carbon material has a graphite, the lithium salt includes a LiPF6, the potassium salt includes a KFSI, the fluoride cyclic carbonate includes a fluoroethylene carbonate, and the fluoride chain carbonate includes a trifluoro methyl propionate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One embodiment of the present invention relates to an object, a method, or a manufacturing method. Alternatively, the present invention relates to a process, a machine, a manufacture, or a composition of matter. One embodiment of the present invention relates to a power storage device including a battery (also called a secondary battery), a semiconductor device, a display device, a light-emitting device, a lighting device, an electronic device, a vehicle, or a manufacturing method thereof.

[0002] In this specification, the term "electronic device" refers to any device having a power storage device, and an electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all classified as electronic devices. [Background technology]

[0003] In recent years, various types of power storage devices, such as lithium-ion batteries, lithium-ion capacitors, air batteries, etc. In particular, the demand for high-output, high-capacity lithium-ion batteries has rapidly expanded along with the development of the semiconductor industry, and they have become indispensable in the modern information society as a rechargeable energy source.

[0004] In particular, there is a high demand for batteries for mobile electronic devices that have a large discharge capacity per weight and excellent cycle characteristics. In order to meet this demand, the positive electrode active material of the battery positive electrode has been improved. Research on the crystal structure of the positive electrode active material has also been conducted (Non-Patent Documents 1 to 3).

[0005] X-ray diffraction (XRD) is one of the techniques used to analyze crystal structures. XRD data can be analyzed by using the Inorganic Crystal Structure Database (ICSD) introduced in Non-Patent Document 4. For example, the lattice constant of lithium cobalt oxide described in Non-Patent Document 5 can be referenced from ICSD.

[0006] However, general lithium-ion batteries have problems with charging and discharging at low temperatures. In particular, there is a problem that sufficient charge and discharge characteristics cannot be obtained in a low-temperature environment of 0° C. or below. However, since it is desirable for a battery to exhibit stable performance regardless of the environment, development of battery components (positive electrode active material, negative electrode active material, electrolyte, etc.) for use in lithium-ion batteries is being promoted in order to obtain sufficient charge and discharge characteristics even in a low-temperature environment of 0° C. or below (Patent Document 1).

[0007] As a method for improving the battery performance of a lithium-ion battery, Patent Document 2 describes a conditioning method for reducing the reaction resistance in a negative electrode active material, in which sodium ions or potassium ions are inserted into graphite.

[0008] The phenomenon of potassium ions being inserted into graphite has been reported in detail in, for example, Non-Patent Document 6.

[0009] In calculations related to graphite, it is important to take van der Waals forces into account. Corrections related to dispersion forces such as van der Waals forces in computational science are reported in, for example, Non-Patent Document 7. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] WO2023 / 73480 Brochure [Patent Document 2] JP 2005-302630 A [Non-patent literature]

[0011] [Non-Patent Document 1] Toyoki Okumura et al., “Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation”, Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-Patent Document 2] T. Motohashi, et al., “Electronic phase diagram of the layered cobalt oxide system LixCoO2(0.0≦x≦1.0)”, Physical Review B, 80(16);165114 [Non-Patent Document 3] Zhaohui Chen et al., “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society,2002,149(12)A1604-A1609 [Non-Patent Document 4] Belsky, A. et al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., (2002) B58 364-369. [Non-Patent Document 5] Akimoto, J.; Gotoh, Y.; Oosawa, Y. “Synthesis and structural refinement of LiCoO2 single crystals” Journal of Solid State Chemistry (1998) 141, p. 298-302. [Non-Patent Document 6] H. Onuma et al., “Phase evolution of electrochemically potassium intercalated graphite.” Journal of Materials Chemistry A 9.18 (2021): 11187-11200 [Non-Patent Document 7] S. Grimme “Semiempirical GGA-type density functional constructed with a long-range dispersion correction.” Journal of computational chemistry 27.15 (2006): 1787-1799. Summary of the Invention [Problem to be solved by the invention]

[0012] Patent Document 1 describes that a battery capable of operating even in a low-temperature environment has been realized by using the nonaqueous solvent described in Patent Document 1. However, even with the battery described in Patent Document 1, the discharge capacity when discharged at a temperature of 0° C. or lower was not large at the time of filing the present invention, and further improvement is desired.

[0013] For example, Patent Document 1 discloses that the use of hard carbon facilitates charging and discharging in a low-temperature environment of 0° C. or less, but the reaction potential of hard carbon with lithium ions is higher than the reaction potential of graphite with lithium at 25° C. In other words, when hard carbon is used in the negative electrode of a battery, the operating voltage of a battery using hard carbon as the negative electrode active material is lower than that of a battery using graphite as the negative electrode active material.

[0014] Patent Document 2 describes a method for reducing the reaction resistance of a negative electrode containing graphite, but does not describe use in a low-temperature environment below 0° C. In addition, there is no description of an electrolyte or organic solvent suitable for charging and discharging in a low-temperature environment.

[0015] In view of this, an object of one embodiment of the present invention is to provide a battery that uses graphite as a negative electrode active material and has excellent battery characteristics even in a low-temperature environment (for example, 0° C. or lower, preferably −20° C. or lower, more preferably −30° C. or lower, more preferably −40° C. or lower). Note that the battery characteristics refer to charge capacity, discharge capacity, charge / discharge cycle characteristics, safety, reliability, etc., and a battery is said to have excellent battery characteristics when one or more of these are excellent.

[0016] Another object of the present invention is to provide a battery with a high charging voltage. Another object of the present invention is to provide a battery with high safety or reliability. Another object of the present invention is to provide a battery with little deterioration. Another object of the present invention is to provide a battery with a long life. Another object of the present invention is to provide a new battery.

[0017] Another object is to provide a novel substance, active material, battery, or a manufacturing method thereof.

[0018] Note that the description of these problems does not preclude the existence of other problems. Note that one embodiment of the present invention does not necessarily solve all of these problems. Note that it is possible to extract problems other than these from the description of the specification, drawings, and claims. [Means for solving the problem]

[0019] One embodiment of the present invention is a battery having a positive electrode, a negative electrode, an electrolyte, and a separator, with the electrolyte and separator between the positive electrode and the negative electrode, the negative electrode having a carbon material, and the electrolyte having a lithium salt, a potassium salt, a fluorinated cyclic carbonate, a fluorinated chain carbonate, and at least one type of anion.

[0020] In the above, the carbon material is preferably graphite, and more preferably natural graphite.

[0021] In any one of the above, it is preferable that the lithium salt includes LiPF6, the potassium salt includes KFSI, the fluorinated cyclic carbonate includes fluoroethylene carbonate, and the fluorinated chain carbonate includes methyl trifluoropropionate.

[0022] In the above, the positive electrode preferably has lithium cobalt oxide to which magnesium, aluminum, and nickel are added, or the positive electrode preferably has lithium cobalt oxide to which magnesium, aluminum, nickel, and titanium are added. Effect of the Invention

[0023] According to one embodiment of the present invention, a battery can be provided that uses graphite as a negative electrode active material and has excellent battery characteristics even in a low-temperature environment (e.g., 0° C. or lower, preferably −20° C. or lower, more preferably −30° C. or lower, and more preferably −40° C. or lower).

[0024] According to one embodiment of the present invention, a battery with a high charging voltage can be provided. A battery with high safety or reliability can be provided. A battery with little deterioration can be provided. A battery with a long life can be provided. Or a novel battery can be provided.

[0025] According to one embodiment of the present invention, a novel substance, active material, battery, or a manufacturing method thereof can be provided.

[0026] Note that the description of these effects does not preclude the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of these effects. Note that effects other than these will become apparent from the description in the specification, drawings, claims, etc., and it is possible to extract effects other than these from the description in the specification, drawings, claims, etc. [Brief description of the drawings]

[0027] [Figure 1]1(A) and 1(B) are diagrams showing an example of a cross section of an electrode. [Diagram 2] 2(A) and 2(B) are diagrams for explaining a calculation model. [Diagram 3] 3(A) and 3(B) are diagrams for explaining a calculation model. [Figure 4] 4(A) and 4(B) are diagrams for explaining a calculation model. [Diagram 5] 5(A) and 5(B) are graphs illustrating the calculation results. [Figure 6] 6(A) and 6(B) are graphs illustrating the calculation results. [Figure 7] FIG. 7 is a diagram showing the external appearance of a secondary battery. [Figure 8] 8A to 8C are diagrams illustrating a method for manufacturing a secondary battery. [Figure 9] FIG. 9(A) is a cross-sectional view of a positive electrode active material, and FIG. 9(B) is a diagram illustrating the distribution of an additive element in the positive electrode active material. [Figure 10] FIG. 10 is a diagram illustrating the results of the DSC analysis. [Figure 11] Figure 11 is an example of a TEM image in which the crystal orientations are roughly consistent. [Figure 12] Figure 12(A) is an example of a STEM image in which the crystal orientations are roughly consistent, Figure 12(B) is an FFT pattern of the region of the rock-salt-type crystal RS, and Figure 12(C) is an FFT pattern of the region of the layered rock-salt-type crystal LRS. [Figure 13] FIG. 13 is a diagram illustrating the crystal structure of the positive electrode active material. [Figure 14] FIG. 14 is a diagram illustrating the crystal structure of a conventional positive electrode active material. [Figure 15] FIG. 15 shows an XRD pattern calculated from the crystal structure. [Figure 16] FIG. 16 shows an XRD pattern calculated from the crystal structure. [Figure 17] 17(A) and 17(B) are diagrams showing XRD patterns calculated from the crystal structure. [Figure 18] FIG. 18 is a cross-sectional view of the positive electrode active material. [Figure 19] FIG. 19 is a diagram illustrating a method for producing a positive electrode active material. [Figure 20] 20A to 20C are diagrams illustrating a method for manufacturing a positive electrode active material. [Figure 21] 21(A) and 21(B) are diagrams illustrating a method for manufacturing a positive electrode active material. [Figure 22] 22A to 22H are diagrams illustrating examples of electronic devices. [Figure 23] 23A to 23D are diagrams illustrating examples of electronic devices. [Figure 24] 24A to 24C are diagrams illustrating examples of electronic devices. [Diagram 25] 25(A) to 25(C) are diagrams illustrating an example of a vehicle. [Figure 26] 26(A) to 26(D) are diagrams for explaining an example of space equipment. [Figure 27] 27(A) and 27(B) are graphs illustrating the results of the examples. [Figure 28] 28(A) and 28(B) are graphs illustrating the results of the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following description, and it will be easily understood by those skilled in the art that the form and details of the present invention can be modified in various ways. Furthermore, the present invention is not to be interpreted as being limited to the description of the embodiments shown below.

[0029] In the configuration of the invention described below, the same parts or parts having similar functions are denoted by the same reference numerals in different drawings, and the repeated explanations are omitted. In addition, when referring to similar functions, the same hatching pattern may be used and no particular reference numeral may be used.

[0030] In addition, for ease of understanding, the position, size, range, etc. of each component shown in the drawings may not represent the actual position, size, range, etc. Therefore, the disclosed invention is not necessarily limited to the position, size, range, etc. disclosed in the drawings.

[0031] In this specification, the ordinal numbers "first" and "second" are used for convenience and do not limit the number of components or the order of the components (e.g., the order of processes or the order of stacking). In addition, an ordinal number attached to a component in one part of this specification may not match an ordinal number attached to the same component in another part of this specification or in the claims.

[0032] (Embodiment 1) [battery] The battery according to one embodiment of the present invention includes a positive electrode, a negative electrode, an electrolyte, and a separator. The battery according to one embodiment of the present invention may also include an exterior body that covers at least a portion of the periphery of the positive electrode, the negative electrode, and the electrolyte.

[0033] In this embodiment, the description will focus on the configuration of a battery required to realize a battery having excellent battery characteristics even in a low-temperature environment (for example, 0° C. or lower, preferably −20° C. or lower, more preferably −30° C. or lower, more preferably −40° C. or lower). Specifically, the description will focus on the negative electrode active material and electrolyte contained in the negative electrode.

[0034] Fig. 1(A) is a schematic cross-sectional view illustrating the internal structure of a battery 10 according to one embodiment of the present invention. Fig. 1(B) is an enlarged view of a region A indicated by a dashed line in Fig. 1(A).

[0035] 1(A), the positive electrode 20 has a positive electrode current collector 22 and a positive electrode active material layer 23. The negative electrode 30 has a negative electrode current collector 32 and a negative electrode active material layer 33. The positive electrode 20 and the negative electrode 30 are overlapped with the separator 40 in between, such that the positive electrode active material layer 23 and the negative electrode active material layer 33 face each other. In addition, the battery has an electrolyte in the voids of the positive electrode active material layer 23, the negative electrode active material layer 33, and the separator 40.

[0036] [Negative electrode 1] The negative electrode 30 will be described with reference to Fig. 1(B). The negative electrode active material layer 33 is provided on the negative electrode current collector 32. The negative electrode active material layer 33 includes a negative electrode active material 34 and a binder 35. An electrolyte 45 is also included in the voids of the negative electrode active material layer 33. The negative electrode active material layer 33 may further include a conductive material 36.

[0037] For example, a metal foil can be used as the negative electrode current collector 32. The negative electrode active material layer 33 can be formed by applying a slurry onto the negative electrode current collector 32 and drying it. The negative electrode active material layer 33 after drying may be pressed.

[0038] The slurry is a dispersion liquid used to form an active material layer on a current collector, and contains an active material, a binder, and a solvent, and preferably further contains a conductive material. A thickener may be added together with the binder. The slurry is sometimes called an electrode slurry or an active material slurry, and when a negative electrode active material layer is formed, it is sometimes called a negative electrode slurry.

[0039] <Negative electrode active material> It is preferable to use a carbon material as the negative electrode active material 34. As the carbon material, for example, graphite can be used.

[0040] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, as the artificial graphite, spherical artificial graphite (spherical artificial graphite) having a spherical shape can be used. Examples of natural graphite include flake graphite and spheroidized natural graphite (spherical natural graphite).

[0041] When lithium ions are inserted between the crystal layers of graphite (when lithium-graphite intercalation compounds are formed), graphite exhibits a low potential similar to that of metallic lithium (0.05 V to 0.5 V vs. Li / Li + ). This allows lithium ion batteries using graphite to exhibit a high operating voltage. Furthermore, graphite is preferred because it has the advantages of being relatively high capacity per unit volume, relatively small volume expansion, inexpensive, and safer than metallic lithium. Furthermore, graphite is preferred because it can exhibit a higher operating voltage when incorporated into the negative electrode of a lithium ion battery compared to non-graphitizable carbon.

[0042] In addition to graphite, the negative electrode active material layer may further include graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon fiber (carbon nanotube, carbon nanofiber), graphene, carbon black, silicon (Si), tin (Sn), gallium (Ga), silicon monoxide (SiO), and lithium titanium oxide (Li4Ti5O 12 ) may have any one or more of.

[0043] The negative electrode current collector 32, binder 35, and conductive material 36 of the negative electrode 30 will be described later in [Negative electrode 2].

[0044] [Electrolyte] An example of an electrolyte that has good charge characteristics in a low-temperature environment and / or good discharge characteristics in a low-temperature environment and is used in the battery of one embodiment of the present invention will be described below.

[0045] The electrolyte described below is a liquid electrolyte in which a metal salt (such as a lithium salt) is dissolved in an organic solvent, and is also called an electrolyte solution or an organic electrolyte solution. The electrolyte solution used in the battery of one embodiment of the present invention contains a lithium salt and a metal M salt as metal salts. The molar concentration of the lithium salt contained in the electrolyte solution is preferably higher than the molar amount of the metal M salt contained in the electrolyte solution. A battery in which the electrolyte solution contains a large amount of lithium ions as metal cations can be called a lithium ion battery. When the electrolyte solution used in the battery of one embodiment of the present invention contains two types of metal cations, the battery can be called a dual cation battery or a dual ion battery.

[0046] <Lithium salt> Lithium salts include, for example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, and Li2B 10 Cl 10 , Li2B 12 Cl 12 At least one lithium salt of LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(FSO2)2, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, lithium bis(oxalato)borate (LiBOB), or two or more of these in any combination and ratio, can be used.

[0047] <Metal M salt> Metal M salts have as a cation a metal M. Elements that can be used as the metal M are described below.

[0048] Here, an element that can be used as the metal M can be said to be an element that can enter between the crystal layers of graphite and can widen the distance between the crystal layers of graphite more than when Li enters. Scientific calculations related to elements that can be used as the metal M are described below.

[0049] <<Calculation 1>> Using a model assuming a bulk graphite, the formation energy of graphite intercalation compounds (GICs) of each intercalant and the spread between the graphite crystal layers were calculated by first-principles molecular dynamics calculations. Note that an intercalant refers to an element inserted between the graphite crystal layers.

[0050] A calculation was performed in which one intercalant was inserted between the crystal layers of graphite. In this calculation, lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), scandium (Sc), yttrium (Y), and lanthanum (La: La is used as a representative of lanthanoids) were calculated for each element as intercalant. The specific calculation conditions for quantum molecular dynamics were as shown in Table 1. The models used in the calculation are shown in Figures 2(A) to 4(B).

[0051] [Table 1]

[0052] The conditions for van der Waals force interactions in density functional theory (DFT-D2) calculations are shown below. IVDW:1 VDW_RADIUS:30 VDW_S6:0.75 VDW_D:20 VDW_C6: Use the values ​​listed in Non-Patent Document 7 (Table 1) for each element (however, for Cs, Ba, and La, use the value of 38.54) VDW_R0: Use the values ​​listed in Non-Patent Document 7 (Table 1) for each element (however, the values ​​used are 1.771 for Cs, 1.738 for Ba, and 1.716 for La)

[0053] Figures 2(A) and 2(B) are calculation models of graphite without intercalants between the crystal layers, Figures 3(A) and 3(B) are calculation models of graphite with intercalants between the crystal layers, and Figures 4(A) and 4(B) are calculation models in which the intercalants exist as bulk metals. In each schematic diagram, the parallelepiped shown by the dashed line indicates the lattice, which is the repeating unit of the calculation model.

[0054] The calculation models of Figures 2(A) and 2(B) show 144 carbon atoms (C) and have a structure in which two layers of 72 carbon atoms are stacked. In addition, the calculation models of Figures 3(A) and 3(B) show a structure in which one intercalant atom (metal M) is inserted between the layers in the calculation models of Figures 2(A) and 2(B). In addition, the calculation models of Figures 4(A) and 4(B) show a structure in which 128 atoms (metal) are used as intercalants in the calculation models of Figures 3(A) and 3(B).

[0055] The results of calculations performed under the above conditions are shown in Figure 5(A), Figure 5(B), Table 2, and Table 3. Figure 5(A) and Table 2 show the amount of change in energy ΔE caused by inserting an intercalant between the crystal layers of graphite. Also, Figure 5(B) and Table 3 show the amount of change in the c-axis length of the lattice ΔD caused by inserting an intercalant between the crystal layers of graphite.

[0056] [Table 2]

[0057] The calculation method of ΔE shown in FIG. 5(A) and Table 2 will be described. The energy value obtained by performing a structural relaxation calculation on the calculation model shown in FIG. 2(A) and FIG. 2(B) is defined as Eg, and the energy value obtained by performing an atomic relaxation calculation on the calculation model shown in FIG. 3(A) and FIG. 3(B) is defined as E GIC(M) The energy value obtained by performing atomic relaxation calculations on the calculation models shown in Figs. 4(A) and 4(B) is divided by 128 (the number of atoms) to obtain E METAL(M) Then, ΔE=E GIC(M)-(Eg+E METAL(M) ) ΔE is calculated using the formula. For example, if the intercalant is lithium (Li), ΔE = E GIC(Li) -(Eg+E METAL(Li) ).

[0058] When ΔE is a negative value, the intercalant may enter between the crystal layers of graphite. As shown in FIG. 5(A) and the calculation results in Table 2, the elements that may enter between the crystal layers of graphite are lithium, potassium, rubidium, cesium, strontium, and barium.

[0059] [Table 3]

[0060] The calculation method of ΔD shown in FIG. 5(B) and Table 3 will be described. The c-axis length of the lattice after the atomic relaxation calculation of the calculation model shown in FIG. 2(A) and FIG. 2(B) is Dg, and the c-axis length of the lattice after the atomic relaxation calculation of the calculation model shown in FIG. 3(A) and FIG. GIC(M) Then, ΔD=D GIC(M) -Dg is calculated using the formula. For example, if the intercalant is lithium (Li), then ΔD = D GIC(Li) -Dg. Note that 1Å=10 -10 m.

[0061] When metal M is inserted between the crystal layers of graphite, the interlayer distance D GIC(M) However, when lithium is inserted between the graphite crystal layers, the interlayer distance D GIC(Li) Thus, it is preferable that the interlayer distance D GIC(Li) Layer distance D longer than GIC(M) When a region where this occurs (a region where metal M is intercalated) is present in graphite, it is expected that the reaction resistance when lithium is intercalated between the crystal layers of graphite in the region where metal M is intercalated will be reduced.

[0062] Therefore, the layer distance D GIC(Li) Layer distance D longer than GIC(M)When such a region exists in graphite, it is considered that lithium can be inserted between the crystal layers of graphite in the region where metal M is inserted, even in a low-temperature environment. In other words, the charge / discharge characteristics of the battery can be improved in a low-temperature environment.

[0063] As shown in FIG. 5(B) and the calculation results in Table 3, it is predicted that all of the elements calculated this time will be able to expand the space between the graphite crystal layers more than when lithium is inserted.

[0064] <<Calculation 2>> Next, calculation 2 was performed, in which some of the calculation conditions were changed from calculation 1.

[0065] As the calculation model, the calculation model explained with reference to FIGS. 2(A) to 4(B) was used, as in Calculation 1.

[0066] The specific calculation conditions for the first-principles molecular dynamics calculations are shown in Table 4.

[0067] [Table 4]

[0068] The IVDW was set to 12 as a condition for van der Waals force interactions in density functional theory (DFT-D3BJ) calculations.

[0069] The results of calculations performed under the same conditions as those shown in Calculation 1, except for the conditions related to the functionals described above, are shown in Figures 6(A), 6(B), Tables 5 and 6. Figure 6(A) and Table 5 show the amount of change in energy ΔE caused by inserting an intercalant between the crystal layers of graphite. Also, Figure 6(B) and Table 6 show the amount of change in the c-axis length of the lattice ΔD caused by inserting an intercalant between the crystal layers of graphite.

[0070] [Table 5]

[0071] Elements with a negative ΔE value have the potential to enter between the crystalline layers of graphite. As shown in Figure 6(A) and the calculation results in Table 5, the elements that have the potential to enter between the crystalline layers of graphite are lithium, potassium, rubidium, cesium, calcium, strontium, barium, and lanthanum. As a result of calculation 2, it is believed that lanthanum may enter between the crystalline layers of graphite, and therefore lanthanoids other than lanthanum, as well as lanthanum, may also be elements that have the potential to enter between the crystalline layers of graphite.

[0072] [Table 6]

[0073] As shown in FIG. 6(B) and the calculation results in Table 6, it is predicted that all of the elements calculated this time will be able to expand the space between the graphite crystal layers more than when lithium is inserted.

[0074] Calculation 1 and Calculation 2 are calculations with different correction conditions for van der Waals forces. The calculation conditions for Calculation 1 are conditions that obtain a calculated value (0.523-0.530 nm) close to the measured value (0.535 nm) of the interlayer distance of KC8, and the calculation conditions for Calculation 2 are conditions that obtain a calculated value (0.359 nm-0.360 nm) close to the measured value (0.372 nm) of the interlayer distance of LiC6. In this way, calculations dealing with layered materials such as graphite may differ in calculation results depending on the correction conditions for van der Waals forces, so calculations were performed under multiple correction conditions.

[0075] Based on the results of Calculation 1 and Calculation 2 shown above, elements that can be used as the metal M will be considered. In at least one of Calculation 1 and Calculation 2, an element that has a negative energy change when inserted between the crystal layers of graphite can be used as the metal M. In other words, the metal M can be any one or more of potassium, rubidium, cesium, calcium, strontium, barium, and lanthanum (or lanthanoids). Among these, it is more preferable to use any one or both of potassium and barium as the metal M because of its high safety.

[0076] As the anion of the metal M salt, for example, bis(fluorosulfonyl)imide (FSI - ), bis(trifluoromethanesulfonyl)imide (TFSI - ), PF6 - , ClO4 - , BF4 - , and SCN - At least one anion among the above can be used.

[0077] When potassium is used as the metal M, at least one of potassium salts of potassium bis(fluorosulfonyl)imide (KFSI), potassium bis(trifluoromethanesulfonyl)imide (KTFSI), KPF6, KClO4, KBF4, and KSCN can be used. For an electrolyte that exhibits excellent battery characteristics in a low-temperature environment, it is preferable to use KFSI. The reason for this preference will be described later.

[0078] <Organic solvent> Examples of organic solvents include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc. One of these solvents, or a combination of two or more of these solvents in any combination and ratio can be used. Alternatively, an organic solvent exemplified below can be used as an organic solvent suitable for a low-temperature environment.

[0079] <<Organic Solvent 1 Suitable for Low-Temperature Environment>> As an example of an organic solvent suitable for a low-temperature environment, one containing EC, EMC, and DMC can be used. When the total amount of these EC, EMC, and DMC is 100 vol%, the volume ratio of EC, EMC, and DMC is x:y:100 - x - y (where 5 ≤ x ≤ 35 and 0 < y < 65). More specifically, an organic solvent containing EC, EMC, and DMC in a volume ratio of EC:EMC:DMC = 30:35:35 can be used. The above volume ratio may be the volume ratio before mixing the electrolytic solution, and the environment for mixing the electrolytic solution may be room temperature (typically 25°C).

[0080] EC is a cyclic carbonate and has a high relative permittivity, so it has the effect of promoting the dissociation of lithium salts. On the other hand, EC has a high viscosity and a high freezing point (melting point) of 38 °C. Therefore, when EC alone is used as an organic solvent, it is difficult to use it in a low-temperature environment. Thus, the organic solvent specifically described as one aspect of the present invention is not EC alone, but further includes EMC and DMC. EMC is a chain carbonate, which has the effect of lowering the viscosity of the electrolyte and has a freezing point of -54 °C. Also, DMC is also a chain carbonate, which has the effect of lowering the viscosity of the electrolyte and has a freezing point of -43 °C. An electrolyte prepared using an organic solvent in which EC, EMC, and DMC having such physical properties are mixed such that the total amount of these three organic solvents is 100 vol% and the volume ratio is x:y:100 - x - y (where 5 ≤ x ≤ 35 and 0 < y < 65) has the characteristic that its freezing point is -40 °C or lower.

[0081] A general electrolyte used in a lithium-ion battery solidifies at about -20 °C at the highest, so it is difficult to fabricate a battery that can be charged and discharged at -40 °C. The electrolyte described as an example in the present embodiment has a freezing point of -40 °C or lower, so a lithium-ion battery that can be charged and discharged even in a low-temperature environment of -40 °C can be realized.

[0082] <<Organic Solvent 2 Suitable for Low-Temperature Environment>> As another example of an organic solvent suitable for a low-temperature environment, it may include a fluorinated cyclic carbonate (sometimes referred to as a fluorinated cyclic carbonate) or a fluorinated chain carbonate (sometimes referred to as a fluorinated chain carbonate). Furthermore, it is preferable that the above organic solvent includes both a fluorinated cyclic carbonate and a fluorinated chain carbonate. Both the fluorinated cyclic carbonate and the fluorinated chain carbonate have a substituent exhibiting electron-withdrawing properties, and their solvation energy for lithium ions is lower than that of an organic compound having no substituent exhibiting electron-withdrawing properties. Therefore, both the fluorinated cyclic carbonate and the fluorinated chain carbonate are suitable as organic solvents.

[0083] As the fluorinated cyclic carbonate, fluoroethylene carbonate (also referred to as fluorinated ethylene carbonate, fluoroethylene carbonate, FEC, F1EC), difluoroethylene carbonate (DFEC, F2EC), trifluoroethylene carbonate (F3EC), tetrafluoroethylene carbonate (F4EC), etc. can be used. DFEC has isomers such as cis-4,5 and trans-4,5. Since all of the fluorinated cyclic carbonates have a substituent that exhibits electron-withdrawing properties, it is considered that the solvation energy of lithium ions is lower than that of EC.

[0084] The following structural formula (H10) is the structural formula of FEC, in which the electron-withdrawing substituent is an F group.

[0085] [ka]

[0086] Methyl 3,3,3-trifluoropropionate is an example of a fluorinated chain carbonate. The following structural formula (H22) is the structural formula of methyl 3,3,3-trifluoropropionate. The abbreviation for methyl 3,3,3-trifluoropropionate is "MTFP." In MTFP, the electron-withdrawing substituent is a CF3 group.

[0087] [ka]

[0088] An example of a fluorinated chain carbonate is trifluoromethyl 3,3,3-trifluoropropionate. The following structural formula (H23) is the structural formula of trifluoromethyl 3,3,3-trifluoropropionate. The electron-withdrawing substituent is a CF3 group.

[0089] [ka]

[0090] As a fluorinated chain carbonate, there is trifluoromethyl propionate. The following structural formula (H24) is the structural formula of trifluoromethyl propionate. The electron-withdrawing substituent is the CF3 group.

[0091] [Chemical formula]

[0092] As a fluorinated chain carbonate, there is methyl 2,2-difluoropropionate. The following structural formula (H25) is the structural formula of methyl 2,2-difluoropropionate. The electron-withdrawing substituent is the CF2 group.

[0093] [Chemical formula]

[0094] As the organic solvent included in the electrolytic solution which is one aspect of the present invention, it is preferable to include one or more selected from the above-described fluorinated cyclic carbonates and one or more selected from fluorinated chain carbonates. For example, the organic solvent described in this embodiment preferably includes FEC and MTFP. The reason will be explained.

[0095] <<FEC and MTFP>> FEC is a cyclic carbonate and has a high relative dielectric constant, so when used in an organic solvent, it has the effect of promoting the dissociation of lithium salts. On the other hand, FEC has a substituent that exhibits electron-withdrawing properties, so it is easier to desolvate with lithium ions than ethylene carbonate (EC). Specifically, the solvation energy of lithium ions in FEC is smaller than that of EC that does not have a substituent that exhibits electron-withdrawing properties. Therefore, it is easier to separate lithium ions on the surface of the positive electrode active material and the surface of the negative electrode active material, and the internal resistance of the secondary battery can be reduced. Furthermore, since FEC has a deep highest occupied molecular orbital (HOMO: Highest Occupied Molecular Orbital) level, it is less likely to be oxidized and its oxidation resistance is improved. On the other hand, there is a concern that FEC has a high viscosity. Therefore, it is recommended to use a mixed organic solvent containing not only FEC but also MTFP in the electrolyte. MTFP is a chain carbonate, and it is possible to have the effect of lowering the viscosity of the electrolyte, or maintaining the viscosity at room temperature (typically 25°C) even at low temperatures (typically 0°C). Furthermore, although MTFP has a smaller solvation energy than methyl propionate (abbreviated as "MP"), which does not have an electron-withdrawing substituent, it may form a solvate with lithium ions when used in an electrolyte.

[0096] The organic solvent described above is preferably highly purified with a low content of particulate waste or molecules other than the constituent molecules of the organic solvent (hereinafter, simply referred to as "impurities", including oxygen (O2), water (H2O) or moisture). It is also preferable that the reaction by-products during synthesis are suppressed through appropriate purification. Specifically, the impurity concentration of the electrolyte is 100 ppm or less, preferably 50 ppm or less, and more preferably less than 10 ppm. The concentration of moisture among the impurities can be detected by Karl Fischer titration.

[0097] Furthermore, it is preferable that the above-mentioned organic solvent has almost no peaks due to impurities confirmed by NMR measurement or the like. Almost no peaks can be confirmed includes that the ratio of the integrated area of ​​the peak due to the impurities to the integrated area of ​​the peak due to the main component (simply called integral ratio) is 0.005 or less, preferably 0.002 or less. The device used for NMR measurement is not particularly limited, but for example, Bruker's "AVANCE III 400 type" can be used. In addition, the central peak of the five peaks of acetonitrile derived from acetonitrile-d3 used as a solvent in 1H-NMR measurement can be 1.94 ppm.

[0098] For example, in the case of MTFP, it is known that when 1H-NMR is measured using acetonitrile-d3 solvent, four peaks occur at δ between 3.29 ppm and 3.43 ppm. However, if other peaks occur in the vicinity, for example, if a peak occurs at δ between 3.24 ppm and 3.29 ppm, the peak is considered to be due to impurities. Therefore, if the ratio (integral ratio) of the peak area between 3.24 ppm and 3.29 ppm to the peak area between 3.29 ppm and 3.43 ppm is 0.005 or less, preferably 0.002 or less, it can be said that the peaks due to impurities are almost not confirmed.

[0099] FEC and MTFP having such physical properties are preferably mixed and used in a volume ratio of x:100-x (where 5≦x≦30, preferably 10≦x≦20) with the total content of these two organic solvents being 100 vol%. The organic solvents are preferably mixed so that MTFP is greater than FEC. The volume ratio may be the volume ratio measured before mixing the organic solvents, and the outside air when mixing the organic solvents may be room temperature (typically 25° C.). An organic solvent mixed with FEC and MTFP is preferable because it exhibits a viscosity that allows operation as a lithium ion battery and maintains an appropriate viscosity even in a low-temperature environment.

[0100] Although FEC has been described as a representative above, any of the organic compounds described as fluorinated cyclic carbonates has the effect of promoting dissociation of lithium salts, has a small solvation energy and is easily solvated with lithium ions, and has a high viscosity, making it difficult to use in a low-temperature environment when used alone. Furthermore, although MTFP has been described as a representative above, any of the organic compounds described as fluorinated chain carbonates has the effect of reducing or maintaining the viscosity of the electrolyte solution, which is one embodiment of the present invention. Therefore, if the organic solvent, which is one embodiment of the present invention, contains a fluorinated cyclic carbonate and a fluorinated chain carbonate, it is possible to provide a lithium-ion battery that can be well inserted and removed from the negative electrode active material and can be charged and discharged in a wide temperature range, including low-temperature environments.

[0101] Therefore, the electrolyte solution in the battery of one embodiment of the present invention preferably contains a lithium salt, a metal M salt, and the above-mentioned "organic solvent 1 suitable for low-temperature environments" or "organic solvent 2 suitable for low-temperature environments."

[0102] As a specific example of the electrolyte solution used in the battery of one embodiment of the present invention, a configuration example of an electrolyte solution using LiPF6 as the lithium salt, a potassium salt as the metal M salt, and the above-mentioned "organic solvent 2 suitable for low-temperature environment" as the organic solvent will be described.

[0103] By using a potassium salt as the metal M salt and inserting potassium ions between the crystalline layers of graphite, the crystalline layers of graphite can be made wider than when lithium ions are inserted. This makes it easier for lithium to enter between the crystalline layers of graphite, and therefore a battery in which the potassium ions exist between the crystalline layers of graphite has improved charge / discharge characteristics in a low-temperature environment, which involve the insertion and desorption of lithium ions.

[0104] Here, the battery according to one embodiment of the present invention preferably uses an organic solvent suitable for low-temperature environments, which contains a lithium salt and a metal M salt (potassium salt in this case) in the electrolyte. In particular, it is particularly preferable to use a mixed solvent containing a fluorinated cyclic carbonate and a fluorinated chain carbonate, which has been described as the organic solvent 2 suitable for low-temperature environments.

[0105] A configuration in which the electrolyte contains a lithium salt and a metal M salt (here, a potassium salt) and uses the organic solvent suitable for the above-mentioned low-temperature environment will be described below.

[0106] When FEC was used as the fluorinated cyclic carbonate, MTFP was used as the fluorinated chain carbonate, and LiPF6 was dissolved in a mixed solvent to give an electrolyte solution containing these materials at a concentration of 1 mol / L, and potassium salt was then further dissolved in the electrolyte solution. When potassium hexafluorophosphate (KPF6) was used as the potassium salt, the potassium salt was difficult to dissolve in the electrolyte solution, and the amount of potassium salt that could be added to the electrolyte solution was small, and even with 0.05 mol / L KPF6, some potassium salt remained undissolved.

[0107] Therefore, it is preferable that the potassium salt used in the electrolyte of the battery of one embodiment of the present invention is not KPF6. For example, potassium bis(fluorosulfonyl)imide (KFSI) can be used as the potassium salt used in the electrolyte of the battery of one embodiment of the present invention. This potassium salt is preferable because it can dissolve even an electrolyte in which a lithium salt is dissolved in the mixed solvent described as the organic solvent 2 suitable for the low-temperature environment. Although details will be described in the examples, when KFSI is used as the potassium salt, 0.2 mol / L of KFSI can be dissolved in an electrolyte in which LiPF6 is dissolved to 1 mol / L in a mixed solvent containing FEC:MTFP=2:8 (volume ratio). Note that the above value of 0.2 mol / L does not indicate the upper limit for dissolving KFSI.

[0108] [Negative electrode 2] Here, we will explain items related to the negative electrode that were not explained in [Negative electrode 1].

[0109] <Binder> As the binder, it is preferable to use a rubber material such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Also, as the binder, fluororubber can be used.

[0110] Moreover, it is preferable to use, for example, a water-soluble polymer as the binder. For example, polysaccharides can be used as the water-soluble polymer. For example, carboxymethylcellulose (CMC) such as sodium carboxymethylcellulose (CMC-Na), cellulose derivatives such as methylcellulose, ethylcellulose, hydroxypropylcellulose, diacetylcellulose, and regenerated cellulose, or starch can be used as the polysaccharide. It is even more preferable to use these water-soluble polymers in combination with the above-mentioned rubber material.

[0111] Alternatively, it is preferable to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (polymethyl methacrylate, PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose as the binder.

[0112] The binder may be a combination of two or more of the above.

[0113] For example, a material having a particularly excellent viscosity adjusting effect may be used in combination with another material. For example, while rubber materials and the like have excellent adhesive strength and elasticity, it may be difficult to adjust the viscosity when mixed with a solvent. In such a case, it is preferable to mix the material with a material having a particularly excellent viscosity adjusting effect. For example, a water-soluble polymer may be used as a material having a particularly excellent viscosity adjusting effect. In addition, as a water-soluble polymer having a particularly excellent viscosity adjusting effect, the above-mentioned polysaccharides, for example, carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxypropylcellulose, and diacetylcellulose, cellulose derivatives such as regenerated cellulose, or starch may be used.

[0114] In addition, the solubility of cellulose derivatives such as carboxymethylcellulose is increased by converting them into salts such as sodium salt or ammonium salt of carboxymethylcellulose, and they are more likely to exhibit their effect as viscosity adjusters. The increased solubility can also increase the dispersibility with the active material or other components when preparing a slurry for an electrode. In this specification, the cellulose and cellulose derivatives used as the binder for an electrode include their salts.

[0115] Water-soluble polymers stabilize the viscosity by dissolving in water, and can stably disperse active materials and other materials combined as binders, such as styrene-butadiene rubber, in an aqueous solution. In addition, since they have functional groups, they are expected to be easily and stably adsorbed onto the surface of active materials. In addition, many cellulose derivatives, such as carboxymethyl cellulose, have functional groups such as hydroxyl groups or carboxyl groups, and since they have functional groups, they are expected to interact with each other and widely cover the surface of active materials.

[0116] When the binder covers the active material surface or contacts the surface to form a film, it is expected to play a role as a passive film and suppress the decomposition of the electrolyte. Here, the "passive film" is a film with no electrical conductivity or a film with extremely low electrical conductivity. For example, when a passive film is formed on the surface of the active material, the decomposition of the electrolyte can be suppressed at the battery reaction potential. Moreover, it is more preferable that the passive film suppresses electrical conductivity and can conduct lithium ions.

[0117] <Conductive material> The conductive material is also called a conductive agent or conductive assistant, and is made of a carbon material. By attaching the conductive material between a plurality of active materials, the active materials are electrically connected to each other, and the conductivity is increased. Note that the term "attachment" does not only refer to the physical adhesion between the active material and the conductive material, but also includes the case where a covalent bond is formed, the case where the conductive material is bonded by van der Waals forces, the case where the conductive material covers a part of the surface of the active material, the case where the conductive material is embedded in the surface irregularities of the active material, and the case where the two materials are electrically connected even if they are not in contact with each other.

[0118] The active material layers, such as the positive electrode active material layer and the negative electrode active material layer, preferably contain a conductive material.

[0119] As the conductive material, for example, one or more of carbon blacks such as acetylene black and furnace black, graphites such as artificial graphite and natural graphite, carbon fibers such as carbon nanofibers and carbon nanotubes, and graphene compounds can be used.

[0120] As the carbon fiber, for example, mesophase pitch carbon fiber, isotropic pitch carbon fiber, etc. can be used. In addition, as the carbon fiber, carbon nanofiber or carbon nanotube can be used. Carbon nanotube can be produced by, for example, vapor phase growth method.

[0121] The active material layer may also contain, as a conductive material, metal powder or metal fiber of copper, nickel, aluminum, silver, gold, or the like, a conductive ceramic material, or the like.

[0122] The content of the conductive material relative to the total amount of the active material layer is preferably 0.1 wt % or more and 10 wt % or less, and more preferably 1 wt % or more and 5 wt % or less.

[0123] Unlike particulate conductive materials such as carbon black, which are in point contact with the active material, the graphene compound allows for surface contact with low contact resistance, and therefore can improve the electrical conductivity between the particulate active material and the graphene compound with a smaller amount than that of a normal conductive material. This allows the ratio of the active material in the active material layer to be increased, thereby increasing the discharge capacity of the secondary battery.

[0124] Particulate carbon-containing compounds such as carbon black and graphite, or fibrous carbon-containing compounds such as carbon nanotubes, tend to enter microspaces. Microspaces refer to, for example, regions between a plurality of active materials. By using a combination of a carbon-containing compound that tends to enter microspaces and a sheet-like carbon-containing compound such as graphene that can impart conductivity across a plurality of particles, the density of the electrode can be increased and an excellent conductive path can be formed. The secondary battery obtained by the manufacturing method of one embodiment of the present invention has a high capacity density and can be stable, and is effective as an in-vehicle secondary battery.

[0125] <Current collector> As the current collector, a material having high conductivity and not alloyed with carrier ions such as lithium, such as metals such as stainless steel, gold, platinum, zinc, iron, copper, aluminum, and titanium, and alloys thereof, can be used. The current collector can be appropriately shaped in a sheet, mesh, punched metal, expanded metal, or other form. It is preferable to use a current collector having a thickness of 10 μm or more and 30 μm or less.

[0126] The negative electrode current collector is preferably made of a material that does not form an alloy with carrier ions such as lithium.

[0127] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer has a positive electrode active material, and may further have at least one of a conductive material and a binder. The positive electrode current collector, the conductive material, and the binder may be the same as those described in [Negative electrode 2].

[0128] The current collector may be a metal foil such as aluminum foil. The positive electrode may be formed by applying a slurry onto a metal foil and drying it. After drying, the positive electrode may be pressed. The positive electrode is formed by forming an active material layer on a current collector.

[0129] The slurry is a material liquid used to form an active material layer on a current collector, and contains an active material, a binder, and a solvent, and preferably further contains a conductive material. The slurry is also called an electrode slurry or an active material slurry, and when a positive electrode active material layer is formed, it is also called a positive electrode slurry.

[0130] <Cathode active material> A positive electrode active material according to one embodiment of the present invention will be described. As the positive electrode active material, lithium cobalt oxide and / or lithium nickel-cobalt-manganese oxide can be used.

[0131] As the lithium cobalt oxide, for example, lithium cobalt oxide to which magnesium is added is preferably used. Alternatively, lithium cobalt oxide to which magnesium, aluminum, nickel, and titanium are added is preferably used. Lithium cobalt oxide to which magnesium, aluminum, and nickel are added is preferably used. Lithium cobalt oxide that can be used in the battery 10 of one embodiment of the present invention will be described in detail as the positive electrode active material 100 in Embodiments 2 and 3.

[0132] As the lithium nickel-cobalt-manganese oxide, for example, lithium nickel-cobalt-manganese oxide having an atomic ratio of nickel:cobalt:manganese=1:1:1, nickel:cobalt:manganese=6:2:2, nickel:cobalt:manganese=8:1:1, nickel:cobalt:manganese=9:0.5:0.5, etc. may be used. In addition, as the lithium nickel-cobalt-manganese oxide, it is preferable to use lithium nickel-cobalt-manganese oxide to which one or more of aluminum, calcium, barium, strontium, and gallium have been added.

[0133] As a positive electrode active material that can be used in a low-temperature environment, it is preferable to use the lithium cobalt oxide described in embodiment 2 or embodiment 3. The lithium cobalt oxide described in embodiment 2 or embodiment 3 is a positive electrode active material that can be used up to a high charging voltage (hereinafter also referred to as "high charging voltage") and is a positive electrode active material that can insert and extract lithium ions at low temperatures.

[0134] In this specification, unless otherwise specified, the "charging voltage" is expressed based on the potential of lithium metal. In this specification, the "high charging voltage" is, for example, a charging voltage of 4.6V or more, preferably 4.65V or more, more preferably 4.7V or more, even more preferably 4.75V or more, and most preferably 4.8V or more. As the positive electrode active material, two or more materials with different particle sizes and / or compositions can be used as long as they are materials that are less likely to deteriorate with charging and discharging even at high charging voltages. In this specification, the term "different composition" includes not only the case where the composition of elements contained in the material is different, but also the case where the ratio of elements contained in the material is different even if the composition of elements contained in the material is the same.

[0135] As described above, in this specification, the "high charging voltage" is defined as 4.6 V or more based on the potential when the negative electrode is lithium metal, but when the potential when the negative electrode is graphite is used as the reference, the "high charging voltage" is 4.5 V or more. In short, in the case of a half cell in which lithium metal is used as the negative electrode, the charging voltage of 4.6 V or more is called the high charging voltage, and in the case of a full cell in which graphite is used as the negative electrode, the charging voltage of 4.5 V or more is called the high charging voltage.

[0136] <Second Positive Electrode Active Material> The positive electrode of one embodiment of the present invention can include a second positive electrode active material in addition to the above-described positive electrode active material containing lithium. The second positive electrode active material includes a metal M and is capable of inserting and releasing ions of the metal M during charging and discharging the battery.

[0137] When potassium is used as the metal M, the second positive electrode active material may be, for example, K x MnO2, K x CoO2, K x V2O5, K x CrO2, K x Fe 0.5 Mn 0.5 O2, K x Mn 0.8 Fe 0.2 O2, K x Co 0.5 Mn 0.5 O2, K x Ni 0.05 Mn 0.95 O2, K x Mn 0.7 Ni 0.3 O2, K x Mn 0.8 Fe 0.1 Ni 0.1 O2 and K x Fe 0.1 Mn 0.8 Ti 0.1 O2. Any one or more of the following can be used. Note that x is 0 or more and 1 or less. Among them, K x MnO2, K x CoO2, K x V2O5, Kx It is preferable to use one or more of CrO2. In this example, the second positive electrode active material can be called a positive electrode active material having potassium. A positive electrode having a positive electrode active material having potassium in addition to a positive electrode active material having lithium can insert and remove lithium ions and potassium ions.

[0138] A positive electrode having a second positive electrode active material in addition to a positive electrode active material having lithium can be formed by applying a positive electrode slurry having a positive electrode active material having lithium and a second positive electrode active material onto a metal foil and drying the slurry. Note that pressing may be performed after drying.

[0139] [Ion insertion / desorption] In the battery according to one embodiment of the present invention, the electrolyte contains a lithium salt and a metal M salt, and graphite is used for the negative electrode. The insertion and desorption of ions (cations) will be described below. Note that the following description will be given of an example in which a potassium salt is used as the metal M salt.

[0140] In conventional lithium ion batteries, lithium ions are inserted into or extracted from the negative electrode active material and the electrolyte solution, and the positive electrode active material and the electrolyte solution.

[0141] In one example of a battery according to one embodiment of the present invention, when the electrolyte contains a lithium salt and a metal M salt and the positive electrode contains only a positive electrode active material containing lithium, lithium ions and potassium ions are inserted or removed from the negative electrode, and only lithium ions are inserted or removed from the positive electrode.

[0142] Alternatively, in another example of the battery of one embodiment of the present invention, when the electrolyte contains a lithium salt and a metal M salt and the positive electrode contains a second positive electrode active material in addition to a positive electrode active material containing lithium, lithium ions and potassium ions are inserted and removed from the negative electrode, and lithium ions and potassium ions are inserted and removed from the positive electrode, respectively.

[0143] In this manner, in the positive electrode and negative electrode of the battery according to one embodiment of the present invention, lithium ions and / or metal M ions are inserted into or extracted from the positive electrode or negative electrode in association with a charge reaction or a discharge reaction.

[0144] In addition, for example, in a low-temperature environment, when the metal M ion has a lower reaction resistance with the positive electrode or negative electrode compared to the lithium ion, it is considered that the metal M ion may contribute more to the charge / discharge reaction of the battery.

[0145] [Separator] A separator is disposed between the positive electrode and the negative electrode. For example, the separator may be made of polyimide, polyolefin, cellulose fiber, nonwoven fabric, glass fiber, ceramics, or nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester, acrylic, polyurethane fiber, etc. The separator is preferably processed into a bag shape and disposed so as to encase either the positive electrode or the negative electrode.

[0146] The separator may have a multi-layer structure. For example, an organic material film such as polypropylene, polyethylene, polyimide, etc. may be coated with a ceramic material, a fluorine material, a polyamide material, or a mixture of these. For example, aluminum oxide particles, silicon oxide particles, etc. may be used as the ceramic material. For example, PVDF, polytetrafluoroethylene, etc. may be used as the fluorine material. For example, nylon, aramid (meta-aramid, para-aramid), etc. may be used as the polyamide material.

[0147] [Exterior body] The exterior body of the battery may be made of a metal material such as aluminum, stainless steel, or titanium. Alternatively, a film-shaped exterior body may be used. As the film-shaped exterior body, a three-layer structure film may be used in which a metal thin film or metal foil having excellent flexibility such as aluminum, stainless steel, titanium, copper, or nickel is provided on a film made of a resin material such as polyethylene, polypropylene, polycarbonate, ionomer, or polyamide, and an insulating synthetic resin film such as a polyamide resin or polyester resin is provided on the metal thin film as the outer surface of the exterior body. Such a multilayer structure film may be called a laminate film. In this case, the laminate film may be called an aluminum (aluminum) laminate film, a stainless steel laminate film, a titanium laminate film, a copper laminate film, a nickel laminate film, or the like, using the material name of the metal layer of the laminate film.

[0148] The material or thickness of the metal layer of the laminate film may affect the flexibility of the battery. For example, an aluminum laminate film having a polypropylene layer, an aluminum layer, and nylon is preferably used as an exterior body for a battery with excellent flexibility (bendability). Here, the thickness of the aluminum layer is preferably 50 μm or less, more preferably 40 μm or less, more preferably 30 μm or less, and more preferably 20 μm or less. If the aluminum layer is thinner than 10 μm, there is a concern that the gas barrier property may be reduced due to pinholes in the aluminum layer, so the thickness of the aluminum layer is desirably 10 μm or more.

[0149] [Laminated secondary battery and its manufacturing method] 7 and 8 are external views of a laminated secondary battery 500 as an example of the battery 10 of one embodiment of the present invention. Note that the shape of the battery 10 of one embodiment of the present invention is not limited to a laminated type and may be a cylindrical type, a square type, a coin type, or the like.

[0150] An example of a method for manufacturing a laminated secondary battery will be described with reference to Fig. 8(A) to Fig. 8(C). As shown in Fig. 8(A) to Fig. 8(C), the laminated secondary battery has a positive electrode 503, a negative electrode 506, a separator 507, an outer casing 509, a positive electrode lead electrode 510, and a negative electrode lead electrode 511 as components. As shown in Fig. 8(A), the positive electrode 503 has a positive electrode current collector 501 and a positive electrode active material layer 502, and the negative electrode 506 has a negative electrode current collector 504 and a negative electrode active material layer 505. If the laminated secondary battery has a flexible structure, the secondary battery can be bent according to the deformation of the electronic device when it is mounted on an electronic device having at least a part having flexibility.

[0151] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. FIG. 8(B) shows the laminated negative electrode 506, the separator 507, and the positive electrode 503. Here, an example is shown in which five pairs of negative electrodes and four pairs of positive electrodes are used. Next, the tab regions of the positive electrodes 503 are bonded to each other, and the positive electrode lead electrode 510 is bonded to the tab region of the outermost positive electrode. For example, ultrasonic welding or the like may be used for the bonding. Similarly, the tab regions of the negative electrodes 506 are bonded to each other, and the negative electrode lead electrode 511 is bonded to the tab region of the outermost negative electrode.

[0152] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .

[0153] Next, as shown in Fig. 8(C), exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of exterior body 509 is joined. For the joining, for example, thermocompression bonding or the like may be used. At this time, a region (hereinafter referred to as an inlet) that is not joined is provided in a part (or one side) of exterior body 509 so that an electrolyte can be introduced later.

[0154] Next, an electrolyte (not shown) is introduced into the inside of the exterior body 509 through an inlet provided in the exterior body 509. The introduction of the electrolyte is preferably performed under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is joined. In this manner, the laminate type secondary battery 500 can be produced.

[0155] By using the positive electrode active material described in Embodiment 2 or 3 for the positive electrode 503, the secondary battery 500 can have a high discharge capacity and excellent cycle characteristics.

[0156] This embodiment mode can be used in appropriate combination with other embodiment modes.

[0157] (Embodiment 2) In this embodiment, a positive electrode active material 100 that can be used for a battery 10 of one embodiment of the present invention will be described with reference to FIGS.

[0158] Fig. 9(A) is a cross-section of a positive electrode active material 100 that can be used for a battery 10 of one embodiment of the present invention. Fig. 9(B) is a schematic diagram of an element concentration distribution when measuring from the surface toward the inside in a cross-sectional analysis including the surface and a surface layer portion of the positive electrode active material 100. Measurement from the surface toward the inside is also called measurement in the depth direction, and the X1-X2 and Y1-Y2 arrows in Fig. 9(A) are an example of the depth direction.

[0159] As shown in Fig. 9(A), the positive electrode active material 100 has a surface layer portion 100a and an inner portion 100b. In Fig. 9(A), the boundary between the surface layer portion 100a and the inner portion 100b is indicated by a dashed line. (001) in the figure indicates the (001) plane of LiMO2. LiMO2 belongs to the space group R-3m.

[0160] In the present specification, the surface layer 100a of the positive electrode active material 100 refers to, for example, a region within 50 nm from the surface toward the inside, more preferably within 35 nm from the surface toward the inside, even more preferably within 20 nm from the surface toward the inside, and most preferably within 10 nm from the surface toward the inside, perpendicular or approximately perpendicular from the surface. Note that approximately perpendicular is 80° or more and 100° or less. Surfaces caused by cracks and / or cracks may also be called the surface. The surface layer 100a is synonymous with the surface vicinity, surface vicinity region, or shell.

[0161] The region deeper than the surface layer 100a of the positive electrode active material is referred to as the inner portion 100b, which is synonymous with the inner region or the core.

[0162] In addition, when the positive electrode active material 100 has a layered rock salt type crystal structure of space group R-3m, the surface layer portion 100a has an edge region and a basal region. Here, the edge region has a surface exposed in a direction intersecting with the (001) plane (also referred to as a surface other than the (001) orientation), and the edge region is a region within 50 nm from the surface toward the inside, more preferably within 35 nm from the surface toward the inside, even more preferably within 20 nm from the surface toward the inside, and most preferably within 10 nm perpendicular or approximately perpendicular from the surface toward the inside. Note that, intersecting here means that the angle between the perpendicular line of the first surface ((001) plane) and the normal line of the second surface (surface of the positive electrode active material 100) is 10 degrees or more and 90 degrees or less, more preferably 30 degrees or more and 90 degrees or less, and even more preferably 50 degrees or more and 90 degrees or less.

[0163] The basal region has a surface parallel to the (001) plane (also referred to as a (001)-oriented surface), and is a region within 50 nm from the surface toward the inside, more preferably within 35 nm from the surface toward the inside, even more preferably within 20 nm from the surface toward the inside, and most preferably within 10 nm perpendicular or approximately perpendicular from the surface toward the inside. Note that "parallel" here means that the angle between the perpendicular to the first surface (the (001) plane) and the normal to the second surface (the surface of the positive electrode active material 100) is 0 degrees or more and less than 10 degrees, preferably 0 degrees or more and 5 degrees or less, more preferably 0 degrees or more and 2.5 degrees or less.

[0164] The surface of the positive electrode active material 100 refers to the surface of the composite oxide including the surface layer portion 100a and the interior portion 100b. Therefore, the positive electrode active material 100 does not include metal oxides such as aluminum oxide (Al2O3) that do not have lithium sites that can contribute to charging and discharging, carbonates chemically adsorbed after the preparation of the positive electrode active material, hydroxyl groups, etc. The attached metal oxide refers to, for example, a metal oxide whose crystal structure does not match that of the interior portion 100b.

[0165] In addition, the positive electrode active material 100 does not include the electrolyte, organic solvent, binder, conductive material, or compounds derived from these that are attached to the positive electrode active material 100 .

[0166] Although not shown, the positive electrode active material 100 may have a crystal grain boundary. The crystal grain boundary refers to, for example, a portion where particles of the positive electrode active material 100 are adhered to each other, a portion where the crystal orientation changes inside the positive electrode active material 100, that is, a portion where the repetition of bright and dark lines in a STEM image or the like becomes discontinuous, a portion containing many crystal defects, a portion where the crystal structure is disordered, and the like. The crystal defect refers to a defect that can be observed in a cross-sectional TEM (transmission electron microscope) or a cross-sectional STEM image, that is, a structure in which other atoms have entered between lattices, a cavity, and the like. The crystal grain boundary can be said to be one of the plane defects. The vicinity of the crystal grain boundary refers to a region within 10 nm from the crystal grain boundary.

[0167] <Contained elements> The positive electrode active material 100 is a material containing lithium and a transition metal M T , oxygen, and an additive element. Transition metal M T is at least one selected from cobalt, nickel, and manganese. Alternatively, the positive electrode active material 100 is a mixture of lithium and a transition metal M T The composite oxide (LiM T However, the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention may have any distribution or crystal structure of the additive element described below. T :O=1:1:2 (atomic ratio) is not limited to this.

[0168] The positive electrode active material of a lithium ion secondary battery needs to contain a transition metal capable of oxidation and reduction in order to maintain charge neutrality even when lithium ions are inserted and removed. The positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention contains a transition metal M that is responsible for the oxidation and reduction reaction. T It is preferable to mainly use cobalt as the transition metal. When cobalt is 75 atomic % or more, preferably 90 atomic % or more, and more preferably 95 atomic % or more among the transition metals contained in the positive electrode active material 100, it is preferable because it has many advantages such as being relatively easy to synthesize and easy to handle, and having excellent cycle characteristics.

[0169] The transition metal M of the positive electrode active material 100 T When cobalt is 75 atomic % or more, preferably 90 atomic % or more, and more preferably 95 atomic % or more, the stability is superior when a large amount of lithium is released by charging, compared to composite oxides in which nickel accounts for the majority of the transition metal, such as lithium nickel oxide (LiNiO2). This is thought to be because cobalt is less affected by distortion due to the Jahn-Teller effect than nickel. The strength of the Jahn-Teller effect in transition metal compounds varies depending on the number of electrons in the d orbital of the transition metal. When low-spin nickel (III) in octahedrally coordinated structures, such as lithium nickel oxide, is used as a transition metal M, the transition metal M is more stable than when cobalt is used as a transition metal. T In layered rock-salt complex oxides, which account for the majority of the nickel-oxygen octahedrons, the Jahn-Teller effect is significant, and the layers, which are made up of nickel and oxygen octahedra, are easily distorted. This raises concerns that the crystal structure may collapse during charge-discharge cycles. Nickel ions are also larger than cobalt ions, and are close in size to lithium ions. This is why nickel, as in lithium nickel oxide, is a transition metal M T In the layered rock-salt type composite oxides, which account for the majority of the above, there is a problem that cation mixing of nickel and lithium is likely to occur.

[0170] The additive elements contained in the positive electrode active material 100 are preferably one or more selected from magnesium, titanium, nickel, aluminum, fluorine, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine, and beryllium.

[0171] That is, the positive electrode active material 100 may include lithium cobalt oxide to which magnesium and titanium are added, lithium cobalt oxide to which magnesium, titanium, and fluorine are added, lithium cobalt oxide to which magnesium, nickel, aluminum, and titanium are added, lithium cobalt oxide to which magnesium, nickel, aluminum, titanium, and fluorine are added, lithium cobalt oxide to which magnesium is added, lithium cobalt oxide to which magnesium and fluorine are added, lithium cobalt oxide to which magnesium, nickel, and aluminum are added, lithium cobalt oxide to which magnesium, nickel, aluminum, and fluorine are added, and the like.

[0172] The additive element is preferably in a solid solution in the positive electrode active material 100. For this reason, for example, when performing a line analysis by STEM-EDX, the depth at which the amount of the additive element detected increases is the depth at which the amount of the transition metal M T It is preferable that the positive electrode active material 100 is located at a position deeper than the depth at which the amount of the detected positive electrode active material 100 increases, that is, on the inner side of the positive electrode active material 100 .

[0173] In this specification and the like, the depth at which the amount of a certain element detected in a STEM-EDX line analysis increases refers to the depth at which measurement values ​​that can be determined to be not noise in terms of intensity, spatial resolution, etc., are successively obtained.

[0174] As described below, these additive elements further stabilize the crystal structure of the positive electrode active material 100. In this specification and the like, the additive element is synonymous with a mixture or a part of a raw material.

[0175] The additive element does not necessarily have to include fluorine, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine, or beryllium.

[0176] For example, if the positive electrode active material 100 is substantially free of manganese, the above-mentioned advantages of being relatively easy to synthesize and easy to handle, and having excellent cycle characteristics, will be even greater. The weight of manganese contained in the positive electrode active material 100 is preferably, for example, 600 ppm or less, more preferably 100 ppm or less.

[0177] The positive electrode active material 100 has the above-mentioned additive element in the surface layer portion 100a. It is more preferable that the positive electrode active material 100 has a plurality of additive elements. It is preferable that the surface layer portion 100a has a higher concentration of one or more selected from the additive elements than the inner portion 100b. Alternatively, it is preferable that the surface layer portion 100a has a larger detected amount of one or more selected from the additive elements than the inner portion 100b. It is also preferable that the one or more selected from the additive elements contained in the positive electrode active material 100 have a concentration gradient.

[0178] It is more preferable that the distribution of the positive electrode active material 100 differs depending on the added element. For example, it is more preferable that the depth of the peak of the detection amount in the surface layer portion from the surface or a reference point in EDX ray analysis described later differs depending on the added element. The detection amount peak here refers to the maximum value of the detection amount at 50 nm or less from the surface of the surface layer portion 100a. The detection amount refers to, for example, the count in EDX ray analysis.

[0179] 〔titanium〕 The presence of titanium as an additive element in the surface layer portion 100a is expected to promote the insertion and desorption of lithium ions into and from the positive electrode active material 100. On the other hand, if the titanium concentration is too high, or if the region containing only titanium is too wide, the layered rock salt type crystal structure of the positive electrode active material 100 may be distorted. Therefore, it is preferable that other additive elements, such as nickel and magnesium, are also present in the surface layer portion 100a. It is expected that the distortion of the crystal structure is alleviated by the other additive elements such as nickel and magnesium.

[0180] 〔distribution〕 In order to achieve the above effects, it is preferable that at least magnesium, nickel, and titanium among the additive elements have a higher concentration in the surface layer 100a than in the inside 100b, as shown in FIG. 9(B). Or, it is preferable that the detection amount of the surface layer 100a is larger than that of the inside 100b. Furthermore, it is preferable that the detection amount peak is in a region closer to the surface in the surface layer 100a. For example, it is preferable that the detection amount peak is on the surface or within 3 nm from the reference point. It is also preferable that the distributions of magnesium and nickel overlap. The detection amount peaks of magnesium and nickel may be at the same depth, or the magnesium peak may be closer to the surface, or the nickel peak may be closer to the surface. The difference in depth between the detection amount peak of nickel and the detection amount peak of magnesium is preferably within 3 nm, and more preferably within 1 nm. It is also preferable that the half-width of the detection amount peak is narrow.

[0181] Similarly, it is preferable that the distributions of magnesium and titanium overlap. The peaks of the detected amounts of magnesium and titanium may be at the same depth, or the peak of magnesium may be closer to the surface, or the peak of titanium may be closer to the surface. The difference in depth between the peak of the detected amount of titanium and the peak of the detected amount of magnesium is preferably within 3 nm, and more preferably within 1 nm. It is also preferable that the half-width of the detected amount is narrow.

[0182] In other words, it is preferable that the distributions of magnesium, nickel, and titanium overlap. The difference in depth between the peak of the detected amount of titanium, the peak of the detected amount of nickel, and the peak of the detected amount of magnesium is preferably within 3 nm, and more preferably within 1 nm. In addition, it is preferable that the half-width of the detected amount is narrow.

[0183] The above-mentioned region where the distributions of magnesium and nickel overlap, the region where the distributions of magnesium and titanium overlap, or the region where the distributions of magnesium, nickel, and titanium overlap is preferably in the edge region where lithium ions are inserted and removed in the surface layer portion 100a. That is, the distribution of the additive element shown in the schematic diagram of FIG. 9(B) is preferably observed in the direction of the arrow X1-X2 in FIG. 9(A). On the other hand, the above-mentioned overlapping region is not necessarily required in the basal region of the surface layer portion 100a.

[0184] Furthermore, the amount of nickel detected in the interior 100b may be very small compared to the surface layer 100a, or may not be detected, or may be 1 atomic % or less.

[0185] Although not shown, it is preferable that the amount of fluorine detected in the surface layer 100a is greater than the amount of fluorine detected inside, similar to magnesium or nickel. It is also preferable that the surface layer 100a has a peak of the amount of detection closer to the surface. For example, it is preferable that the peak of the amount of detection is on the surface or within 3 nm from the reference point. Similarly, it is preferable that the amount of silicon, phosphorus, boron and / or calcium detected in the surface layer 100a is greater than the amount of detection inside. It is also preferable that the surface layer 100a has a peak of the amount of detection closer to the surface. For example, it is preferable that the peak of the amount of detection is on the surface or within 3 nm from the reference point.

[0186] Of the added elements, at least aluminum preferably has a peak of detection amount inside magnesium and titanium. As shown in FIG. 9(B), the distributions of magnesium and aluminum may overlap, but there may be almost no overlapping area. The peak of detection amount of aluminum may be present in the surface layer portion 100a, or may be deeper than the surface layer portion 100a. For example, it is preferable that the peak is present on the surface, or in a region from 5 nm to 30 nm from the reference point toward the inside.

[0187] The distribution of aluminum as described above can further stabilize the layered rock-salt crystal structure of the positive electrode active material 100. For example, it is expected that the change from the layered rock-salt crystal structure to a spinel crystal structure in the surface layer 100a of the positive electrode active material 100 can be suppressed. Note that the spinel crystal structure generated in the layered rock-salt crystal structure is formed by the addition of a transition metal M T The lithium ions may move or spread accompanied by the movement of charges of the positive electrode active material 100. Furthermore, defects such as grain boundaries in the positive electrode active material 100 may become a diffusion path for lithium ions in the c-axis direction. Additive elements such as aluminum may be contained in the vicinity of the defects. In other words, it can be said that the presence of aluminum may facilitate the diffusion of lithium ions.

[0188] The reason why aluminum is distributed deeper into the material than magnesium and titanium is believed to be because the diffusion rate of aluminum is faster than that of magnesium and titanium. On the other hand, the amount of aluminum detected in the area closest to the surface is low, presumably because aluminum is more stable in areas where magnesium and other elements are not present than in areas where they are dissolved in high concentrations.

[0189] More specifically, in the region of the layered rock-salt type of space group R-3m or the cubic rock-salt type of space group, where magnesium is dissolved at a high concentration, the distance between the cation and oxygen is longer than in the layered rock-salt type LiAlO2, making it difficult for aluminum to exist stably. + Mg 2+ The valence change due to substitution to Co 3+From Co 2+ However, since Al can only be trivalent, it is thought that it is difficult for it to exist stably near magnesium in the rock salt or layered rock salt structure.

[0190] Although not shown, it is preferable that manganese has a detection amount peak inside magnesium, similar to aluminum.

[0191] However, the additive element does not necessarily have to have the same concentration gradient or distribution throughout the entire surface layer portion 100a of the positive electrode active material 100.

[0192] The (001)-oriented surface of the positive electrode active material 100 may have a different distribution of additive elements from the other surfaces. For example, the (001)-oriented surface and its surface layer 100a may have a lower detection amount of one or more additive elements selected from the additive elements compared to surfaces other than the (001)-oriented surface. Specifically, the detection amount of one or more of magnesium, nickel, and titanium may be low. Alternatively, the (001)-oriented surface and its surface layer 100a may have one or more additive elements not detected or the detection amount is 1 atomic % or less. Specifically, the detection amount of nickel may be not detected or 1 atomic % or less. In particular, in the case of an analysis method that detects characteristic X-rays such as EDX, since the energy of Kβ of cobalt and Kα of nickel are close, it is difficult to detect a trace amount of nickel in a material in which cobalt is the main element. Alternatively, the (001)-oriented surface and its surface layer 100a may have a peak of one or more additive elements detected shallower from the surface compared to surfaces other than the (001)-oriented surface. Specifically, the (001) oriented surface and its surface layer 100a may have peak positions of the detected amounts of magnesium and aluminum that are shallower than those of surfaces other than the (001) oriented surface.

[0193] In the layered rock-salt crystal structure of R-3m, the cations are arranged parallel to the (001) plane. TIt can be said that the structure is one in which O2 layers and lithium layers are alternately stacked parallel to the (001) plane. Therefore, the diffusion path of lithium ions also exists parallel to the (001) plane.

[0194] M T Since the O2 layer is relatively stable, it is more stable for the surface of the positive electrode active material 100 to have a (001) orientation. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) plane.

[0195] On the other hand, the diffusion path of lithium ions is exposed on the surface other than the (001) orientation. Therefore, the surface and the surface layer 100a other than the (001) orientation are important regions for maintaining the diffusion path of lithium ions, and at the same time, they are regions from which lithium ions are first desorbed and are therefore prone to become unstable. Therefore, it is extremely important to reinforce the surface and the surface layer 100a other than the (001) orientation in order to maintain the crystal structure of the entire positive electrode active material 100.

[0196] Therefore, in the positive electrode active material 100 according to another embodiment of the present invention, it is important that the distribution of the additive elements in the surface other than the (001) orientation and the surface layer 100a thereof is, for example, as shown in FIG. 9B. Of the additive elements, nickel is particularly preferably detected in the surface other than the (001) orientation and the surface layer 100a thereof. On the other hand, the concentration of the additive element in the (001) oriented surface and the surface layer 100a thereof may be low or absent as described above.

[0197] For example, the magnesium distribution in the (001) oriented surface and its surface layer 100a preferably has a half-width of 10 nm to 200 nm, more preferably 50 nm to 150 nm, and even more preferably 80 nm to 120 nm. Also, the magnesium distribution in the non-(001) oriented surface and its surface layer 100a preferably has a half-width of more than 200 nm to 500 nm, more preferably more than 200 nm to 300 nm, and even more preferably 230 nm to 270 nm.

[0198] The nickel distribution in the non-(001) oriented surface and in the surface layer 100a thereof preferably has a half-width of 30 nm to 150 nm, more preferably 50 nm to 130 nm, and even more preferably 70 nm to 110 nm.

[0199] High-purity LiM, which will be described in a later embodiment. T In the method of preparing O2, the additive elements are mixed and heated, and the additive elements spread mainly through the diffusion path of lithium ions. Therefore, it is easy to make the distribution of the additive elements in the surface other than the (001) orientation and the surface layer portion 100a thereof into a preferred range.

[0200] 〔magnesium〕 Magnesium is divalent, and magnesium ions are more stable at the lithium site than at the cobalt site in the layered rock-salt crystal structure, so they are more likely to enter the lithium site. The presence of magnesium at an appropriate concentration at the lithium site of the surface layer 100a makes it easier to maintain the layered rock-salt crystal structure. This is because magnesium present at the lithium site is M T It is speculated that this is because it acts as a pillar supporting the O2 layers. x When x in CoO2 is, for example, 0.24 or less, the detachment of oxygen from around magnesium can be suppressed. In addition, the presence of magnesium is expected to increase the density of the positive electrode active material 100. In addition, if the magnesium concentration in the surface layer portion 100a is high, it is expected that the corrosion resistance against hydrofluoric acid generated by decomposition of the electrolyte solution will be improved.

[0201] If magnesium is present at an appropriate concentration, it does not adversely affect the insertion and desorption of lithium during charging and discharging, and the above-mentioned benefits can be enjoyed. However, if there is an excess of magnesium, it may adversely affect the insertion and desorption of lithium. Furthermore, the effect of stabilizing the crystal structure may be reduced. This is thought to be because magnesium enters the cobalt site in addition to the lithium site. In addition, unnecessary magnesium compounds (oxides, fluorides, etc.) that do not substitute for either the lithium site or the cobalt site may segregate on the surface of the positive electrode active material, and may become resistance components of the secondary battery. In addition, as the magnesium concentration of the positive electrode active material increases, the discharge capacity of the positive electrode active material may decrease. This is thought to be because too much magnesium enters the lithium site, reducing the amount of lithium that contributes to charging and discharging.

[0202] Therefore, it is preferable that the amount of magnesium contained in the entire positive electrode active material 100 is appropriate. For example, the number of magnesium atoms is preferably 0.002 to 0.06 times the number of cobalt atoms, more preferably 0.005 to 0.03 times, and even more preferably about 0.01 times. The amount of magnesium contained in the entire positive electrode active material 100 may be a value obtained by performing elemental analysis of the entire positive electrode active material 100 using, for example, GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material 100.

[0203] 〔nickel〕 Nickel is LiM T In the layered rock salt crystal structure of O2, it can exist in either the cobalt site or the lithium site. When it exists in the cobalt site, it has a lower redox potential than cobalt, so it can be said that it is easier to release lithium and electrons during charging, for example. This is expected to increase the charge and discharge speed. Therefore, even with the same charging voltage, the transition metal M T However, a larger charge / discharge capacity can be obtained with nickel than with cobalt.

[0204] In addition, when nickel is present at the lithium site, the shift in the layered structure consisting of octahedra of cobalt and oxygen can be suppressed. The change in volume caused by charging and discharging is also suppressed. The elastic modulus also increases, that is, the material becomes harder. This is because nickel present at the lithium site also has a large effect on the M T This is presumably because they function as pillars supporting the O2 layers. Therefore, it is expected that the crystal structure will be more stable especially at high temperatures, for example, at 45°C or higher in the charged state, which is preferable.

[0205] In addition, the distance between the cations and anions of nickel oxide (NiO) is closer to the average distance between the cations and anions of LiCoO2 than to the rock-salt type MgO and rock-salt type CoO, and the orientation is more likely to match that of LiCoO2.

[0206] In addition, the order of ionization tendency is lowest for magnesium, followed by aluminum, cobalt, and nickel (Mg>Al>Co>Ni). Therefore, nickel is thought to be less likely to dissolve into the electrolyte during charging than the other elements listed above. Therefore, it is thought to have a high effect of stabilizing the crystal structure of the surface layer when in a charged state.

[0207] Furthermore, nickel is Ni 2+ , Ni 3+ , Ni 4+ Of which, Ni 2+ is the most stable, and nickel has a higher trivalent ionization energy than cobalt. Therefore, it is known that nickel and oxygen alone do not form a spinel crystal structure. Therefore, nickel is thought to have the effect of suppressing the phase change from the layered rock salt type to the spinel type crystal structure.

[0208] On the other hand, an excess of nickel is undesirable because it increases the influence of distortion due to the Jahn-Teller effect, and may also adversely affect the insertion and extraction of lithium.

[0209] Therefore, it is preferable that the amount of nickel contained in the entire positive electrode active material 100 is appropriate. For example, the number of nickel atoms contained in the positive electrode active material 100 is preferably more than 0% and 7.5% or less of the number of cobalt atoms, more preferably 0.05% to 4%, more preferably 0.1% to 2%, and more preferably 0.2% to 1%. Alternatively, more than 0% and 4% or less is preferable. Alternatively, more than 0% and 2% or less is preferable. Alternatively, more than 0.05% to 7.5% or less is preferable. Alternatively, more than 0.1% to 7.5% or less is preferable. Alternatively, more than 0.1% to 4% or less is preferable. The amount of nickel shown here may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.

[0210] 〔aluminum〕 Aluminum can also be present at the cobalt site in the layered rock salt crystal structure. Aluminum is a typical trivalent element and its valence does not change, so lithium around the aluminum is less likely to move during charging and discharging. Therefore, aluminum and the lithium around it function as columns, and can suppress changes in the crystal structure. Therefore, as described below, even if the positive electrode active material 100 is subjected to a force that causes it to expand and contract in the c-axis direction due to the insertion and removal of lithium ions, that is, even if a force that causes it to expand and contract in the c-axis direction is applied by changing the charge depth or charge rate, deterioration of the positive electrode active material 100 can be suppressed.

[0211] Aluminum also has the effect of suppressing the dissolution of surrounding cobalt and improving the continuous charging resistance. Furthermore, since the Al-O bond is stronger than the Co-O bond, it is possible to suppress the desorption of oxygen from the surroundings of aluminum. These effects improve the thermal stability. Therefore, when aluminum is contained as an additive element, the safety of the positive electrode active material 100 when used in a secondary battery can be improved. Furthermore, the positive electrode active material 100 can be made to have a crystal structure that is less likely to collapse even when repeatedly charged and discharged.

[0212] On the other hand, an excess of aluminum may adversely affect the insertion and extraction of lithium.

[0213] Therefore, it is preferable that the amount of aluminum contained in the entire positive electrode active material 100 is appropriate. For example, the number of aluminum atoms contained in the entire positive electrode active material 100 is preferably 0.05% to 4% of the number of cobalt atoms, preferably 0.1% to 2% and more preferably 0.3% to 1.5%. Alternatively, 0.05% to 2% is preferable. Alternatively, 0.1% to 4% is preferable. The amount contained in the entire positive electrode active material 100 may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material 100 using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material 100.

[0214] [Fluorine] Fluorine is a monovalent anion, and when part of the oxygen in the surface layer portion 100a is replaced by fluorine, the lithium desorption energy is reduced. This is because the redox potential of the cobalt ion accompanying lithium desorption differs depending on the presence or absence of fluorine. In other words, when there is no fluorine, the cobalt ion changes from trivalent to tetravalent as lithium desorption occurs. On the other hand, when there is fluorine, the cobalt ion changes from divalent to trivalent as lithium desorption occurs. The redox potential of the cobalt ion differs between the two. Therefore, when part of the oxygen in the surface layer portion 100a of the positive electrode active material 100 is replaced by fluorine, it can be said that the desorption and insertion of lithium ions near the fluorine easily occurs. Therefore, when the positive electrode active material 100 is used in a secondary battery, the charge / discharge characteristics, large current characteristics, etc. can be improved. In addition, the presence of fluorine in the surface layer portion 100a having a surface that is in contact with the electrolyte, or the attachment of fluoride to the surface, can suppress excessive reaction between the positive electrode active material 100 and the electrolyte. In addition, the corrosion resistance to hydrofluoric acid can be effectively improved.

[0215] In addition, when the melting point of the fluoride, such as lithium fluoride, is lower than that of the other additive element sources, it can function as a flux (also called a fluxing agent) that lowers the melting point of the other additive element sources. When the fluoride contains LiF and MgF2, since the eutectic point of LiF and MgF2 is around 742°C, it is preferable to set the heating temperature to 742°C or higher in the heating step after mixing the additive elements.

[0216] Here, the differential scanning calorimetry (DSC) measurement of the fluoride and the mixture will be explained with reference to FIG. 10. The fluoride in FIG. 10 is a mixture of LiF and MgF2. They were mixed so that LiF:MgF2 = 1:3 (molar ratio). The mixture in FIG. 10 is a mixture using lithium cobalt oxide as the lithium oxide and LiF and MgF2 as the fluoride. They were mixed so that LiCoO2:LiF:MgF2 = 100:0.33:1 (molar ratio).

[0217] As shown in Fig. 10, an endothermic peak is observed around 735°C for the fluoride, and around 830°C for the mixture. Therefore, the heating temperature after mixing the additive element is preferably 742°C or higher, and more preferably 830°C or higher. It may also be 800°C or higher, which is between these temperatures.

[0218] [Other additive elements] When phosphorus is present in the surface layer 100a, Li x When x in CoO2 is kept small, it is preferable because short circuits can be suppressed. For example, it is preferable that CoO2 exists in the surface layer portion 100a as a compound containing phosphorus and oxygen.

[0219] In the case where the positive electrode active material 100 contains phosphorus, it is possible that the hydrogen fluoride generated by decomposition of the electrolytic solution or electrolyte reacts with the phosphorus, thereby decreasing the hydrogen fluoride concentration in the electrolyte, which is preferable.

[0220] When the electrolyte contains LiPF6, hydrogen fluoride may be generated by hydrolysis. In addition, hydrogen fluoride may be generated by a reaction between polyvinylidene fluoride (PVDF), which is used as a component of the positive electrode, and an alkali. By reducing the hydrogen fluoride concentration in the electrolyte, corrosion of the current collector and / or peeling of the coating 104 may be suppressed. In addition, a decrease in adhesion due to gelation and / or insolubilization of PVDF may be suppressed.

[0221] When the positive electrode active material 100 contains phosphorus together with magnesium, Li x This is preferable because the stability is extremely high when x in CoO2 is small. When the positive electrode active material 100 contains phosphorus, the number of phosphorus atoms is preferably 1% to 20% of the number of cobalt atoms, more preferably 2% to 10%, and even more preferably 3% to 8%. Or preferably 1% to 10%. Or preferably 1% to 8%. Or preferably 2% to 20%. Or preferably 2% to 8%. Or preferably 3% to 20%. Or preferably 3% to 10%. In addition, the number of magnesium atoms is preferably 0.1% to 10% of the number of cobalt atoms, more preferably 0.5% to 5%, and more preferably 0.7% to 4%. Or preferably 0.1% to 5%. Or preferably 0.1% to 4%. Or preferably 0.5% to 10%. Or preferably 0.5% to 4%. Or preferably 0.7% to 10%. The phosphorus and magnesium concentrations shown here may be values ​​obtained by performing elemental analysis of the entire positive electrode active material 100 using, for example, GD-MS, ICP-MS, or the like, or may be based on values ​​of the composition of raw materials in the process of producing the positive electrode active material 100.

[0222] Furthermore, when the positive electrode active material 100 has a crack, the progression of the crack can be suppressed by the presence of phosphorus, more specifically, a compound containing phosphorus and oxygen, inside the positive electrode active material with the crack on the surface, for example, in the embedded portion.

[0223] [Synergistic effect of multiple added elements] Furthermore, when the surface layer 100a contains both magnesium and nickel, there is a possibility that the divalent nickel can exist more stably near the divalent magnesium. x M T Even when x in O2 is small, the elution of magnesium can be suppressed, which can contribute to the stabilization of the surface layer 100a.

[0224] For the same reason, in the manufacturing process, when adding an additive element to lithium cobalt oxide, it is preferable that magnesium is added in a process before nickel. Alternatively, it is preferable that magnesium and nickel are added in the same process. Magnesium has a large ionic radius and tends to remain in the surface layer of lithium cobalt oxide regardless of the process in which it is added, whereas nickel can diffuse widely inside lithium cobalt oxide in the absence of magnesium. Therefore, if nickel is added before magnesium, there is a concern that nickel will diffuse into the lithium cobalt oxide and will not remain in the surface layer in a desired amount.

[0225] Also, if the positive electrode active material 100 has additive elements with different distributions, it is preferable that the crystal structure of a wider region can be stabilized. For example, if the positive electrode active material 100 has both magnesium and nickel distributed in a region closer to the surface of the surface layer portion 100a and aluminum distributed in a region deeper than these, it can stabilize the crystal structure of a wider region than if it had only one of them. In this way, when the positive electrode active material 100 has additive elements with different distributions, aluminum is not essential for the surface because the stabilization of the surface can be sufficiently achieved by magnesium, nickel, etc. Rather, it is preferable that aluminum is widely distributed in a deeper region. For example, it is preferable that aluminum is continuously detected in a region from the surface to a depth of 1 nm to 25 nm. It is preferable that aluminum is widely distributed in a region from 0 nm to 100 nm from the surface, preferably from 0.5 nm to 50 nm from the surface, because the crystal structure of a wider region can be stabilized.

[0226] When a plurality of additive elements are contained as described above, the effects of the respective additive elements are synergistic and can contribute to further stabilization of the surface layer portion 100a. In particular, when magnesium, nickel, and aluminum are contained, the effect of providing a stable composition and crystal structure is high, and therefore it is preferable.

[0227] However, if the surface layer 100a is composed only of a compound of the additive element and oxygen, it is not preferable because it makes it difficult to insert and remove lithium. T It is not preferable that the surface layer 100a is dominated by a structure in which O(II) is dissolved. Therefore, the surface layer 100a should be composed of at least a transition metal M such as cobalt. T In a discharged state, the material must have lithium and must have a path for lithium insertion and desorption.

[0228] In order to ensure sufficient paths for lithium insertion and desorption, the surface layer 100a preferably has a higher cobalt concentration than magnesium. For example, when measured from the surface of the positive electrode active material 100 by XPS, the ratio Mg / Co of the number of magnesium atoms Mg to the number of cobalt atoms Co is preferably 0.62 or less. The surface layer 100a preferably has a higher cobalt concentration than nickel. The surface layer 100a preferably has a higher cobalt concentration than aluminum. The surface layer 100a preferably has a higher cobalt concentration than fluorine.

[0229] Furthermore, since too much nickel may hinder the diffusion of lithium, it is preferable that the surface layer portion 100a has a higher concentration of magnesium than nickel. For example, when measured from the surface of the positive electrode active material 100 by XPS, the number of nickel atoms is preferably 1 / 6 or less of the number of magnesium atoms.

[0230] In addition, it is preferable that some of the added elements, particularly magnesium, nickel and aluminum, have a higher concentration in the surface layer 100a than in the interior 100b, but it is also preferable that they are present randomly and dilutely in the interior 100b. When magnesium and aluminum are present at appropriate concentrations in the lithium sites of the interior 100b, it has the effect of making it easier to maintain the layered rock-salt crystal structure as described above. When nickel is present at an appropriate concentration in the interior 100b, it is possible to suppress the deviation of the layered structure consisting of octahedra of cobalt and oxygen as described above. When magnesium and nickel are present together, a synergistic effect of suppressing the elution of magnesium can be expected as described above.

[0231] It is preferable that the crystal structure changes continuously from the inside 100b toward the surface due to the concentration gradient of the added element as described above, or that the crystal orientation of the surface layer portion 100a and the inside 100b is approximately the same.

[0232] For example, it is preferable that the crystal structure changes continuously from the inside 100b of the layered rock salt type toward the surface and surface layer portion 100a having characteristics of the rock salt type or both the rock salt type and the layered rock salt type. It is also preferable that the crystal orientation of the surface layer portion 100a having characteristics of the rock salt type or both the rock salt type and the layered rock salt type and the inside 100b of the layered rock salt type are approximately the same.

[0233] In this specification, the layered rock-salt type crystal structure belonging to the space group R-3m, which is possessed by a composite oxide containing lithium and a transition metal such as cobalt, refers to a crystal structure having a rock-salt type ion arrangement in which cations and anions are alternately arranged, and in which the transition metal and lithium are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. Defects such as deficiencies of cations or anions may be present. Strictly speaking, the layered rock-salt type crystal structure may have a structure in which the lattice of the rock-salt type crystal is distorted.

[0234] The rock-salt crystal structure refers to a cubic crystal structure, such as a crystal structure belonging to the space group Fm-3m, in which cations and anions are arranged alternately. Note that cations or anions may be missing.

[0235] Moreover, the fact that it has both the characteristics of the layered rock salt type and the rock salt type crystal structure can be determined by electron beam diffraction, TEM images, cross-sectional STEM images, etc.

[0236] In the rock salt type, there is no distinction in the cation sites, but in the layered rock salt type, there are two types of cation sites in the crystal structure, one of which is mostly occupied by lithium and the other by a transition metal. The layered structure in which two-dimensional planes of cations and two-dimensional planes of anions are alternately arranged is the same for both the rock salt type and the layered rock salt type. Among the bright spots in the electron diffraction pattern corresponding to the crystal planes that form this two-dimensional plane, when the central spot (transmitted spot) is set as the origin 000, the bright spot closest to the central spot is, for example, the (111) plane in the ideal rock salt type, and, for example, the (003) plane in the layered rock salt type. For example, when comparing the electron diffraction patterns of rock salt type MgO and layered rock salt type LiCoO2, the distance between the bright spots on the (003) plane of LiCoO2 is observed to be about half the distance between the bright spots on the (111) plane of MgO. Therefore, if the analysis area contains two phases, for example, rock-salt MgO and layered rock-salt LiCoO2, the electron beam diffraction pattern will have a plane orientation in which bright spots of high brightness and bright spots of low brightness are arranged alternately. Bright spots common to both the rock-salt and layered rock-salt types will have high brightness, while bright spots occurring only in the layered rock-salt type will have low brightness.

[0237] Furthermore, when a layered rock-salt crystal structure is observed from a direction perpendicular to the c-axis in cross-sectional STEM images, layers observed with strong brightness and layers observed with weak brightness are observed alternating. This characteristic is not seen in the rock-salt type, as there is no distinction in the cation sites. In the case of a crystal structure that has characteristics of both the rock-salt type and the layered rock-salt type, when observed from a specific crystal orientation, layers observed with strong brightness and layers observed with weak brightness are observed alternating in cross-sectional STEM images, and furthermore, a metal with an atomic number higher than that of lithium is present in part of the weak brightness layer, i.e., the lithium layer.

[0238] Layered rock salt crystals and the anions of rock salt crystals have a cubic close-packed structure (face-centered cubic lattice structure). It is presumed that the anions of O3' type and monoclinic O1(15) crystals described below also have a cubic close-packed structure. Therefore, when a layered rock salt crystal and a rock salt crystal come into contact, there are crystal faces where the cubic close-packed structure composed of anions is aligned.

[0239] Alternatively, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock-salt type has a space group of R-3m and a rhombohedral structure, but to make the structure easier to understand, it is generally represented as a compound hexagonal lattice, and the (0001) plane of the layered rock-salt type has a hexagonal lattice. The triangular lattice of the cubic {111} plane has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock-salt type. When the two lattices are compatible, it can be said that the orientation of the cubic close-packed structure is aligned.

[0240] However, the space group of the layered rock salt crystal and O3' type crystal is R-3m, which is different from the space group Fm-3m (the space group of general rock salt crystals) of the rock salt crystal, so the Miller indices of the crystal planes that satisfy the above conditions are different between the layered rock salt crystal and O3' type crystal and the rock salt crystal. In this specification, when the orientation of the cubic close-packed structure composed of anions is aligned in the layered rock salt crystal, O3' type, and rock salt crystal, it may be said that the crystal orientation is approximately the same. In addition, the three-dimensional structural similarity in which the crystal orientation is approximately the same, or the same crystallographic orientation, is called topotaxis.

[0241] The fact that the crystal orientations of the two regions roughly coincide can be determined from TEM (Transmission Electron Microscope) images, STEM (Scanning Transmission Electron Microscope) images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM) images, ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope) images, electron beam diffraction patterns, and the like. It can also be determined from FFT patterns of TEM images and FFT patterns of STEM images, etc. Furthermore, XRD (X-ray Diffraction), neutron beam diffraction, and the like can also be used as materials for determination.

[0242] An example of a TEM image in which the orientation of the layered rock-salt crystal LRS and the rock-salt crystal RS roughly coincides is shown in Figure 11. Images reflecting the crystal structure can be obtained in TEM images, STEM images, HAADF-STEM images, ABF-STEM images, etc.

[0243] For example, in high-resolution TEM images, contrast originating from crystal planes is obtained. When an electron beam is incident perpendicular to the c-axis of a layered rock-salt type composite hexagonal lattice, for example, the contrast originating from the (0003) plane is obtained as a repetition of bright and dark bands (bright strips) due to the diffraction and interference of the electron beam. Therefore, a repetition of bright and dark lines is observed in the TEM image, and the bright lines (for example, the L shown in Figure 11) are not clearly distinguishable from each other. RS and L LRS ) is 5 degrees or less, or 2.5 degrees or less, it can be determined that the crystal planes are roughly aligned, that is, the crystal orientations are roughly aligned. Similarly, when the angle between the dark lines is 5 degrees or less, or 2.5 degrees or less, it can be determined that the crystal orientations are roughly aligned.

[0244] In addition, in the HAADF-STEM image, contrast proportional to the atomic number is obtained, and elements with higher atomic numbers are observed brighter. For example, in the case of layered rock-salt lithium cobalt oxide belonging to the space group R-3m, cobalt (atomic number 27) has the highest atomic number, so the electron beam is strongly scattered at the position of the cobalt atom, and the arrangement of the cobalt atoms is observed as a bright line or an arrangement of dots with high brightness. Therefore, when lithium cobalt oxide with a layered rock-salt crystal structure is observed perpendicular to the c-axis, the arrangement of the cobalt atoms is observed as a bright line or an arrangement of dots with high brightness perpendicular to the c-axis, and the arrangement of the lithium atoms and oxygen atoms is observed as a dark line or a region with low brightness. The same is true when fluorine (atomic number 9) and magnesium (atomic number 12) are added to the lithium cobalt oxide.

[0245] Therefore, in a HAADF-STEM image, when bright and dark lines are repeatedly observed in two regions with different crystal structures and the angle between the bright lines is 5 degrees or less or 2.5 degrees or less, it can be determined that the atomic arrangements are roughly the same, that is, the crystal orientations are roughly the same. Similarly, when the angle between the dark lines is 5 degrees or less or 2.5 degrees or less, it can also be determined that the crystal orientations are roughly the same.

[0246] In ABF-STEM, elements with smaller atomic numbers appear brighter; however, like HAADF-STEM, it is possible to obtain contrast according to the atomic number, and therefore it is possible to determine the crystal orientation in the same way as with HAADF-STEM images.

[0247] Figure 12(A) shows an example of a STEM image in which the orientations of the layered rock-salt crystal LRS and the rock-salt crystal RS roughly coincide. Figure 12(B) shows the FFT pattern of the region of the rock-salt crystal RS, and Figure 12(C) shows the FFT pattern of the region of the layered rock-salt crystal LRS. The composition, JCPDS card number, and d-values ​​and angles calculated from the data on the JCPDS card are shown on the left of Figures 12(B) and 12(C), and the measured values ​​are shown on the right. The spot marked with O is the zeroth order diffraction.

[0248] The spot marked A in Fig. 12(B) is due to the 11-1 reflection of the cubic crystal. The spot marked A in Fig. 12(C) is due to the 0003 reflection of the layered rock salt type. From Figs. 12(B) and 12(C), it can be seen that the orientation of the 11-1 reflection of the cubic crystal and the orientation of the 0003 reflection of the layered rock salt type are roughly consistent. In other words, it can be seen that the straight line passing through AO in Fig. 12(B) is roughly parallel to the straight line passing through AO in Fig. 12(C). In this case, roughly consistent and roughly parallel mean that the angle is 5 degrees or less, or 2.5 degrees or less.

[0249] In this way, in the FFT pattern and the electron beam diffraction pattern, when the orientation of the layered rock salt type crystal and the rock salt type crystal roughly coincides, the <0003> orientation of the layered rock salt type and the <11-1> orientation of the rock salt type may roughly coincide. In this case, it is preferable that these reciprocal lattice points are spot-like, that is, not continuous with other reciprocal lattice points. The fact that the reciprocal lattice points are spot-like and not continuous with other reciprocal lattice points means that the crystallinity is high.

[0250] In addition, when the orientation of the 11-1 reflection of the cubic crystal and the orientation of the 0003 reflection of the layered rock salt type are roughly the same as described above, depending on the incidence orientation of the electron beam, a spot not originating from the 0003 reflection of the layered rock salt type may be observed in a reciprocal lattice space different from the orientation of the 0003 reflection of the layered rock salt type. For example, the spot marked B in FIG. 12(C) is originating from the 10-14 reflection of the layered rock salt type. This may be observed at an angle of 52° to 56° (i.e., ∠AOB is 52° to 56°) from the orientation of the reciprocal lattice point (A in FIG. 12(C)) originating from the 0003 reflection of the layered rock salt type, and at a position where d is 0.19 nm to 0.21 nm. Note that this index is an example, and does not necessarily have to be the same. For example, a reciprocal lattice point equivalent to 0003 and 10-14 may be used.

[0251] Similarly, a spot not originating from the 11-1 reflection of a cubic crystal may be observed in a reciprocal lattice space different from the orientation where the 11-1 reflection of a cubic crystal is observed. For example, the spot marked with B in FIG. 12(B) originates from the 200 reflection of a cubic crystal. This is a diffraction spot observed at an angle of 54° to 56° (i.e., ∠AOB is 54° to 56°) from the orientation of the reflection originating from the 11-1 of a cubic crystal (A in FIG. 12(B)). Note that this index is only an example, and does not necessarily have to be the same. For example, a reciprocal lattice point equivalent to 11-1 and 200 of a cubic crystal may be used.

[0252] It is known that the layered rock salt type positive electrode active material, including lithium cobalt oxide, is likely to have the (0003) plane and its equivalent plane, as well as the (10-14) plane and its equivalent plane as crystal planes. Therefore, for example, when observing the (0003) plane with a TEM or the like, first select a particle of the positive electrode active material in which a crystal plane expected to be the (0003) plane is observed with a SEM or the like, and then, for example, the particle of the positive electrode active material may be processed into a thin slice with a FIB (Focused Ion Beam) or the like so that the (0003) plane can be observed with an electron beam incident on [12-10] in a TEM or the like. When it is desired to determine the coincidence of the crystal orientation, it is preferable to slice the layered rock salt type so that the (0003) plane can be easily observed.

[0253] <Crystal structure> <Li x M T When x in O2 is 1≫ The positive electrode active material 100 that can be used in the battery 10 according to one embodiment of the present invention is in a discharged state, i.e., Li x M TWhen x=1 in O2, it has a layered rock-salt type crystal structure belonging to the space group R-3m. The layered rock-salt type composite oxide has a high discharge capacity, has a two-dimensional lithium ion diffusion path, is suitable for lithium ion insertion / extraction reactions, and is excellent as a positive electrode active material for secondary batteries. Therefore, it is particularly preferable that the inner part 100b, which occupies most of the volume of the positive electrode active material 100, has a layered rock-salt type crystal structure. The layered rock-salt type crystal structure is shown in FIG. 13 with R-3m O3 attached. R-3m O3 has lattice constants a = 2.81610, b = 2.81610, c = 14.05360, α = 90.0000, β = 90.0000, and γ = 120.0000, and the coordinates of lithium, cobalt, and oxygen in the unit cell are Li(0, 0, 0), Co(0, 0, 0.5), and O(0, 0, 0.23951) (Non-Patent Document 5).

[0254] On the other hand, in the surface layer 100a of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, even if lithium is removed from the positive electrode active material 100 by charging, the transition metal M T It is preferable that the surface layer 100a has a function of reinforcing the layered structure consisting of an octahedron of oxygen and oxygen so that it is not broken. Alternatively, it is preferable that the surface layer 100a functions as a barrier film for the positive electrode active material 100. Alternatively, it is preferable that the surface layer 100a, which is the outer periphery of the positive electrode active material 100, reinforces the positive electrode active material 100. The reinforcement here refers to the elimination of oxygen and / or the transfer of the transition metal M. T This means suppressing structural changes in the surface layer portion 100a and the interior portion 100b of the positive electrode active material 100, such as a shift in the layered structure formed of an octahedron of oxygen and oxygen, and / or suppressing oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.

[0255] Therefore, it is preferable that the surface portion 100a has a different crystal structure from the inner portion 100b. It is also preferable that the surface portion 100a has a composition and a crystal structure that are more stable at room temperature (25° C.) than the inner portion 100b. For example, it is preferable that at least a part of the surface portion 100a of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention has a rock-salt crystal structure. Alternatively, it is preferable that the surface portion 100a has both a layered rock-salt crystal structure and a rock-salt crystal structure. Alternatively, it is preferable that the surface portion 100a has characteristics of both a layered rock-salt crystal structure and a rock-salt crystal structure.

[0256] The surface layer 100a is the region from which lithium ions are first desorbed during charging, and is a region where the lithium concentration is likely to be lower than that of the interior 100b. The atoms on the surface of the particles of the positive electrode active material 100 in the surface layer 100a are in a state where some of the bonds are broken. Therefore, the surface layer 100a is likely to become unstable, and is a region where degradation of the crystal structure is likely to begin. For example, in the surface layer 100a, a transition metal M T When the crystal structure of the layered structure consisting of an octahedron of Li and oxygen is displaced, the effect is linked to the inner portion 100b, and the crystal structure of the layered structure is also displaced in the inner portion 100b, which is considered to lead to deterioration of the crystal structure of the entire positive electrode active material 100. On the other hand, if the surface layer portion 100a can be sufficiently stabilized, x M T Even when x in O2 is small, for example, when x is 0.24 or less, the transition metal M T The layered structure consisting of octahedra of oxygen and oxygen can be made hard to break. Furthermore, the transition metal M T This can suppress the shift of the layers consisting of octahedra of oxygen and oxygen.

[0257] Furthermore, the interior 100b of the positive electrode active material 100 preferably has a low density of defects including dislocations. Furthermore, the positive electrode active material 100 preferably has a large crystallite size measured by XRD. In other words, the interior 100b preferably has high crystallinity. Furthermore, the surface of the positive electrode active material 100 preferably is smooth. These characteristics are important factors supporting the reliability of the positive electrode active material 100 when used in a secondary battery. If the reliability of the positive electrode active material is high, the upper limit of the charging voltage of the secondary battery can be increased, and a secondary battery with a high charge / discharge capacity can be obtained.

[0258] Dislocations in the interior 100b can be observed, for example, by TEM. If the density of defects including dislocations is sufficiently low, they may not be observed in a specific 1 μm square of the observation sample. Note that dislocations are a type of crystal defect and are different from vacancy defects.

[0259] The larger the crystallite size, the greater the Li x When x in CoO2 is small, the O3' type crystal structure is easily maintained, and the contraction of the c-axis length is easily suppressed.

[0260] It is believed that the fewer defects, including dislocations, observed by TEM, the larger the crystallite size as measured by XRD.

[0261] The XRD diffraction pattern for calculating the crystallite size is preferably obtained only from the positive electrode active material, but may be obtained from the positive electrode including the positive electrode active material, the current collector, the binder, the conductive material, etc. However, in the positive electrode state, the particles of the positive electrode active material may be oriented so that the crystal planes of the particles of the positive electrode active material are aligned in one direction due to the influence of pressure in the manufacturing process. If the orientation is too strong, the crystallite size may not be calculated accurately, so it is more preferable to obtain the XRD diffraction pattern by removing the positive electrode active material layer from the positive electrode, removing the binder, etc. in the positive electrode active material layer to a certain extent using a solvent, etc., and then filling the sample holder. There is also a method in which a powder sample is applied to a silicon non-reflective plate with grease, and the powder sample of the positive electrode active material, etc. is attached to the silicon non-reflective plate.

[0262] The crystallite size can be calculated using, for example, a Bruker D8 ADVANCE, with CuKα X-rays, 2θ between 15° and 90°, increment 0.005, and a LYNXEYE XE-T detector, using a diffraction pattern and ICSD coll.code.172909 as the literature value for lithium cobalt oxide. Analysis can be performed using DIFFRAC.TOPAS ver.6 as crystal structure analysis software, and can be set, for example, as follows. Emission Profile: CuKa5.lam Background:Chebychev polynomial, 5th order Instrument Primary radius: 280mm Secondary radius:280mm Linear PSD 2Th angular range:2.9 FDS angle: 0.3 Full Axial Convolution Filament length: 12mm Sample length: 15mm Receiving Slit Length: 12mm Primary Sollers: 2.5 Secondary Sollers: 2.5 Corrections Specimen displacement:Refine LP Factor:0

[0263] It is preferable to use the LVol-IB value, which is the crystallite size calculated by the above method, as the crystallite size. Note that if the calculated Preferred Orientation is less than 0.8, the orientation of the sample is too strong and it may not be suitable for determining the crystallite size.

[0264] <Lix M T The state where x in O2 is small≫ The positive electrode active material 100 that can be used in the battery 10 according to one embodiment of the present invention has the above-described distribution of additive elements and / or crystal structure in a discharged state, and thus has a high conductivity. x M T The crystal structure when x in O2 is small is different from that of conventional positive electrode active materials. <x≦0.24をいうこととする。

[0265] Using Figs. 13 to 17, Li x M T The change in crystal structure accompanying the change in x in O 2 will be described while comparing a conventional positive electrode active material with a positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention.

[0266] The change in the crystal structure of a conventional positive electrode active material is shown in Figure 14. The conventional positive electrode active material shown in Figure 14 is lithium cobalt oxide (LiCoO2) that does not have any added elements. The change in the crystal structure of lithium cobalt oxide that does not have any added elements is described in Non-Patent Documents 1 to 3, etc.

[0267] Figure 14 shows R-3m O3 and Li x The crystal structure of lithium cobalt oxide with x=1 in CoO2 is shown. In this crystal structure, lithium occupies the octahedral site, and there are three CoO2 layers in the unit cell. For this reason, this crystal structure is sometimes called an O3 type crystal structure. Note that a CoO2 layer is an octahedral structure in which cobalt is coordinated with six oxygen atoms, and the edges are shared to form a continuous plane. This is sometimes called a layer made of octahedra of cobalt and oxygen.

[0268] Conventional lithium cobalt oxide is known to have a crystal structure that belongs to the monoclinic space group P2 / m when the symmetry of lithium increases when x is about 0.5. This structure has one CoO2 layer in the unit cell. Therefore, it is sometimes called O1 type or monoclinic O1 type.

[0269] When x=0, the positive electrode active material has a trigonal space group P-3m1 crystal structure, and one CoO2 layer is present in the unit cell. Therefore, this crystal structure is sometimes called O1 type or trigonal O1 type. In addition, the trigonal structure may be converted to a composite hexagonal lattice and called hexagonal O1 type.

[0270] Furthermore, when x=0.12, conventional lithium cobalt oxide has a crystal structure of space group R-3m. This structure can be said to be a structure in which a trigonal O1-type CoO2 structure and an R-3m O3-type LiCoO2 structure are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3-type crystal structure. Note that the actual insertion and desorption of lithium does not necessarily occur uniformly in the positive electrode active material, and the lithium concentration may become uneven, so experimentally, an H1-3-type crystal structure is observed from about x=0.25. In fact, the number of cobalt atoms per unit cell in the H1-3-type crystal structure is twice that of other structures. However, in this specification, including FIG. 14, the c-axis of the H1-3-type crystal structure is shown as 1 / 2 of the unit cell in order to make it easier to compare with other crystal structures.

[0271] As an example of the H1-3 type crystal structure, as described in Non-Patent Document 3, the coordinates of cobalt and oxygen in the unit cell can be expressed as Co (0,0,0.42150±0.00016), O1 (0,0,0.27671±0.00045), and O2 (0,0,0.11535±0.00045). O1 and O2 are oxygen atoms. Which unit cell should be used to express the crystal structure of the positive electrode active material can be determined, for example, by Rietveld analysis of the XRD pattern. In this case, it is sufficient to adopt a unit cell with a small GOF (goodness of fit) value.

[0272] Li x When the battery is repeatedly charged and discharged such that x in CoO2 becomes 0.24 or less, conventional lithium cobalt oxide repeatedly undergoes a change in crystal structure (i.e., a non-equilibrium phase change) between the H1-3 type crystal structure and the R-3m O3 structure in the discharged state.

[0273] However, these two crystal structures have a large misalignment of the CoO2 layer. As shown by the dotted line and arrow in Figure 14, in the H1-3 type crystal structure, the CoO2 layer is significantly misaligned from the R-3m O3 in the discharged state. Such dynamic structural changes can adversely affect the stability of the crystal structure.

[0274] Furthermore, the difference in volume between these two crystal structures is large, so that, per the same number of cobalt atoms, the difference in volume between the H1-3 crystal structure and the discharged R-3m O3 crystal structure exceeds 3.5%, typically 3.9% or more.

[0275] In addition, the H1-3 crystal structure, which has continuous CoO2 layers like the trigonal O1 type, is likely to be unstable.

[0276] Therefore, when charging and discharging are repeated so that x is 0.24 or less, the crystal structure of conventional lithium cobalt oxide collapses. The collapse of the crystal structure causes a deterioration in cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably and makes it difficult to insert and remove lithium.

[0277] On the other hand, in the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention shown in FIG. x M T The change in the crystal structure between the discharge state in O2 where x is 1 and the state where x is 0.24 or less is smaller than that of conventional positive electrode active materials. More specifically, the change in the crystal structure between the discharge state in O2 where x is 1 and the state where x is 0.24 or less is smaller than that of conventional positive electrode active materials. T The displacement of the O2 layer can be reduced. Also, the change in volume per cobalt atom can be reduced. Therefore, the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention is less likely to lose its crystal structure even when it is repeatedly charged and discharged so that x is 0.24 or less, and can achieve excellent cycle characteristics. In addition, the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention is Li x MT In the state where x in O2 is 0.24 or less, the positive electrode active material 100 can have a more stable crystal structure than the conventional positive electrode active material. x M T When the state where x in O2 is 0.24 or less is maintained, short circuits are unlikely to occur. In such a case, the safety of the secondary battery is further improved, which is preferable.

[0278] Li x M T FIG. 13 shows the crystal structure of the interior 100b of the positive electrode active material 100 when x in O2 is 1, approximately 0.2, and approximately 0.15. The interior 100b occupies most of the volume of the positive electrode active material 100 and is a portion that contributes greatly to charge and discharge. T The shift in the O2 layer and the change in volume are the most problematic areas.

[0279] When x=1, the positive electrode active material 100 has the same crystal structure of R-3m O3 as conventional lithium cobalt oxide.

[0280] However, the positive electrode active material 100 has a crystal structure different from that of conventional lithium cobalt oxide when x is 0.24 or less, for example, about 0.2 or about 0.15, in which case the lithium cobalt oxide has an H1-3 type crystal structure.

[0281] The positive electrode active material 100 that can be used in the battery 10 according to one embodiment of the present invention when x=0.2 has a crystal structure that belongs to the trigonal space group R-3m. The symmetry of the CoO2 layer is the same as that of O3. Therefore, this crystal structure is called an O3'-type crystal structure. This crystal structure is shown in FIG. 13 with R-3m O3'.

[0282] The O3' type crystal structure can be expressed by the coordinates of cobalt and oxygen in the unit cell being Co(0,0,0.5), O(0,0,x), in the range of 0.20≦x≦0.25. The lattice constant of the unit cell is 2.797≦a≦2.837(×10 -10 m), and 2.807≦a≦2.827(×10 -10m) is more preferable, and typically a = 2.817(×10 -10 m). The c-axis is 13.681≦c≦13.881(×10 -10 m), and 13.751 ≤ c ≤ 13.811 (× 10 -10 m) is more preferable, and typically c = 13.781 (× 10 -10 m).

[0283] Furthermore, the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention when x=0.15 may have a crystal structure that belongs to the monoclinic space group P2 / m. In this case, one CoO2 layer exists in the unit cell. In addition, the amount of lithium present in the positive electrode active material 100 at this time is about 15 atomic % in the discharged state. Therefore, this crystal structure is referred to as a monoclinic O1(15) type crystal structure. This crystal structure is shown in FIG. 13 with the P2 / m monoclinic O1(15) attached.

[0284] The monoclinic O1(15) crystal structure has the coordinates of cobalt and oxygen in the unit cell as follows: Co1(0.5,0,0.5), Co2(0,0.5,0.5), O1(X O1 ,0,Z O1 ), 0.23≦X O1 ≦0.24, 0.61≦Z O1 ≦0.65, O2(X O2 ,0.5,Z O2 ), 0.75≦X O2 ≦0.78, 0.68≦Z O2 The lattice constant of the unit cell is in the range of ≦0.71. a = 4.880 ± 0.05 (× 10 -10 m), b = 2.817 ± 0.05 (× 10 -10 m), c = 4.839 ± 0.05(×10 -10 m), α=90°, β=109.6±0.1°, γ=90°.

[0285] It is possible to show the lattice constants of this crystal structure in the space group R-3m if a certain degree of error is allowed. In this case, the coordinates of cobalt and oxygen in the unit cell are Co(0,0,0.5), O(0,0,Z O ), 0.21≦Z O ≦0.23. The lattice constant of the unit cell is a = 2.817 ± 0.02(×10 -10 m), c = 13.68 ± 0.1 (× 10 -10 m).

[0286] In both the O3' and monoclinic O1(15) crystal structures, ions of cobalt, nickel, magnesium, etc. occupy 6-coordinate oxygen sites, although light elements such as lithium and magnesium may occupy 4-coordinate oxygen sites.

[0287] As shown by the dotted line in FIG. 13, there is almost no deviation in the CoO2 layer between R-3m O3 in the discharged state and O3' and the monoclinic O1(15) type crystal structure.

[0288] The difference in volume per the same number of cobalt atoms between R-3m O3 in a discharged state and the O3' type crystal structure is 2.5% or less, more specifically 2.2% or less, typically 1.8%.

[0289] The difference in volume per the same number of cobalt atoms between R-3m O3 in a discharged state and the monoclinic O1(15) type crystal structure is 3.3% or less, more specifically 3.0% or less, typically 2.5%.

[0290] Table 7 shows the difference in volume per cobalt atom between R-3m O3 in a discharged state, O3', monoclinic O1(15), H1-3 type, and trigonal O1. For the lattice constants of the crystal structures of R-3m O3 and trigonal O1 in a discharged state used in the calculation of Table 7, ICSD coll.code.172909 and 88721 can be referred to. For R-3m O3 and trigonal O1 in a discharged state, literature values ​​can be referred to (ICSD coll.code.172909 and 88721). For H1-3, Non-Patent Document 3 can be referred to. For O3' and monoclinic O1(15), calculations can be made from experimental values ​​of XRD.

[0291] [Table 7]

[0292] In this way, in the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, Li x M T When x in O2 is small, that is, when a large amount of lithium is released, the change in the crystal structure is suppressed more than in conventional positive electrode active materials. In addition, the change in volume is also suppressed when compared per the same number of cobalt atoms. Therefore, the crystal structure of the positive electrode active material 100 is not easily broken even when charging and discharging are repeated so that x is 0.24 or less. Therefore, the positive electrode active material 100 suppresses the decrease in charge and discharge capacity during charge and discharge cycles. In addition, since more lithium can be stably used than in conventional positive electrode active materials, the positive electrode active material 100 has a large discharge capacity per weight and volume. Therefore, by using the positive electrode active material 100, a secondary battery with a high discharge capacity per weight and volume can be manufactured.

[0293] The positive electrode active material 100 is Li x M T It has been confirmed that when x in O2 is 0.15 or more and 0.24 or less, it may have an O3' type crystal structure, and it is presumed that even when x is more than 0.24 and 0.27 or less, it has an O3' type crystal structure. x M TIt has been confirmed that when x in O2 is greater than 0.1 and less than 0.2, typically between 0.15 and 0.17, it may have a monoclinic O1(15) type crystal structure. However, the crystal structure is Li x M T Since it is affected by not only x in O2 but also the number of charge / discharge cycles, charge / discharge current, temperature, electrolyte, etc., it is not necessarily limited to the above range of x.

[0294] Therefore, the positive electrode active material 100 is Li x M T When x in O2 is more than 0.1 and not more than 0.24, it may have only O3' type, may have only monoclinic O1(15) type, or may have both crystal structures. All of the particles in the inside 100b of the positive electrode active material 100 do not have to have O3' type and / or monoclinic O1(15) type crystal structures. It may contain other crystal structures, or may be partially amorphous.

[0295] Also Li x M T To make x in O2 small, it is generally necessary to charge at a high charging voltage. x M T A state in which x in O2 is small can be rephrased as a state in which the battery is charged at a high charging voltage.

[0296] Therefore, in other words, the positive electrode active material 100 that can be used for the battery 10 of one embodiment of the present invention is preferable because it can maintain a crystal structure having the symmetry of R-3mO3 even when charged at a high charging voltage, for example, a voltage of 4.6 V or higher at 25° C.

[0297] Even with the positive electrode active material 100, the H1-3 crystal structure may be observed only when the charging voltage is further increased. As described above, the crystal structure is affected by the number of charge / discharge cycles, the charge / discharge current, the temperature, the electrolyte, and the like. Therefore, when the charging voltage is lower, for example, even when the charging voltage is 4.5 V or more and less than 4.6 V at 25° C., the positive electrode active material 100 usable in the battery 10 of one embodiment of the present invention may have the O3′ crystal structure. Similarly, when the battery is charged at a voltage of 4.65 V or more and 4.7 V or less at 25° C., the positive electrode active material 100 may have the monoclinic O1(15) crystal structure.

[0298] In addition, when graphite is used as the negative electrode active material in the secondary battery, the voltage of the secondary battery is lower than the above by the potential of the graphite. The potential of graphite is about 0.05 V to 0.2 V based on the potential of lithium metal. Therefore, in the case of a secondary battery using graphite as the negative electrode active material, the battery has the same crystal structure at a voltage obtained by subtracting the potential of graphite from the above voltage.

[0299] In addition, in the O3' and monoclinic O1(15) of FIG. 13, lithium is shown to exist at all lithium sites with equal probability, but this is not limited to this. It may exist biasedly at some lithium sites, or, for example, the monoclinic O1(Li 0.5 The lithium distribution can be analyzed, for example, by neutron diffraction.

[0300] It can also be said that the O3' and monoclinic O1(15) types have random lithium between the layers, but are similar to the CdCl2 type crystal structure. 0.06 Although the crystal structure is close to that when charged to NiO2, it is known that pure lithium cobalt oxide or layered rock salt type positive electrode active materials containing a large amount of cobalt do not usually adopt a CdCl2 type crystal structure.

[0301] <Grain Boundaries> It is more preferable that the additive element contained in the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention has the above-described distribution, and at least a part of the additive element is unevenly distributed in and near the crystal grain boundaries.

[0302] In this specification and the like, uneven distribution refers to the concentration of an element in a certain region being different from that in other regions, and is synonymous with segregation, precipitation, non-uniformity, bias, or the presence of a mixture of areas with high concentration and areas with low concentration.

[0303] For example, the magnesium concentration at and near the grain boundaries of the positive electrode active material 100 is preferably higher than that in other regions of the interior 100b. The fluorine concentration at and near the grain boundaries is preferably higher than that in other regions of the interior 100b. The nickel concentration at and near the grain boundaries is preferably higher than that in other regions of the interior 100b. The aluminum concentration at and near the grain boundaries is preferably higher than that in other regions of the interior 100b.

[0304] Grain boundaries are one type of planar defect. Therefore, like the particle surface, they are prone to become unstable and changes in the crystal structure are likely to occur. Therefore, if the concentration of added elements at and near the grain boundaries is high, changes in the crystal structure can be more effectively suppressed.

[0305] In addition, when the magnesium concentration and fluorine concentration are high at and near the grain boundary, even if cracks occur along the grain boundary of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, the magnesium concentration and fluorine concentration are high near the surface caused by the cracks. Therefore, even in the positive electrode active material after the cracks have occurred, the corrosion resistance to hydrofluoric acid can be improved. In addition, even in the positive electrode active material after the cracks have occurred, a side reaction between the electrolyte and the positive electrode active material can be suppressed.

[0306] <Particle size> If the particle size of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention is too large, problems such as difficulty in diffusing lithium and excessive roughness of the surface of the active material layer when applied to a current collector arise, etc. On the other hand, if the particle size is too small, problems such as excessive reaction with the electrolyte solution arise.

[0307] The particle size of the positive electrode active material 100 can be measured, for example, by a laser diffraction type particle size distribution measuring device. The particle size of the positive electrode active material 100 measured by the laser diffraction type particle size distribution measuring device is preferably a median diameter (D50) of 1 μm or more and 100 μm or less, more preferably 2 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less. Alternatively, 1 μm or more and 40 μm or less is preferable. Alternatively, 1 μm or more and 30 μm or less is preferable. Alternatively, 2 μm or more and 100 μm or less is preferable. Alternatively, 2 μm or more and 30 μm or less is preferable. Alternatively, 5 μm or more and 100 μm or less is preferable. Alternatively, 5 μm or more and 40 μm or less is preferable.

[0308] In addition, when particles having different particle sizes are mixed and used in the positive electrode, the electrode density can be increased, and a secondary battery with high energy density can be obtained, which is preferable. The positive electrode active material 100 having a relatively small particle size is expected to have high charge / discharge rate characteristics. The positive electrode active material 100 having a relatively large particle size is expected to have high charge / discharge cycle characteristics and to maintain a high discharge capacity.

[0309] <Analysis method> A certain positive electrode active material is Li x M T When x in O2 is small, whether or not the positive electrode active material 100 can be used in the battery 10 of one embodiment of the present invention having an O3′ type and / or monoclinic O1(15) type crystal structure is determined by Li x M T This can be determined by analyzing a positive electrode having a positive electrode active material with a small x in O2 using XRD, electron beam diffraction, neutron beam diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc.

[0310] In particular, XRD is preferred in that it can analyze the symmetry of transition metals such as cobalt contained in the positive electrode active material with high resolution, can compare the degree of crystallinity and the orientation of the crystals, can analyze the periodic distortion of the lattice and the crystallite size, can obtain sufficient accuracy even when the positive electrode obtained by disassembling the secondary battery is measured as it is, etc. Among XRD, powder XRD can obtain diffraction peaks reflecting the crystal structure of the inside 100b of the positive electrode active material 100, which occupies most of the volume of the positive electrode active material 100.

[0311] When analyzing the crystallite size by powder XRD, it is preferable to perform the measurement while excluding the influence of the orientation of the positive electrode active material particles due to pressure, etc. For example, it is preferable to take out the positive electrode active material from the positive electrode obtained by disassembling a secondary battery, prepare a powder sample, and then perform the measurement.

[0312] The positive electrode active material 100 that can be used in the battery 10 according to one embodiment of the present invention is Li x M T It is characterized by the fact that there is little change in the crystal structure when x in O2 is 1 and when it is 0.24 or less. Materials in which the crystal structure that undergoes large changes when charged at high voltage accounts for 50% or more of the crystal structure are not desirable because they cannot withstand repeated high-voltage charging and discharging.

[0313] It should also be noted that the addition of an additive element alone may not result in an O3' or monoclinic O1(15) crystal structure. For example, lithium cobalt oxide with magnesium and fluorine, or lithium cobalt oxide with magnesium and aluminum, may have the same structure, but depending on the concentration and distribution of the additive element, Li x M T When x in O2 is 0.24 or less, the O3' type and / or monoclinic O1(15) type crystal structure accounts for 60% or more, and when H1-3 type crystal structure accounts for 50% or more.

[0314] Furthermore, even in the case of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, an H1-3 type or trigonal O1 type crystal structure may be generated when x is too small, such as 0.1 or less, or under conditions where the charging voltage exceeds 4.9 V. Therefore, in order to determine whether the positive electrode active material 100 can be used in the battery 10 of one embodiment of the present invention, analysis of the crystal structure using XRD or other methods, and information such as the charging capacity or the charging voltage are required.

[0315] However, when the positive electrode active material has a small x, its crystal structure may change when exposed to air. For example, the crystal structure may change from O3' type or monoclinic O1(15) type to H1-3 type. Therefore, it is preferable to handle all samples used for crystal structure analysis in an inert atmosphere such as an argon atmosphere.

[0316] Furthermore, whether or not the distribution of the additive elements in a certain positive electrode active material is in the state described above can be determined by analyzing it using, for example, XPS, energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.

[0317] The crystal structure of surface layer 100a, grain boundaries, and the like can be analyzed by electron beam diffraction or the like of a cross section of positive electrode active material 100.

[0318] ≪Charging method≫ In order to determine whether a certain complex oxide is the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, for example, a coin cell (CR2032 type, diameter 20 mm, height 3.2 mm) using the complex oxide for the positive electrode and lithium metal for the counter electrode can be fabricated and charged. The coin cell has an electrolyte, a separator, a positive electrode can, and a negative electrode can.

[0319] More specifically, for the positive electrode, a slurry in which a positive electrode active material, a conductive material, and a binder are mixed is applied to a positive electrode current collector made of aluminum foil and used.

[0320] Lithium metal can be used for the counter electrode. When a material other than lithium metal is used for the counter electrode, the potential of the secondary battery is different from the potential of the positive electrode. Unless otherwise specified, the voltage and potential in this specification are the potential of the positive electrode.

[0321] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6), and the electrolytic solution can be a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of EC:DEC = 3:7, with 2 wt% vinylene carbonate (VC).

[0322] The separator can be a 25 μm thick porous polypropylene film.

[0323] The positive electrode can and the negative electrode can may be made of stainless steel.

[0324] The coin cell prepared under the above conditions is charged at an arbitrary voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V, or 4.8V). The charging method is not particularly limited as long as charging can be performed at an arbitrary voltage for a sufficient time. For example, when charging by CCCV, the current in CC charging can be 20mA / g or more and 100mA / g or less. CV charging can be terminated at 2mA / g or more and 10mA / g or less. In order to observe the phase change of the positive electrode active material, it is desirable to charge at such a small current value. On the other hand, if the current does not become 2mA / g or more and 10mA / g or less even after CV charging for a long time, it is considered that the current is consumed not for charging the positive electrode active material but for decomposing the electrolyte, so CV charging may be terminated when a sufficient time has passed since the start. The sufficient time in this case can be, for example, 1.5 hours or more and 3 hours or less. The temperature is 25°C or 45°C. After charging in this manner, the coin cell is disassembled in a glove box in an argon atmosphere to remove the positive electrode, and a positive electrode active material with a desired charging capacity can be obtained. When various analyses are performed thereafter, it is preferable to seal the cell in an argon atmosphere in order to suppress reactions with external components. For example, XRD can be performed by sealing the cell in a sealed container in an argon atmosphere. In addition, it is preferable to quickly remove the positive electrode and subject it to analysis after charging is completed. Specifically, it is preferable to do so within 1 hour after charging is completed, and more preferably within 30 minutes.

[0325] In addition, when analyzing the crystal structure in the charged state after multiple charge / discharge cycles, the multiple charge / discharge conditions may be different from the above-mentioned charging conditions. For example, charging can be performed by constant current charging at a current value of 20 mA / g to 100 mA / g up to an arbitrary voltage (e.g., 4.6 V, 4.65 V, 4.7 V, 4.75 V, or 4.8 V), followed by constant voltage charging until the current value becomes 2 mA / g to 10 mA / g, and discharging can be performed by constant current discharging at 2.5 V and 20 mA / g to 100 mA / g.

[0326] Furthermore, when analyzing the crystal structure in the discharged state after multiple charge / discharge cycles, constant current discharge can be performed at, for example, 2.5 V and a current value of 20 mA / g or more and 100 mA / g or less.

[0327] <XRD> The XRD measurement apparatus and conditions are not particularly limited. For example, the measurement can be performed using the following apparatus and conditions. XRD equipment: Bruker AXS, D8 ADVANCE X-ray:CuKα1 ray Output: 40kV, 40mA Divergence angle: Div.Slit, 0.5° Detector: LynxEye Scan method: 2θ / θ continuous scan Measurement range (2θ): 15° to 90° Step width (2θ): 0.01° setting Counting time: 1 second / step Sample stage rotation: 15 rpm

[0328] If the measurement sample is a powder, it can be set by placing it in a glass sample holder, sprinkling the sample on a greased silicone non-reflective plate, etc. If the measurement sample is a positive electrode, the positive electrode can be attached to a substrate with double-sided tape, and the positive electrode active material layer can be set to match the measurement surface required by the device.

[0329] The ideal powder XRD patterns calculated from the O3' type crystal structure, the monoclinic O1(15) type crystal structure, and the H1-3 type crystal structure model using CuKα1 radiation are shown in Figures 15, 16, 17(A), and 17(B). For comparison, Li xThe ideal XRD patterns calculated from the crystal structure of LiCoO2O3 with x=1 in CoO2 and trigonal O1 with x=0 are also shown. Figures 17(A) and 17(B) show the XRD patterns of the O3' type crystal structure, monoclinic O1(15) type crystal structure, and H1-3 type crystal structure, with Figure 17(A) showing an enlarged view of the region where 2θ is in the range of 18° to 21°, and Figure 17(B) showing an enlarged view of the region where 2θ is in the range of 42° to 46°. The patterns of LiCoO2(O3) and CoO2(O1) were created using Reflex Powder DiffracTion, one of the modules of Materials Studio (BIOVIA), from crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) (see Non-Patent Document 4). The range of 2θ was 15° to 75°, Step size=0.01, and wavelength λ1=1.540562×10 -10 m and λ2 were not set, and monochromator was set to single. The pattern of the H1-3 type crystal structure was similarly created from the crystal structure information described in Non-Patent Document 3. The patterns of the O3' type and monoclinic O1(15) type crystal structures were estimated from the XRD pattern of the positive electrode active material, and fitted using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker), and XRD patterns were created in the same manner as the others.

[0330] As shown in Figures 15, 17(A) and 17(B), in the O3' type crystal structure, diffraction peaks appear at 2θ = 19.25 ± 0.12° (greater than 19.13° and less than 19.37°) and 2θ = 45.47 ± 0.10° (greater than 45.37° and less than 45.57°).

[0331] In addition, in the monoclinic O1(15) type crystal structure, diffraction peaks appear at 2θ = 19.47 ± 0.10° (19.37° to 19.57°) and 2θ = 45.62 ± 0.05° (45.57° to 45.67°).

[0332] However, as shown in Figures 16, 17(A) and 17(B), no peaks appear at these positions in the H1-3 type crystal structure and trigonal O1. x The appearance of peaks at 19.13° or more and less than 19.37° and / or 19.37° or more and 19.57° or less, and at least 45.37° or more and less than 45.57° and / or at least 45.57° or more and 45.67° or less when x in CoO2 is small can be said to be a characteristic of the positive electrode active material 100 that can be used for the battery 10 of one embodiment of the present invention.

[0333] This can also be said to mean that in the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, the positions at which XRD diffraction peaks appear are close between the crystal structures where x=1 and where x≦0.24. More specifically, it can be said that the difference in 2θ between the main diffraction peaks appearing at 2θ of 42° or more and 46° or less in the crystal structures where x=1 and where x≦0.24 are 0.7° or less, more preferably 0.5° or less.

[0334] The positive electrode active material 100 that can be used in the battery 10 according to one embodiment of the present invention is Li x When x in CoO2 is small, it may have O3'-type and / or monoclinic O1(15)-type crystal structure, but not all of the particles may have O3'-type and / or monoclinic O1(15)-type crystal structure. It may contain other crystal structures, or may be partially amorphous. However, when Rietveld analysis is performed on the XRD pattern, it is preferable that the O3'-type and / or monoclinic O1(15)-type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more. If the O3'-type and / or monoclinic O1(15)-type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more, it can be a positive electrode active material with sufficiently excellent cycle characteristics.

[0335] Similarly, when Rietveld analysis is performed, the H1-3 type and O1 type crystal structures are preferably 50% or less, more preferably 34% or less, and even more preferably substantially not observed.

[0336] Furthermore, even after 100 or more charge / discharge cycles from the start of measurement, when Rietveld analysis is performed, the O3' type and / or monoclinic O1(15) type crystal structure is preferably 35% or more, more preferably 40% or more, and even more preferably 43% or more.

[0337] The sharpness of the diffraction peaks in the XRD pattern indicates the high crystallinity. Therefore, it is preferable that each diffraction peak after charging is sharp, that is, the half-width is narrow. For example, it is preferable that the full width at half maximum is narrow. The half-width varies depending on the XRD measurement conditions and the value of 2θ, even for peaks generated from the same crystal phase. In the case of the above-mentioned measurement conditions, the full width at half maximum is preferably 0.2° or less, more preferably 0.15° or less, and even more preferably 0.12° or less, for example, in peaks observed at 2θ=43° or more and 46° or less. It is not necessary for all peaks to meet this requirement. If some peaks meet this requirement, it can be said that the crystallinity of the crystal phase is high. Such high crystallinity contributes to the stabilization of the crystal structure after charging sufficiently.

[0338] In addition, the crystallite size of the O3' type and monoclinic O1(15) crystal structures of the positive electrode active material 100 is reduced to only about 1 / 20 of that of LiCoO2(O3) in the discharged state. x When x in CoO2 is small, clear peaks of O3' type and / or monoclinic O1(15) crystal structure can be confirmed. On the other hand, in conventional LiCoO2, even if some parts have a structure similar to O3' type and / or monoclinic O1(15) crystal structure, the crystallite size becomes small and the peak becomes broad and small. The crystallite size can be calculated from the half-width of the XRD peak.

[0339] In the positive electrode active material 100 that can be used in the battery 10 according to one embodiment of the present invention, it is preferable that the influence of the Jahn-Teller effect is small, as described above. As long as the influence of the Jahn-Teller effect is small, a transition metal such as nickel or manganese may be contained as an additive element in addition to cobalt.

[0340] For example, when the nickel concentration is 5 atomic % and 7.5 atomic %, the a-axis / c-axis tends to change significantly, and when the nickel concentration is 7.5 atomic %, the distortion of the a-axis becomes large. This distortion may be due to the Jahn-Teller distortion of trivalent nickel. Therefore, the transition metal M T Of these, nickel is preferably less than 7.5 atomic %.

[0341] In addition, when the manganese concentration is 5 atomic % or more, the behavior of the change in the lattice constant is different, and it is suggested that it does not follow Vegard's law. T Of these, manganese is preferably 4 atomic % or less.

[0342] The above ranges of nickel concentration and manganese concentration do not necessarily apply to the surface layer portion 100a, that is, the concentrations in the surface layer portion 100a may be higher than the above ranges.

[0343] As a result of considering the above-mentioned preferable range of the lattice constant, it was found that in the positive electrode active material of one embodiment of the present invention, the layered rock-salt crystal structure of the positive electrode active material 100 in a state in which no charge / discharge is performed or in a discharged state, which can be estimated from the XRD pattern, has an a-axis lattice constant of 2.814 × 10 -10 m or larger, 2.817×10 -10 m and the c-axis lattice constant is 14.05×10 -10 m or larger, 14.07×10 -10 It has been found that the value is preferably smaller than m. The state in which charging and discharging are not performed may be, for example, the powder state prior to fabrication of the positive electrode of a secondary battery.

[0344] Alternatively, in the layered rock-salt crystal structure of the positive electrode active material 100 in a state where no charge or discharge is performed or in a discharged state, the value obtained by dividing the lattice constant of the a-axis by the lattice constant of the c-axis (a-axis / c-axis) is preferably greater than 0.20000 and smaller than 0.20049.

[0345] Alternatively, when XRD analysis is performed on the layered rock-salt crystal structure of the positive electrode active material 100 in a state where no charge or discharge is performed or in a discharged state, a first peak may be observed at 2θ of 18.50° or more and 19.30° or less, and a second peak may be observed at 2θ of 38.00° or more and 38.80° or less.

[0346] <XPS> In X-ray photoelectron spectroscopy (XPS), in the case of inorganic oxides, when monochromatic aluminum Kα rays are used as X-rays, it is possible to analyze a region from the surface to a depth of about 2 to 8 nm (usually 5 nm or less), so the concentration of each element can be quantitatively analyzed in a region about half the depth of the surface layer 100a. In addition, narrow scan analysis can be used to analyze the bonding state of elements. The quantitative accuracy of XPS is often about ±1 atomic %, with a lower limit of about 1 atomic %, depending on the element.

[0347] In the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, the concentration of one or more selected from the additive elements is preferably higher in the surface layer portion 100a than in the interior portion 100b. This is synonymous with the fact that the concentration of one or more selected from the additive elements in the surface layer portion 100a is preferably higher than the average concentration of the additive elements in the entire positive electrode active material 100. Therefore, for example, it can be said that the concentration of one or more selected additive elements in the surface layer portion 100a measured by XPS or the like is preferably higher than the average concentration of the additive elements in the entire positive electrode active material 100 measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry). For example, it is preferable that the magnesium concentration of at least a part of the surface layer portion 100a measured by XPS or the like is higher than the average magnesium concentration of the entire positive electrode active material 100. It is also preferable that the titanium concentration of at least a part of the surface layer portion 100a is higher than the average titanium concentration of the entire positive electrode active material 100. It is also preferable that the nickel concentration in at least a part of the surface layer portion 100a is higher than the average nickel concentration in the entire positive electrode active material 100. It is also preferable that the aluminum concentration in at least a part of the surface layer portion 100a is higher than the average aluminum concentration in the entire positive electrode active material 100. It is also preferable that the fluorine concentration in at least a part of the surface layer portion 100a is higher than the average fluorine concentration in the entire positive electrode active material 100.

[0348] The surface and surface layer 100a of the positive electrode active material 100 that can be used in the battery 10 according to one embodiment of the present invention do not contain carbonates, hydroxyl groups, or the like that are chemically adsorbed after the preparation of the positive electrode active material 100. Also, the surface of the positive electrode active material 100 does not contain an electrolyte, a binder, a conductive material, or compounds derived therefrom that are attached to the surface of the positive electrode active material 100. Therefore, when quantifying the elements contained in the positive electrode active material, a correction may be made to exclude carbon, hydrogen, excess oxygen, excess fluorine, and the like that can be detected by surface analysis such as XPS. For example, XPS allows the types of bonds to be separated by analysis, and a correction may be made to exclude C-F bonds derived from the binder.

[0349] Furthermore, before being subjected to various analyses, the sample such as the positive electrode active material and the positive electrode active material layer may be washed in order to remove the electrolyte, binder, conductive material, or compounds derived therefrom that are attached to the surface of the positive electrode active material. At this time, lithium may dissolve in the solvent used for washing, but even in this case, the added element is unlikely to dissolve, and therefore the atomic ratio of the added element is not affected.

[0350] The concentration of the added element may be compared in terms of the ratio to cobalt. By using the ratio to cobalt, the influence of carbonates and the like chemically adsorbed after the preparation of the positive electrode active material can be reduced and comparison is preferably made. For example, the ratio Mg / Co of the number of magnesium atoms to cobalt atoms as determined by XPS analysis is preferably 0.4 to 1.5. On the other hand, the ratio Mg / Co as determined by ICP-MS analysis is preferably 0.001 to 0.06.

[0351] Similarly, in the positive electrode active material 100, in order to sufficiently secure a path for the insertion and desorption of lithium, it is preferable that the concentrations of lithium and cobalt in the surface layer portion 100a are higher than the concentrations of one or more additive elements selected from the additive elements contained in the surface layer portion 100a measured by XPS or the like. For example, it is preferable that the concentration of at least a part of cobalt in the surface layer portion 100a measured by XPS or the like is higher than the concentration of magnesium in at least a part of the surface layer portion 100a measured by XPS or the like. Similarly, it is preferable that the concentration of lithium is higher than the concentration of magnesium. It is also preferable that the concentration of cobalt is higher than the concentration of nickel. It is also preferable that the concentration of lithium is higher than the concentration of nickel. It is also preferable that the concentration of cobalt is higher than aluminum. It is also preferable that the concentration of lithium is higher than the concentration of aluminum. It is also preferable that the concentration of cobalt is higher than fluorine. It is also preferable that the concentration of lithium is higher than fluorine.

[0352] Furthermore, it is more preferable that aluminum is widely distributed in a deep region, for example, the surface, or a region having a depth of 5 nm to 50 nm from the reference point. Therefore, although aluminum is detected in the analysis of the entire positive electrode active material 100 using ICP-MS, GD-MS, etc., it is more preferable that the concentration of aluminum is not detected by XPS, etc., or is 1 atomic % or less.

[0353] Furthermore, when the positive electrode active material 100 usable in the battery 10 of one embodiment of the present invention was subjected to XPS analysis, the number of magnesium atoms was preferably 0.4 times or more and 1.2 times or less, and more preferably 0.65 times or more and 1.0 times or less, relative to the number of cobalt atoms. The number of nickel atoms was preferably 0.15 times or less, and more preferably 0.03 times or more and 0.13 times or less, relative to the number of cobalt atoms. The number of aluminum atoms was preferably 0.12 times or less, and more preferably 0.09 times or less, relative to the number of cobalt atoms. The number of fluorine atoms was preferably 0.3 times or more and 0.9 times or less, and more preferably 0.1 times or more and 1.1 times or less, relative to the number of cobalt atoms. The above ranges indicate that these additive elements are not attached to a narrow range on the surface of the positive electrode active material 100, but are widely distributed in a preferred concentration in the surface layer portion 100a of the positive electrode active material 100.

[0354] When performing XPS analysis, for example, monochromated aluminum Kα rays can be used as X-rays. The take-off angle can be set to, for example, 45°. For example, the measurement can be performed using the following equipment and conditions. Measurement equipment: PHI Quantera II X-ray: Monochromatic Al Kα (1486.6 eV) Detection area: 100μmφ Detection depth: Approx. 4 to 5 nm (take-off angle 45°) Measurement spectrum: Wide scan, narrow scan of each detected element

[0355] In addition, when the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention is analyzed by XPS, the peak indicating the bond energy between fluorine and another element is preferably equal to or greater than 682 eV and less than 685 eV, and more preferably about 684.3 eV, which is different from both the bond energy of lithium fluoride (685 eV) and the bond energy of magnesium fluoride (686 eV).

[0356] Furthermore, when the positive electrode active material 100 usable in the battery 10 of one embodiment of the present invention is analyzed by XPS, the peak showing the bond energy between magnesium and other elements is preferably equal to or greater than 1302 eV and less than 1304 eV, and more preferably about 1303 eV, which is a different value from the bond energy of magnesium fluoride, 1305 eV, and is close to the bond energy of magnesium oxide.

[0357] <EDX> It is preferable that one or more selected from the additive elements contained in the positive electrode active material 100 have a concentration gradient. It is more preferable that the depth from the surface of the concentration peak differs depending on the additive element in the positive electrode active material 100. The concentration gradient of the additive element can be evaluated, for example, by exposing a cross section of the positive electrode active material 100 using a focused ion beam (FIB) or the like and analyzing the cross section using energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.

[0358] Among EDX measurements, EDX area analysis is performed by scanning an area and evaluating the area in two dimensions. EDX line analysis is performed by scanning a line and evaluating the distribution of atomic concentration within the positive electrode active material. Line analysis may also be used to extract data from a linear area of ​​EDX area analysis. Point analysis is used to measure an area without scanning it.

[0359] By EDX surface analysis (e.g., element mapping), the concentration of the added element can be quantitatively analyzed in the surface layer 100a, the inside 100b, and the vicinity of the grain boundary of the positive electrode active material 100. In addition, by EDX line analysis, the concentration distribution and maximum value of the added element can be analyzed. In addition, analysis using a thinned sample such as STEM-EDX is more preferable because it can analyze the concentration distribution in the depth direction from the surface to the center of the positive electrode active material in a specific region without being affected by the distribution in the depth direction.

[0360] The positive electrode active material 100 is a compound containing a transition metal capable of inserting and extracting lithium and oxygen, and therefore contains a transition metal M T The interface between the region where metals (e.g., Co, Ni, Mn, Fe, etc.) and oxygen are present and the region where they are not present is defined as the surface of the positive electrode active material. When the positive electrode active material is subjected to analysis, a protective film may be attached to the surface, but the protective film is not included in the positive electrode active material. As the protective film, a single layer film or a multilayer film of carbon, metal, oxide, resin, etc. may be used.

[0361] Therefore, when referring to the depth direction in STEM-EDX line analysis, etc., T The amount of characteristic X-rays detected is T The average amount of characteristic X-rays detected, M TAVE and the above transition metal M in the background T The average amount of characteristic X-rays detected, M TBG The point where the amount of oxygen characteristic X-rays detected is 50% of the sum of the amount of oxygen characteristic X-rays detected inside the sample, or the amount of oxygen characteristic X-rays detected inside the sample is the average amount of oxygen characteristic X-rays detected inside the sample. AVE and the average amount of oxygen characteristic X-rays detected in the background, O BG The reference point is the point where the sum of the transition metals M T The amount of characteristic X-rays detected is the amount of the internal transition metal M T The average amount of characteristic X-rays detected and the background amount of the transition metals M TIf the point where the detection amount of oxygen characteristic X-rays is 50% of the sum of the average detection amount of internal oxygen characteristic X-rays and the average detection amount of background oxygen characteristic X-rays is different from the point where the detection amount of oxygen characteristic X-rays is 50% of the sum of the average detection amount of internal oxygen characteristic X-rays and the average detection amount of background oxygen characteristic X-rays, this is considered to be due to the influence of metal oxides and carbonates containing oxygen attached to the surface. T The amount of characteristic X-rays detected is the amount of the internal transition metal M T The average amount of characteristic X-rays detected, M TAVE and the above transition metal M in the background T The average amount of characteristic X-rays detected, M TBG The 50% point of the sum of these two can be used as the reference point. T In the case of a positive electrode active material having multiple elements, the element M with the highest amount of characteristic X-rays detected inside is TAVE and M TBG The reference point can be obtained using the following formula:

[0362] The above transition metals in the background T The average amount of characteristic X-rays detected, M TBG For example, transition metal M T The amount of the characteristic X-rays detected can be measured by averaging the area of ​​2 nm or more, preferably 3 nm or more, from the outside of the positive electrode active material, while avoiding the area where the amount of the characteristic X-rays detected starts to increase. T The average amount of characteristic X-rays detected, M TAVE is the transition metal M T And the region where the amount of detection of oxygen characteristic X-rays is saturated and stable, for example, transition metal M T The average value of the detection amount of the characteristic X-rays of oxygen in the background can be obtained by averaging the range of 2 nm or more, preferably 3 nm or more, at a depth of 30 nm or more, preferably 50 nm or more, from the region where the detection amount of the characteristic X-rays of oxygen starts to increase. BG and the average amount of internal oxygen characteristic X-rays detected O AVE can also be found in the same way.

[0363] The surface of the positive electrode active material 100 in a cross-sectional STEM image or the like refers to the boundary between an area where an image originating from the crystal structure of the positive electrode active material is observed and an area where it is not observed, and is the outermost area where atomic columns originating from the atomic nuclei of metal elements having atomic numbers larger than that of lithium among the metal elements constituting the positive electrode active material can be confirmed.

[0364] In addition, the spatial resolution of STEM-EDX is about 1 nm. Therefore, the position where the amount of characteristic X-rays detected of the additive element is at its maximum may be shifted by about 1 nm. For example, even if the amount of characteristic X-rays detected of an additive element such as magnesium is at its maximum outside the surface obtained above, it can be considered an error as long as the difference between the maximum value and the surface is less than 1 nm.

[0365] The effect of noise can be reduced by scanning the same location multiple times under the same conditions. For example, the integrated values ​​measured over six scans can be used to graph the characteristic X-rays of each element. The number of scans is not limited to six, and it is also possible to perform more than six scans and average the results to graph the characteristic X-rays of each element.

[0366] The STEM-EDX line analysis can be carried out, for example, as follows. First, a protective film is deposited on the surface of the positive electrode active material. For example, carbon can be deposited using an ion sputtering device (MC1000 manufactured by Hitachi High-Technologies).

[0367] Next, the positive electrode active material is sliced ​​to prepare a STEM cross-section sample. For example, the slice processing can be performed using a FIB-SEM device (Hitachi High-Tech XVision200TBS). In this case, the pickup is performed using an MPS (micro-probing system), and the finishing processing conditions can be, for example, an acceleration voltage of 10 kV.

[0368] For the STEM-EDX analysis, for example, a STEM device (Hitachi High-Tech HD-2700) can be used, and an EDX detector such as EDAX Octane T Ultra W can be used. During EDX analysis, the emission current of the STEM device is set to 6 μA or more and 10 μA or less, and a portion of the sliced ​​sample with little depth and unevenness is measured. The magnification is, for example, about 150,000 times. The conditions for EDX analysis can be drift correction, line width 42 nm, pitch 0.2 nm, and frame number 6 or more.

[0369] When EDX area analysis or EDX point analysis is performed on the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, it is preferable that the concentration of each added element, particularly an added element such as magnesium, in the surface layer portion 100a is higher than that in the interior 100b.

[0370] For example, when EDX surface analysis or EDX point analysis is performed on a positive electrode active material 100 having magnesium as an additive element, the magnesium concentration in the surface layer 100a is preferably higher than the magnesium concentration in the interior 100b. When EDX line analysis is performed, the peak of the magnesium concentration in the surface layer 100a is preferably present on the surface of the positive electrode active material 100 or at a depth of 3 nm from the reference point toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. The magnesium concentration is preferably attenuated to 60% or less of the peak at a point 1 nm deep from the peak. It is also preferable that the magnesium concentration is attenuated to 30% or less of the peak at a point 2 nm deep from the peak. The peak of concentration (also called peak top) here refers to the maximum value of the concentration.

[0371] Furthermore, when EDX line analysis is performed, the maximum value of the magnesium concentration in the surface layer 100a (detected amount of magnesium / sum of detected amounts of magnesium, oxygen, cobalt, fluorine, aluminum, titanium, and nickel) is preferably 0.5 atomic % or more and 10 atomic % or less, and more preferably 1 atomic % or more and 5 atomic % or less.

[0372] Furthermore, when EDX line analysis is performed, the maximum titanium concentration in surface portion 100a (detected amount of titanium / (sum of detected amounts of magnesium, oxygen, cobalt, fluorine, aluminum, titanium, and nickel) is preferably 0.2 atomic % or more and 5 atomic % or less, and more preferably 0.5 atomic % or more and 2 atomic % or less.

[0373] Furthermore, when EDX line analysis is performed, the maximum value of the nickel concentration in the surface layer portion 100a (detected amount of nickel / (sum of detected amounts of magnesium, oxygen, cobalt, fluorine, aluminum, titanium, and nickel) is preferably 0.2 atomic % or more and 5 atomic % or less, and more preferably 0.5 atomic % or more and 3 atomic % or less.

[0374] In the positive electrode active material 100 having magnesium and fluorine as additive elements, the distribution of fluorine preferably has an overlapping region with the distribution of magnesium. For example, the difference in the depth direction between the peak of the fluorine concentration and the peak of the magnesium concentration is preferably within 10 nm, more preferably within 3 nm, and even more preferably within 1 nm.

[0375] In addition, when EDX analysis is performed, the fluorine concentration peak of the surface layer 100a is preferably present on the surface of the positive electrode active material 100 or at a depth of 3 nm from the reference point toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. Furthermore, if the fluorine concentration peak is slightly closer to the surface than the magnesium concentration peak, it is more preferable because it increases resistance to hydrofluoric acid. For example, it is more preferable that the fluorine concentration peak is 0.5 nm or more closer to the surface than the magnesium concentration peak, and even more preferable that it is 1.5 nm or more closer to the surface.

[0376] In the positive electrode active material 100 having nickel as an additive element, the nickel concentration peak of the surface layer 100a is preferably present at a depth of 3 nm from the surface or reference point of the positive electrode active material 100 toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. In the positive electrode active material 100 having magnesium and nickel, the nickel distribution preferably has an overlapping region with the magnesium distribution. For example, the difference in depth between the nickel concentration peak and the magnesium concentration peak is preferably within 3 nm, more preferably within 1 nm.

[0377] In the positive electrode active material 100 having titanium as an additive element, the peak of the titanium concentration in the surface layer 100a is preferably present at a depth of 3 nm from the surface or reference point toward the center of the positive electrode active material 100, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. In the positive electrode active material 100 having magnesium and titanium, the distribution of titanium preferably has an overlapping region with the distribution of magnesium. For example, the difference in the depth direction between the peak of titanium concentration and the peak of magnesium concentration is preferably within 3 nm, more preferably within 1 nm.

[0378] Furthermore, when the positive electrode active material 100 contains aluminum as an added element, it is preferable that the peak of the magnesium, nickel, or fluorine concentration is closer to the surface than the peak of the aluminum concentration in the surface layer portion 100a when EDX line analysis is performed. For example, the peak of the aluminum concentration is preferably present on the surface of the positive electrode active material 100, or at a depth of 0.5 nm to 50 nm from the reference point toward the center, and more preferably at a depth of 5 nm to 50 nm.

[0379] When the positive electrode active material 100 contains magnesium, titanium, nickel, and aluminum as described above, a battery using the positive electrode active material 100 can achieve both "high cycle characteristics" that can suppress deterioration of discharge capacity due to repeated high-voltage charging (e.g., charging with an upper limit of 4.6 V) and discharging, and "high low-temperature characteristics" that can obtain a large discharge capacity at low temperatures (e.g., 0° C., −20° C., −40° C.).

[0380] In addition, when EDX line analysis, surface analysis, or point analysis is performed on the positive electrode active material 100, the ratio of the number of atoms of magnesium Mg and cobalt Co (Mg / Co) at the peak of magnesium concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.4. The ratio of the number of atoms of aluminum Al and cobalt Co (Al / Co) at the peak of aluminum concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.45. The ratio of the number of atoms of nickel Ni and cobalt Co (Ni / Co) at the peak of nickel concentration is preferably 0 to 0.2, more preferably 0.01 to 0.1. The ratio of the number of atoms of fluorine F and cobalt Co (F / Co) at the peak of fluorine concentration is preferably 0 to 1.6, more preferably 0.1 to 1.4.

[0381] Furthermore, when the positive electrode active material 100 is subjected to a line analysis or an area analysis, the ratio (A / Co) of the number of atoms of the additive element A to the cobalt Co in the vicinity of the grain boundaries is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. Still more preferably, it is 0.030 or more and 0.20 or less. Or it is preferably 0.020 or more and 0.30 or less. Or it is preferably 0.020 or more and 0.20 or less. Or it is preferably 0.025 or more and 0.50 or less. Or it is preferably 0.025 or more and 0.20 or less. Or it is preferably 0.030 or more and 0.50 or less. Or it is preferably 0.030 or more and 0.30 or less.

[0382] For example, when the additive element is magnesium, when the positive electrode active material 100 is subjected to a line analysis or a surface analysis, the ratio of the number of magnesium atoms to the number of cobalt atoms (Mg / Co) in the vicinity of the grain boundary is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. More preferably, it is 0.030 or more and 0.20 or less. Or, it is preferably 0.020 or more and 0.30 or less. Or, it is preferably 0.025 or more and 0.50 or less. Or, it is preferably 0.025 or more and 0.20 or less. Or, it is preferably 0.030 or more and 0.50 or less. Or, it is preferably 0.030 or more and 0.30 or less. If the ratio is within the above range at a plurality of locations, for example, three or more locations, of the positive electrode active material 100, it can be said that the additive element is not attached to a narrow range on the surface of the positive electrode active material 100, but is widely distributed at a preferred concentration in the surface layer portion 100a of the positive electrode active material 100.

[0383] EPMA EPMA (Electron Probe Microanalysis) can also quantify elements. Area analysis can analyze the distribution of each element.

[0384] When a cross section of the positive electrode active material 100 usable in the battery 10 according to an embodiment of the present invention is subjected to an EPMA surface analysis, it is preferable that one or more selected from the additive elements have a concentration gradient, as in the EDX analysis results. It is more preferable that the depth from the surface of the concentration peak differs depending on the additive element. The preferable range of the concentration peak of each additive element is also the same as in the case of EDX.

[0385] However, EPMA analyzes the region from the surface to a depth of about 1 μm. Therefore, the quantitative values ​​of each element may differ from the measurement results obtained by other analytical methods. For example, when the surface analysis of the positive electrode active material 100 is performed by EPMA, the concentration of each added element present in the surface layer 100a may be lower than the result of XPS.

[0386] <Raman spectroscopy> The positive electrode active material 100 that can be used in the battery 10 according to one aspect of the present invention preferably has at least a part of the surface layer portion 100a having a rock salt-type crystal structure as described above. Therefore, when the positive electrode active material 100 and the positive electrode having the same are analyzed by Raman spectroscopy, it is preferable that a cubic crystal structure including a rock salt type as well as a layered rock salt crystal structure is observed. In the STEM image and the micro electron beam diffraction pattern described later, cobalt substituted at the lithium position with a certain frequency in the depth direction during observation, and cobalt present at the oxygen four-coordination position, etc., cannot be detected as bright spots in the STEM image and the micro electron beam diffraction pattern. On the other hand, since Raman spectroscopy is an analysis that captures the vibration mode of bonds such as Co-O, even when the abundance of the corresponding Co-O bond is small, peaks of the wave numbers of the corresponding vibration modes may be observed. Furthermore, Raman spectroscopy can measure a range with an area of several μm on the surface layer portion and a depth of about 1 μm, so it can sensitively capture the state existing only on the particle surface. 2 , Since it can measure a range with a depth of about 1 μm, it can sensitively capture the state existing only on the particle surface.

[0387] For example, when the laser wavelength is 532 nm, in layered rock salt-type LiCoO2, peaks (vibration modes: E -1 to 490 cm -1 , 580 cm -1 to 600 cm -1 ) are observed at g , A 1g ). On the other hand, in cubic CoO x (0 < x < 1) (rock salt-type Co 1-y O (0 < y < 1) or spinel-type Co3O4), a peak (vibration mode: A -1 to 685 cm -1 ) is observed at 1g ).

[0388] Therefore, taking the integrated intensity of each peak as I1 for 470 cm -1 to 490 cm -1 , I2 for 580 cm -1 to 600 cm -1 , and 665 cm -1 to 685 cm -1When I3 is taken as I3, the value of I3 / I2 is preferably 1% or more and 10% or less, and more preferably 3% or more and 9% or less.

[0389] When a cubic crystal structure such as a rock-salt type is observed in the above range, it can be said that surface layer portion 100a of positive electrode active material 100 has a rock-salt type crystal structure in a preferred range.

[0390] <Microelectron diffraction pattern> As in the Raman spectroscopy, it is preferable that the characteristics of the rock salt type crystal structure are observed in the electron microbeam diffraction pattern as well as the layered rock salt crystal structure. However, in the STEM image and the electron microbeam diffraction pattern, taking into consideration the above-mentioned difference in sensitivity, it is preferable that the characteristics of the rock salt type crystal structure are not too strong in the surface layer 100a, especially in the outermost surface (for example, 1 nm deep from the surface). This is because the lithium layer can secure a diffusion path for lithium and have a stronger function of stabilizing the crystal structure if an additive element such as magnesium is present in the lithium layer while maintaining the layered rock salt type crystal structure, rather than the outermost surface being covered with the rock salt type crystal structure.

[0391] Therefore, for example, when a micro-beam diffraction pattern of a region having a depth of 1 nm or less from the surface and a micro-beam diffraction pattern of a region having a depth of 3 nm to 10 nm are obtained, it is preferable that the difference in lattice constant calculated from these patterns be small.

[0392] For example, the difference in lattice constant calculated from a measurement point 1 nm or less deep from the surface and a measurement point 3 nm to 10 nm deep is 0.1(×10 -10 m) or less, and the c-axis is preferably 1.0 (× 10 -10 m) or less. Also, the a-axis is preferably 0.05 (× 10 -10 m) or less, and more preferably, 0.6(×10 -10 m) or less. Also, the a-axis is preferably 0.04 (× 10 -10 m) or less, it is more preferable that the c-axis is 0.3 (× 10 -10 It is even more preferable that the thickness is equal to or less than m.

[0393] <Surface roughness and specific surface area> The positive electrode active material 100 that can be used in the battery 10 according to one embodiment of the present invention preferably has a smooth surface with few irregularities. A smooth surface with few irregularities indicates that the effect of a flux, which will be described later, is sufficiently exerted to melt the surfaces of the additive element source and the lithium cobalt oxide. This is one factor indicating that the distribution of the additive element in the surface layer portion 100a is good.

[0394] Whether the surface is smooth and has few projections and recesses can be determined from, for example, a cross-sectional SEM image or cross-sectional TEM image of the positive electrode active material 100, the specific surface area of ​​the positive electrode active material 100, or the like.

[0395] For example, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 as follows.

[0396] First, the cathode active material 100 is processed by FIB or the like to expose the cross section. At this time, it is preferable to cover the cathode active material 100 with a protective film, a protective agent, or the like. Next, an SEM image of the interface between the protective film or the like and the cathode active material 100 is taken. The SEM image is subjected to noise processing using image processing software. For example, Gaussian blurring (σ=2) is performed, and then binarization is performed. Furthermore, interface extraction is performed using image processing software. Furthermore, the interface line between the protective film or the like and the cathode active material 100 is selected using an automatic selection tool or the like, and data is extracted to a spreadsheet software or the like. Using the functions of the spreadsheet software or the like, correction is performed from a regression curve (quadratic regression), and a parameter for calculating roughness is obtained from the data after the slope correction, and the root mean square surface roughness (RMS) is calculated by calculating the standard deviation. In addition, this surface roughness is the surface roughness at least at 400 nm of the outer periphery of the particle of the cathode active material.

[0397] The particle surfaces of the positive electrode active material 100 of this embodiment preferably have a root mean square (RMS) surface roughness, which is an index of roughness, of less than 3 nm, preferably less than 1 nm, and more preferably less than 0.5 nm.

[0398] For example, the actual specific surface area S measured by the constant volume gas adsorption method R and the ideal specific surface area S i The smoothness of the surface of the positive electrode active material 100 can also be expressed as a numerical value based on the ratio of the surface smoothness to the surface smoothness.

[0399] Ideal specific surface area S i is calculated assuming that all particles have the same diameter, the same weight, and an ideal spherical shape.

[0400] The median diameter D50 can be measured by a particle size distribution meter using a laser diffraction / scattering method, etc. The specific surface area can be measured by a specific surface area measuring device using a gas adsorption method by a constant volume method, for example.

[0401] The positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention has an ideal specific surface area S calculated from the median diameter D50. i and the actual specific surface area S R Ratio of S R / S i It is preferable that the ratio is 2.1 or less.

[0402] Alternatively, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 by the following method.

[0403] First, a surface SEM image of the positive electrode active material 100 is obtained. At this time, a conductive coating may be applied as a pretreatment for observation. The observation surface is preferably perpendicular to the electron beam. When comparing multiple samples, the measurement conditions and observation area are the same.

[0404] Next, using image processing software (for example, "ImageJ"), the above SEM image is converted to, for example, an 8-bit image (called a grayscale image). A grayscale image contains luminance (brightness information). For example, in an 8-bit grayscale image, luminance can be expressed as 2 to the power of 8 = 256 gradations. Dark areas have lower gradations, and bright areas have higher gradations. The change in luminance can be quantified in relation to the number of gradations. This numerical value is called the grayscale value. Obtaining the grayscale value makes it possible to numerically evaluate the unevenness of the positive electrode active material.

[0405] Furthermore, it is possible to display the luminance change of the target area in a histogram. A histogram is a three-dimensional representation of the gradation distribution in the target area, and is also called a luminance histogram. Obtaining a luminance histogram makes it possible to visually evaluate the unevenness of the positive electrode active material in an easily understandable manner.

[0406] When evaluating the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, the difference between the maximum and minimum values ​​of the grayscale value is preferably 120 or less, more preferably 115 or less, and even more preferably 70 to 115. The standard deviation of the grayscale value is preferably 11 or less, more preferably 8 or less, and even more preferably 4 to 8.

[0407] <Particle size distribution analysis using cross-sectional SEM images of positive electrodes> The particle size distribution of the positive electrode active material 100 can also be calculated from a cross-sectional SEM image of the positive electrode active material 100 by the following method.

[0408] First, an analysis region is cut out from the obtained cross-sectional SEM image. For example, a range of 50 μm or more × 100 μm or more can be cut out as a range having a sufficient area for image analysis, but this is not limited to this. Depending on factors such as the size of the positive electrode active material, a smaller area or a larger area may be cut out.

[0409] The cross-sectional SEM image may be cut out using the functions of image processing software. For example, ImageJ may be used as the image processing software, and the image may be cut out using its crop function.

[0410] Next, the cut-out first image is binarized using image processing software, and particle analysis is performed.

[0411] ImageJ, for example, can be used as the image processing software. The binarization process is explained below. The first image shown in a 256-value grayscale is used as a frequency graph excluding black (value 0) and white (value 255), and the low value side (HWHM_L) and high value side (HWHM_H) are obtained as the half width at half maximum (HWHM) of the maximum peak in the frequency graph. Next, the minimum value a of the range twice the width of HWHM_L on the low value side from the value that is the peak top (maximum frequency) of the maximum peak, and the maximum value b of the range twice the width of HWHM_H on the high value side are determined.

[0412] Next, binarization is performed so that the range of values ​​less than a is white, the range of values ​​between a and b is black, and the range of values ​​greater than b is white. Specifically, binarization is performed as Threshold(a,b) using the Threshold function of ImageJ. After that, random bright spots thought to be caused by conductive materials are removed using the Gray Morphology (radius=3, operator=open, type=circle) and Gray Morphology (radius=1, operator=close, type=circle) conditions, and a second image can be obtained.

[0413] Next, using the second image, the particle size (projected area) was determined to be 0.5 μm using the Analyze Particles function of ImageJ. 2 More than 700μm 2 The following particles are detected and the area S of each particle is obtained. Next, the diameter r of each particle is calculated based on the area S of each particle (Equation 1).

[0414]

number

[0415] In this way, the particle size distribution of each particle can be calculated from the cross-sectional SEM image. Performing the above analysis is called performing particle size distribution analysis using a cross-sectional SEM image of the positive electrode.

[0416] A coating portion may be attached to at least a portion of the surface of the positive electrode active material 100. Fig. 18 shows an example of a positive electrode active material 100 having a coating portion 104 attached thereto.

[0417] The coating portion 104 is preferably formed by the accumulation of decomposition products of the electrolyte and the organic electrolyte solution during charging and discharging. x When charging and discharging are repeated such that x in CoO2 is 0.24 or less, it is expected that the charge-discharge cycle characteristics will be improved by having a coating portion derived from the electrolyte on the surface of the positive electrode active material 100. This is due to reasons such as suppressing an increase in impedance on the surface of the positive electrode active material or suppressing the elution of cobalt. The coating portion 104 preferably contains, for example, carbon, oxygen, and fluorine. Furthermore, when LiBOB and / or SUN (suberonitrile) are used as the electrolyte, a good quality coating portion is easily obtained. Therefore, the coating portion 104 having one or more selected from boron, nitrogen, sulfur, and fluorine may be a good quality coating portion and is preferable. In addition, the coating portion 104 does not have to cover the entire positive electrode active material 100. For example, it is sufficient to cover 50% or more of the surface of the positive electrode active material 100, more preferably 70% or more, and even more preferably 90% or more.

[0418] <Powder Resistance Measurement> The positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention has a stable crystal structure even at high voltage. Since the crystal structure of the positive electrode active material is stable in a charged state, a decrease in charge / discharge capacity due to repeated charging and discharging can be suppressed. The positive electrode active material 100 having the above-mentioned excellent properties is characterized by the above-mentioned < <xrd>> In Li x It has been explained that when x in CoO2 is small, it has a crystal structure of O3' type and / or monoclinic O1(15) type. <edx>> described a preferable distribution of the additive elements when the positive electrode active material 100 was subjected to STEM-EDX analysis. Furthermore, the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention is also characterized by the volume resistivity of the powder.

[0419] The positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention has a characteristic that the volume resistivity of the powder of the positive electrode active material 100 is 1.0×10 8 Ω cm or more 1.0×10 10 It is preferable that the resistance is 5.0×10 8 Ω cm or more 1.5×10 9 It is more preferable that the resistivity is Ω·cm or less.

[0420] The positive electrode active material 100 having the above volume resistivity has a stable crystal structure even at high voltages. Therefore, the volume resistivity of the powder of the positive electrode active material 100 being within the above range can be used as an indicator that the surface layer portion 100a, which is important for the crystal structure of the positive electrode active material to be stable in a charged state, has been well formed.

[0421] A method for measuring the volume resistivity of powder of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention will be described.

[0422] The powder volume resistivity measuring device preferably has an instrument part having a terminal for resistance measurement and a mechanism for applying pressure to the powder to be measured. The terminal for resistance measurement preferably has four terminals (also called four probes). As a measuring device having a terminal for resistance measurement and a mechanism for applying pressure to the powder (sample) to be measured, for example, MCP-PD51 manufactured by Mitsubishi Chemical Analytech Co., Ltd. can be used. As the resistance measuring device, a low resistance measuring device Loresta-GP or a high resistance measuring device Hiresta-GP can be used. Loresta-GP can be used to measure low resistance samples, and Hiresta-GP can be used to measure high resistance samples. In addition, a stable environment such as a dry room is preferable as the measurement environment. As the dry room environment, for example, a temperature environment of 25°C and a dew point environment of -40°C or less are preferable. When performing measurements in a high humidity environment, the electrical resistance decreases due to the influence of moisture in the air, and the original physical property value may not be obtained.

[0423] The measurement of the volume resistivity of a powder using the measuring device shown above will be described. First, a powder sample is set in the measuring section. In the measuring section, the powder sample and a terminal for resistance measurement are in contact with each other, and pressure can be applied to the powder sample. The measuring section also has a structure for measuring the volume of the powder sample in the measuring section. Specifically, the measuring section has a cylindrical space, and the powder sample is set in the space. The structure for measuring the volume of the powder sample described above can measure the height of the powder set in the space, thereby measuring the volume occupied by the powder at that time.

[0424] In measuring the volume resistivity of a powder, the electrical resistance of the powder and the volume of the powder are measured while pressure is applied to the powder. The pressure applied to the powder can be measured under a variety of conditions. For example, the electrical resistance and the volume of the powder can be measured under each of the pressure conditions of 16 MPa, 25 MPa, 38 MPa, 51 MPa, and 64 MPa. The volume resistivity of the powder can be calculated from the measured electrical resistance and volume of the powder.

[0425] When the above-described measurement is performed, the volume resistivity of the powder of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention is 1.0×10 when measured under a pressure of 64 MPa. 8 Ω cm or more 1.0×10 10 When the dielectric constant is less than 5.0×10 Ω·cm, favorable cycle characteristics are observed in charge-discharge cycle tests under high charging voltage conditions. 8 Ω cm or more 1.5×10 9 When the electrical resistance is Ω·cm or less, more favorable cycle characteristics are exhibited in a charge-discharge cycle test under high voltage conditions.

[0426] Unless otherwise specified in the present specification, the volume resistivity measured as described above is the volume resistivity of the powder.

[0427] <Ion Chromatography> A method for measuring the powder of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention by ion chromatography will be described. The measurement by ion chromatography involves a pretreatment step of dissolving the powder of the positive electrode active material 100 in acid to obtain a solution for measurement, and a measurement step of measuring the solution.

[0428] The ion chromatography apparatus and conditions are not particularly limited. For example, the measurement can be performed using the following apparatus and conditions. As the ion chromatography apparatus, for example, the ion chromatography system Dionex ICS-2100 manufactured by Thermo Fisher Scientific can be used.

[0429] An example of the pretreatment of ion chromatography will be described. 250 mg of powder of the positive electrode active material 100 and 2 ml of 0.05 Mol / L H2SO4 aqueous solution are prepared, put into a glass container with a lid, and mixed to obtain a first mixed solution. For the mixing, ultrasonic waves may be applied for about 1 hour. Then, the container is left to stand in a room temperature environment for 12 hours or more. Then, 1 ml of the filtrate obtained by filtering the first mixed solution is mixed with 9 ml of pure water to obtain a second mixed solution. In this way, the powder of the positive electrode active material 100 can be pretreated.

[0430] Next, the second mixed solution obtained by the above pretreatment is used to perform ion chromatography, which may include anion analysis and cation analysis.

[0431] An example of the conditions for anion analysis is shown below. Anion analysis can be performed at 35°C using a Dionex IonPac AG20 (2 x 50 mm) or Dionex IonPac AS20 (2 x 250 mm) column. A KOH aqueous solution is used as the eluent, and the flow rate is preferably set to 0.44 ml / min. It is preferable to perform gradient measurement so that the concentration of the KOH aqueous solution gradually increases. An electric conductivity detector is used as the detector, and a mixed anion standard solution manufactured by Kanto Chemical Co., Ltd. can be used to create a calibration curve.

[0432] An example of the conditions for cation analysis is shown below. Cation analysis can be performed at 30°C using a Dionex IonPac CG16 (3 x 50 mm) or Dionex IonPac CS16 (3 x 250 mm) column. The eluent should be an aqueous solution of methanesulfonic acid (MSA), and the flow rate should be 0.36 ml / min. It is recommended that the concentration of the MSA aqueous solution be kept constant and that isocratic measurements be performed. An electric conductivity detector is used as the detector, and a mixed cation standard solution manufactured by Kanto Chemical Co., Ltd. can be used to create a calibration curve.

[0433] The above-described ion chromatography measurement allows quantitative measurement of anions such as fluorine (F) and chlorine (Cl), and allows quantitative measurement of cations such as lithium (Li), magnesium (Mg), cobalt (Co), and nickel (Ni).

[0434] In ion chromatography measurement of a powder of the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention, the weight of fluorine relative to the weight of the powder is preferably 100 ppm or more and 1000 ppm or less, and more preferably 100 ppm or more and 200 ppm or less.

[0435] This embodiment mode can be used in combination with other embodiment modes.

[0436] (Embodiment 3) In this embodiment, an example of a manufacturing method of a positive electrode active material 100 that can be used for the battery 10 of one embodiment of the present invention will be described with reference to FIGS.

[0437] In order to prepare the positive electrode active material 100 having the distribution, composition, and / or crystal structure of the additive element as described in the previous embodiment, the method of adding the additive element is important. At the same time, it is also important that the crystallinity of the inner portion 100b is good.

[0438] Therefore, in the process of producing the positive electrode active material 100, it is preferable to first synthesize lithium cobalt oxide, and then mix in the additive element source and perform a heat treatment.

[0439] In the method of synthesizing lithium cobalt oxide having an additive element by mixing a cobalt source and a lithium source at the same time, it is difficult to increase the concentration of the additive element in the surface layer portion 100a. Furthermore, if the additive element source is only mixed after the lithium cobalt oxide is synthesized and heating is not performed, the additive element will only adhere to the lithium cobalt oxide without being dissolved in the lithium cobalt oxide. If sufficient heating is not performed, it is difficult to distribute the additive element well. Therefore, it is preferable to mix the additive element source after synthesizing lithium cobalt oxide and perform a heat treatment. This heat treatment after mixing the additive element source is sometimes called annealing.

[0440] However, if the annealing temperature is too high, cation mixing occurs, increasing the possibility that an added element, such as magnesium, will enter the cobalt site. Magnesium present in the cobalt site will be mixed with Li x When x in CoO2 is small, there is no effect of maintaining the layered rock-salt crystal structure of R-3m. Furthermore, if the heat treatment temperature is too high, there are concerns that adverse effects such as cobalt being reduced to divalent and lithium being evaporated may occur.

[0441] Therefore, it is preferable to mix a material that functions as a flux with the additive element source. If the melting point is lower than that of lithium cobalt oxide, the material can function as a flux. For example, fluorine compounds such as lithium fluoride are suitable. Adding a flux lowers the melting point of the additive element source and lithium cobalt oxide. Lowering the melting point makes it easier to distribute the additive element well at a temperature where cation mixing is unlikely to occur.

[0442] <<Method 1 for preparing positive electrode active material>> A manufacturing method 1 of the positive electrode active material 100 will be described with reference to FIGS.

[0443] <Step S11> In step S11 shown in FIG. 19, a lithium source (Li source) and a cobalt source (Co source) are prepared as starting materials, that is, lithium and transition metal materials, respectively.

[0444] As the lithium source, it is preferable to use a compound containing lithium, such as lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. It is preferable that the lithium source has high purity, and for example, it is preferable to use a material with a purity of 99.99% or more.

[0445] As the cobalt source, it is preferable to use a compound containing cobalt, for example, cobalt oxide such as tricobalt tetroxide, cobalt hydroxide, or the like.

[0446] The cobalt source is preferably of high purity, for example, a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and even more preferably 5N (99.999%) or more may be used. By using a material of high purity, impurities in the positive electrode active material can be controlled. As a result, the capacity of the secondary battery is increased and / or the reliability of the secondary battery is improved.

[0447] In addition, the cobalt source preferably has high crystallinity, for example, single crystal grains. The crystallinity of the cobalt source can be evaluated using a TEM (transmission electron microscope) image, a STEM (scanning transmission electron microscope) image, a HAADF-STEM (high-angle annular dark-field scanning transmission electron microscope) image, an ABF-STEM (annular bright-field scanning transmission electron microscope) image, or an X-ray diffraction (XRD), electron beam diffraction, neutron beam diffraction, or the like. The above-mentioned methods for evaluating crystallinity can be applied not only to the evaluation of cobalt sources, but also to the evaluation of other crystallinity.

[0448] <Step S12> Next, in step S12 shown in FIG. 19, the lithium source and the cobalt source are pulverized and mixed to prepare a mixed material. The pulverization and mixing can be performed in a dry or wet manner. The wet method is preferable because it can be crushed into smaller pieces. When performing the wet method, a solvent is prepared. As the solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent that does not easily react with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. It is preferable to mix the lithium source and the cobalt source with dehydrated acetone with a purity of 99.5% or more, in which the moisture content is suppressed to 10 ppm or less, and then pulverize and mix them. By using dehydrated acetone with the above-mentioned purity, it is possible to reduce impurities that may be mixed in.

[0449] A ball mill, a bead mill, or the like can be used as a means for pulverizing and mixing. When using a ball mill, it is preferable to use aluminum oxide balls or zirconium oxide balls as pulverizing media. Zirconium oxide balls are preferable because they emit less impurities. Furthermore, when using a ball mill, a bead mill, or the like, it is preferable to set the peripheral speed to 100 mm / s or more and 2000 mm / s or less in order to suppress contamination from the media. In this embodiment, the peripheral speed is set to 838 mm / s (rotation speed 400 rpm, ball mill diameter 40 mm).

[0450] <Step S13> Next, in step S13 shown in FIG. 19, the mixed material is heated. The heating is preferably performed at 800°C or more and 1100°C or less, more preferably at 900°C or more and 1000°C or less, and even more preferably at about 950°C. If the temperature is too low, the decomposition and melting of the lithium source and the cobalt source may be insufficient. On the other hand, if the temperature is too high, defects may occur due to lithium transpiration from the lithium source and / or cobalt being excessively reduced. For example, cobalt may change from trivalent to divalent, inducing oxygen defects and the like.

[0451] If the heating time is too short, lithium cobalt oxide will not be synthesized, but if it is too long, productivity will decrease. For example, the heating time is preferably 1 hour or more and 100 hours or less, and more preferably 2 hours or more and 20 hours or less.

[0452] The rate of temperature rise depends on the heating temperature reached, but it is recommended to set it to 80°C / h or more and 250°C / h or less. For example, if heating at 1000°C for 10 hours, the rate of temperature rise should be 200°C / h.

[0453] Heating is preferably performed in an atmosphere with little water, such as dry air, for example, with a dew point of -50° C. or less, more preferably with a dew point of -80° C. or less. In this embodiment, heating is performed in an atmosphere with a dew point of -93° C. In order to suppress impurities that may be mixed into the material, it is preferable that the impurity concentrations of CH4, CO, CO2, H2, etc. in the heating atmosphere are each 5 ppb (parts per billion) or less.

[0454] The heating atmosphere is preferably an atmosphere containing oxygen. For example, there is a method of continuously introducing dry air into the reaction chamber. In this case, the flow rate of the dry air is preferably 10 L / min. The method of continuously introducing oxygen into the reaction chamber and having oxygen flow through the reaction chamber is called flow.

[0455] When the heating atmosphere is an atmosphere containing oxygen, a method that does not allow oxygen to flow may be used. For example, the reaction chamber may be depressurized and then filled with oxygen (or purged) to prevent the oxygen from entering or leaving the reaction chamber. For example, the reaction chamber may be depressurized to -970 hPa and then filled with oxygen to 50 hPa.

[0456] After heating, the material may be naturally cooled, but it is preferable that the time required for the material to cool from the specified temperature to room temperature is within a range of 10 to 50 hours. However, cooling to room temperature is not always necessary, and it is sufficient to cool the material to a temperature that is acceptable for the next step.

[0457] The heating in this step may be performed using a rotary kiln or a roller hearth kiln. Heating using a rotary kiln can be performed while stirring in either a continuous or batch type.

[0458] The crucible used for heating is preferably an aluminum oxide crucible. An aluminum oxide crucible is a material that does not easily release impurities. In this embodiment, an aluminum oxide crucible with a purity of 99.9% is used. It is preferable to place a lid on the crucible when heating it. This can prevent the material from volatilizing.

[0459] It is preferable to use a crucible that has been used multiple times rather than a new one. In this specification, a new crucible is used for lithium, transition metal M, etc. T The term "crucible that has been used multiple times" refers to a crucible that has been heated twice or less with materials containing lithium, transition metals, and / or additive elements. T The term "a crucible" refers to a crucible that has undergone a process of heating the crucible with and / or a material containing an additive element three or more times. This is because, when a new crucible is used, there is a risk that some of the materials, including lithium fluoride, may be absorbed, diffused, moved, and / or attached to the sheath during heating. If some of the materials are lost due to this, there is a growing concern that the distribution of elements in the surface layer of the positive electrode active material may not be within the desired range. On the other hand, this risk is less likely with a crucible that has been used multiple times.

[0460] After the heating is completed, the material may be crushed and sieved as necessary. When recovering the heated material, the material may be transferred from the crucible to a mortar and then recovered. It is preferable to use an aluminum oxide mortar for the mortar. The aluminum oxide mortar is made of a material that does not easily release impurities. Specifically, an aluminum oxide mortar with a purity of 90% or more, preferably 99% or more, is used. Note that the same heating conditions as those in step S13 can be applied to the heating steps described below other than step S13.

[0461] <Step S14> By the above process, lithium cobalt oxide (LiCoO2) can be synthesized as shown in step S14 in FIG.

[0462] Although the example of producing the composite oxide by the solid phase method as in steps S11 to S14 has been shown, the composite oxide may be produced by a coprecipitation method or a hydrothermal method.

[0463] Note that lithium cobalt oxide synthesized in advance may be used in step S14. In this case, steps S11 to S13 can be omitted. By carrying out step S15 on lithium cobalt oxide synthesized in advance, lithium cobalt oxide with a smooth surface can be obtained.

[0464] <Step S20> Next, as shown in step S20, it is preferable to add an additive element to the lithium cobalt oxide. In the method for producing a positive electrode active material described in this embodiment, the additive element is added in a plurality of steps, so that the additive element added first in the flow shown in Fig. 19 is described as A1, the additive element added second time is A2, and the additive element added third time is A3. The step of adding the additive element A1 will be described with reference to Fig. 20(A).

[0465] <Step S21> 20(A), an additive element source (A1 source) to be added to lithium cobalt oxide is prepared. A lithium source may be prepared together with the A1 source.

[0466] The additive element A1 may be any of the additive elements described in the previous embodiment. Specifically, one or more elements selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, and boron may be used. In addition, one or two elements selected from bromine and beryllium may be used.

[0467] When magnesium is selected as the additive element, the source of the additive element can be called a magnesium source. As the magnesium source, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. can be used. In addition, a plurality of the above-mentioned magnesium sources may be used.

[0468] When fluorine is selected as the additive element, the additive element source can be called a fluorine source. As the fluorine source, for example, lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF3, CeF4), lanthanum fluoride (LaF3), or sodium aluminum hexafluoride (Na3AlF6) can be used. Among these, lithium fluoride is preferred because it has a relatively low melting point of 848° C. and is easily melted in the heating step described below.

[0469] Magnesium fluoride can be used as both the fluorine source and the magnesium source, and lithium fluoride can be used as the lithium source. Another lithium source that can be used in step S21 is lithium carbonate.

[0470] The fluorine source may be a gas, such as fluorine (F2), carbon fluoride, sulfur fluoride, oxygen fluoride (OF2, O2F2, O3F2, O4F2, O5F2, O6F2, O2F), or nitrogen trifluoride (NF3), which may be mixed into the atmosphere in the heating step described below. A plurality of the above-mentioned fluorine sources may be used.

[0471] In the manufacturing method 1 of the positive electrode active material described in FIG. 19 to FIG. 20(C), magnesium and fluorine are used as the additive element A1. Lithium fluoride (LiF) is prepared as the fluorine source, and magnesium fluoride (MgF2) is prepared as the fluorine source and magnesium source. When lithium fluoride and magnesium fluoride are mixed at about LiF:MgF2=65:35 (molar ratio), the effect of lowering the melting point is maximized. On the other hand, if the amount of lithium fluoride is large, there is a concern that the lithium becomes excessive and the cycle characteristics deteriorate. Therefore, the molar ratio of lithium fluoride and magnesium fluoride is preferably LiF:MgF2=x:1 (0≦x≦1.9), more preferably LiF:MgF2=x:1 (0.1≦x≦0.5), and even more preferably LiF:MgF2=x:1 (x=0.33 or its vicinity). In this specification, etc., "nearby" refers to a value that is greater than 0.9 times and less than 1.1 times the value.

[0472] <Step S22> 20(A), the magnesium source and the fluorine source are pulverized and mixed. This step can be performed under the pulverization and mixing conditions selected from those described in step S12.

[0473] <Step S23> Next, in step S23 shown in Fig. 20(A), the above-mentioned crushed and mixed materials are collected to obtain the A1 source. Note that the A1 source shown in step S23 has multiple starting materials and can be called a mixture.

[0474] The particle size of the mixture is preferably D50 (median diameter) 600 nm to 10 μm, more preferably 1 μm to 5 μm. Even when a single material is used as the additive element source, the D50 (median diameter) is preferably 600 nm to 10 μm, more preferably 1 μm to 5 μm.

[0475] When such a finely powdered mixture (including the case where only one kind of additive element is included) is mixed with lithium cobalt oxide in a later step, the mixture can be easily attached uniformly to the surface of the lithium cobalt oxide particles. If the mixture is attached uniformly to the surface of the lithium cobalt oxide particles, it is preferable because the additive element can be easily distributed or diffused uniformly in the surface layer portion 100a of the composite oxide after heating.

[0476] <Step S31> 19, lithium cobalt oxide and the Al source are mixed. The ratio of the number of cobalt atoms Co in the lithium cobalt oxide to the number of magnesium atoms Mg in the Al source is preferably Co:Mg=100:y (0.1≦y≦6), and more preferably Co:Mg=100:y (0.3≦y≦3).

[0477] The mixing in step S31 is preferably performed under milder conditions than the mixing in step S12 in order not to destroy the shape of the lithium cobalt oxide particles. For example, the mixing is preferably performed under conditions of a lower rotation speed or a shorter time than in step S12. It can also be said that the dry method is a milder condition than the wet method. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconium oxide balls as the media.

[0478] In this embodiment, the materials are mixed in a ball mill using zirconium oxide balls with a diameter of 1 mm at 150 rpm for 1 hour in a dry room with a dew point of -100°C or higher and -10°C or lower.

[0479] <Step S32> 19, the mixed materials are collected to obtain a mixture 901. When collecting the materials, they may be crushed and then sieved, if necessary.

[0480] <Step S33> Next, in step S33 shown in FIG. 19, the mixture 901 is heated. The heating conditions can be selected from those described in step S13. The heating time is preferably 2 hours or more. At this time, the pressure inside the furnace may be higher than atmospheric pressure in order to increase the oxygen partial pressure of the heating atmosphere. This is because if the oxygen partial pressure of the heating atmosphere is insufficient, cobalt, etc. will be reduced, and lithium cobalt oxide, etc. may not be able to maintain the layered rock salt type crystal structure.

[0481] Here, a supplementary note on the heating temperature will be provided. The lower limit of the heating temperature in step S33 must be equal to or higher than the temperature at which the reaction between the lithium cobalt oxide and the additive element source proceeds. The temperature at which the reaction proceeds may be any temperature at which interdiffusion of elements contained in the lithium cobalt oxide and the additive element source occurs, and may be lower than the melting temperatures of these materials. An oxide will be used as an example to explain the melting temperature T m 0.757 times (Tammann temperature T d ) solid-phase diffusion occurs. Therefore, the heating temperature in step S33 should be 650° C. or higher.

[0482] Of course, the reaction proceeds more easily if the temperature is equal to or higher than the melting temperature of one or more of the materials contained in the mixture 901. For example, when LiF and MgF2 are contained as the additive element source, the eutectic point of LiF and MgF2 is around 742°C, so that the lower limit of the heating temperature in step S33 is preferably set to 742°C or higher.

[0483] In addition, a mixture 901 obtained by mixing LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio) shows an endothermic peak at about 830° C. in differential scanning calorimetry (DSC measurement). Therefore, the lower limit of the heating temperature is more preferably 830° C. or higher.

[0484] A higher heating temperature is preferable because the reaction proceeds more easily, the heating time is shorter, and the productivity is high.

[0485] The upper limit of the heating temperature is set to be lower than the decomposition temperature (1130°C) of lithium cobalt oxide. At temperatures close to the decomposition temperature, there is a concern that lithium cobalt oxide may decompose, albeit in a small amount. Therefore, the temperature is preferably 1000°C or lower, more preferably 950°C or lower, and even more preferably 900°C or lower.

[0486] Considering these, the heating temperature in step S33 is preferably 650°C to 1130°C, more preferably 650°C to 1000°C, even more preferably 650°C to 950°C, and even more preferably 650°C to 900°C. Also, it is preferably 742°C to 1130°C, more preferably 742°C to 1000°C, even more preferably 742°C to 950°C, and even more preferably 742°C to 900°C. Also, it is preferably 830°C to 1130°C, more preferably 830°C to 1000°C, even more preferably 830°C to 950°C, and even more preferably 830°C to 900°C.

[0487] Furthermore, when the mixture 901 is heated, it is preferable to control the partial pressure of fluorine or fluoride resulting from the fluorine source or the like within an appropriate range.

[0488] In the manufacturing method described in this embodiment, some materials, for example, LiF, which is a fluorine source, may function as a flux. This function allows the heating temperature to be lowered to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, to 742°C or higher and 950°C or lower, and additive elements such as magnesium can be distributed in the surface layer to manufacture a positive electrode active material with good characteristics.

[0489] However, since LiF has a lower specific gravity in a gaseous state than oxygen, LiF may volatilize or sublime when heated, and if it volatilizes, the amount of LiF in the mixture 901 will decrease. This weakens its function as a flux. Therefore, it is necessary to heat while suppressing the volatilization of LiF. Even if LiF is not used as the fluorine source, etc., Li on the LiCoO2 surface may react with F of the fluorine source to produce LiF, which may then volatilize. Therefore, even if a fluoride with a higher melting point than LiF is used, it is necessary to suppress the volatilization in the same way.

[0490] Therefore, it is preferable to heat the mixture 901 in an atmosphere containing LiF, that is, to heat the mixture 901 in a state where the partial pressure of LiF is high in the heating furnace. By such heating, the volatilization of LiF in the mixture 901 can be suppressed.

[0491] The heating in this step is preferably performed so as not to cause adhesion between particles of the mixture 901. If the particles of the mixture 901 adhere to each other during heating, the contact area with oxygen in the atmosphere decreases, and the route along which the additive element (e.g., fluorine) diffuses is blocked, which may result in poor distribution of the additive element (e.g., magnesium and fluorine) in the surface layer.

[0492] It is also believed that if an additive element (e.g., fluorine) is uniformly distributed in the surface layer, a smooth positive electrode active material with few irregularities can be obtained. Therefore, in order to maintain the smooth surface or to make it even smoother after the heating in step S15 in this process, it is better for the particles of mixture 901 not to stick together.

[0493] In addition, when heating is performed using a rotary kiln, it is preferable to control the flow rate of the oxygen-containing atmosphere in the kiln. For example, it is preferable to reduce the flow rate of the oxygen-containing atmosphere, or to first purge the atmosphere and not flow the atmosphere after introducing the oxygen atmosphere into the kiln. If oxygen is flowed, the fluorine source may evaporate, which is not preferable in terms of maintaining the smoothness of the surface.

[0494] When heating is performed using a roller hearth kiln, the mixture 901 can be heated in an atmosphere containing LiF, for example, by placing a lid on a container containing the mixture 901.

[0495] Regarding the heating time, the heating time varies depending on conditions such as the heating temperature, the size and composition of the lithium cobalt oxide in step S14, etc. When the lithium cobalt oxide is small, a lower temperature or a shorter heating time may be more preferable than when the lithium cobalt oxide is large.

[0496] When the median diameter (D50) of the lithium cobalt oxide in step S14 of Fig. 19 is about 12 µm, the heating temperature is preferably, for example, 650°C or more and 950°C or less. The heating time is preferably, for example, 3 hours or more and 60 hours or less, more preferably 10 hours or more and 30 hours or less, and further preferably about 20 hours. The temperature reduction time after heating is preferably, for example, 10 hours or more and 50 hours or less.

[0497] On the other hand, when the median diameter (D50) of the lithium cobalt oxide in step S14 is about 7 μm, the heating temperature is preferably, for example, 650° C. to 950° C. The heating time is preferably, for example, 1 hour to 10 hours, more preferably about 5 hours. The cooling time after heating is preferably, for example, 10 hours to 50 hours.

[0498] <Step S34> 19, the heated material is recovered and crushed as necessary to obtain a composite oxide 902. In this production method, the composite oxide 902 can also be called lithium cobalt oxide to which magnesium is added, or lithium cobalt oxide to which magnesium and fluorine are added. In other words, the composite oxide 902 may be used as the positive electrode active material 100 of the battery 10 without carrying out the processes after step S40.

[0499] <Step S40> Next, in step S40 shown in FIG. 19, an additive element source (A2 source) is required. The additive element A2 can be the additive element described in step S21. In the manufacturing method 1 of the positive electrode active material described in FIG. 19 to FIG. 20(C), nickel and aluminum are used as the additive element A2. Nickel oxide, nickel hydroxide, etc. can be used as the nickel source. Aluminum oxide, aluminum hydroxide, etc. can be used as the aluminum source. As shown in steps S41 to S43 in FIG. 20(B), the nickel source and the aluminum source can be crushed to obtain the A2 source. The crushing conditions can be taken into consideration of the conditions in step S22.

[0500] <Step S51> 19, the composite oxide 902 and the A2 source are mixed. The mixing conditions can be taken into consideration in the description of step S31.

[0501] <Step S52> 19, the mixed materials are collected to obtain a mixture 903. When collecting the materials, they may be crushed and then sieved, if necessary.

[0502] <Step S53> 19, the mixture 903 is heated. The heating conditions can be determined by referring to the description of step S33.

[0503] <Step S54> 19, the heated material is recovered and crushed as necessary to obtain a composite oxide 904. In this production method, the composite oxide 904 can also be called lithium cobalt oxide to which magnesium, nickel, and aluminum are added, or lithium cobalt oxide to which magnesium, fluorine, nickel, and aluminum are added. In other words, the composite oxide 904 may be used as the positive electrode active material 100 of the battery 10 without carrying out the processes from step S60 onward.

[0504] <Step S60> Next, in step S60 shown in FIG. 19, an additive element source (A3 source) is required. The additive element A3 can be the additive element described in step S21. In the manufacturing method 1 of the positive electrode active material described in FIG. 19 to FIG. 20(C), titanium is used as the additive element A3. The titanium source can be lithium titanate, titanium oxide, titanium hydroxide, or the like. As shown in steps S61 to S63 in FIG. 20(C), the titanium source can be pulverized to obtain the A3 source. The pulverization conditions can be taken into consideration of the conditions in step S22.

[0505] <Step S71> 19, the composite oxide 904 is mixed with the A3 source. The mixing conditions can be taken into consideration in the description of step S31.

[0506] <Step S72> 19, the mixed materials are collected to obtain a mixture 905. When collecting the materials, they may be crushed and then sieved, if necessary.

[0507] <Step S73> 19, the mixture 905 is heated. The heating conditions can be determined by referring to the description of step S33.

[0508] <Step S74> 19, the heated material is collected and crushed as necessary to obtain the positive electrode active material 100. At this time, it is preferable to further sieve the collected particles. Through the above steps, the positive electrode active material 100 that can be used in the battery 10 of one embodiment of the present invention can be produced. The positive electrode active material of one embodiment of the present invention has a smooth surface.

[0509] The positive electrode active material 100 having a smooth surface may be more resistant to physical destruction due to pressure, etc. than a positive electrode active material having a non-smooth surface. For example, the positive electrode active material 100 is less likely to be destroyed in a test involving pressure, such as a nail penetration test, and as a result, safety may be improved.

[0510] [Initial heating] In the above-described manufacturing method, it may be more preferable to perform heating after the lithium cobalt oxide is synthesized and before the additive element is mixed in. This heating is called initial heating.

[0511] The initial heating causes lithium to be desorbed from a portion of the surface layer 100a of the lithium cobalt oxide, resulting in a more favorable distribution of the additive elements.

[0512] More specifically, it is believed that initial heating makes it easier to vary the distribution depending on the added element through the following mechanism. First, lithium is removed from part of the surface layer 100a by initial heating. Next, this lithium-deficient surface layer 100a is mixed with an added element source, such as a nickel source, an aluminum source, or a magnesium source, and heated. Of the added elements, magnesium is a typical divalent element, and nickel is a transition metal that is prone to becoming a divalent ion. As a result, Mg is released from part of the surface layer 100a. 2+ and Ni 2+ and Co reduced by lithium deficiency. 2+ However, since this phase is formed only in a part of the surface layer portion 100a, it may not be clearly observed in an electron microscope image such as a STEM image or an electron beam diffraction pattern.

[0513] Among the additive elements, nickel diffuses to the inside 100b when the surface layer 100a is a layered rock-salt type lithium cobalt oxide, but tends to remain in the surface layer 100a when part of the surface layer 100a is a rock-salt type. Therefore, by performing initial heating, it is possible to make it easier for divalent additive elements such as nickel to remain in the surface layer 100a. The effect of this initial heating is particularly large on the surface other than the (001)-oriented surface of the positive electrode active material 100 and its surface layer 100a.

[0514] In addition, in these rock salt structures, the bond distance between metal Me and oxygen (Me-O distance) tends to be longer than in the layered rock salt structure.

[0515] For example, rock salt Ni 0.5 Mg 0.5 The Me-O distance in O is 2.09(×10 -10 m), and the Me-O distance in rock-salt MgO is 2.11 (× 10 -10 Even if a spinel phase is formed in a part of the surface layer 100a, the Me-O distance of the spinel NiAl2O4 is 2.0125 (×10 -10 m), and the Me-O distance of spinel-type MgAl2O4 is 2.02 (× 10 -10 m). In both cases, the Me-O distance is 2(×10 -10 m).

[0516] On the other hand, in the layered rock salt type, the bond distance between metals other than lithium and oxygen is shorter than the above. For example, the Al-O distance in the layered rock salt type LiAlO2 is 1.905(×10 -10 m) (Li-O distance is 2.11(×10 -10 m), and the Co-O distance in layered rock-salt LiCoO2 is 1.9224 (× 10 -10 m) (Li-O distance is 2.0916(×10 -10 m)).

[0517] According to Shannon's ionic radius, the ionic radius of 6-coordinate aluminum is 0.535(×10 -10 nm), and the ionic radius of 6-coordinate oxygen is 1.4 (× 10 -10 m), and the sum of these is 1.935(×10 -10 m).

[0518] From the above, it is considered that aluminum exists more stably in the non-lithium sites of the layered rock-salt type than in the rock-salt type, and therefore aluminum is more likely to be distributed in the deeper region having the layered rock-salt type and / or the interior 100b than in the region close to the surface having the rock-salt type phase in the surface layer portion 100a.

[0519] In addition, the initial heating is expected to have the effect of increasing the crystallinity of the layered rock-salt type crystal structure of the inner portion 100b.

[0520] However, initial heating is not necessarily required. In other heating steps, such as annealing, the atmosphere, temperature, time, etc. can be controlled to obtain Li x When x in CoO2 is small, a positive electrode active material 100 having an O3' type can sometimes be produced.

[0521] <<Preparation method 2 of positive electrode active material>> Next, a method 2 for producing a positive electrode active material, which is one embodiment of the present invention and is different from the method 1 for producing a positive electrode active material, will be described with reference to Fig. 21(A) and Fig. 21(B). The method 2 for producing a positive electrode active material differs from the method 1 for producing a positive electrode active material mainly in the number of times that an additive element is added. For the rest of the description, the description of the method 1 can be referred to.

[0522] In the positive electrode active material preparation method 1, LiM T Although the method of adding the additive element only after O2 is produced has been described, the present invention is not limited to the above method. The additive element may be added at other times or multiple times. The timing may be changed depending on the element.

[0523] For example, an additive element may be added to the lithium source and the cobalt source in step S11, that is, in the stage of the starting material of the composite oxide. The additive element source added at this time is shown as A0 source in FIG. 21(A). Then, lithium cobalt oxide having the additive element can be obtained in step S13. In this case, it is not necessary to separate the steps S11 to S14 from the steps S21 to S23. This method can be said to be simple and highly productive.

[0524] Alternatively, lithium cobalt oxide having some of the added elements may be used. For example, if lithium cobalt oxide having magnesium and fluorine added thereto is used, steps S11 to S14 and some of the steps S20 can be omitted. This method is simple and has high productivity.

[0525] Moreover, an additive element may be added to lithium cobalt oxide to which magnesium and fluorine have been added in advance.

[0526] In addition, in the positive electrode active material preparation method 1, magnesium and fluorine are used as the additive element A1, and nickel and aluminum are used as the additive element A2, and a preparation method in which they are added at different times has been described, but magnesium, fluorine, nickel and aluminum may be added simultaneously. Figures 21(A) and 21(B) show a method of adding these simultaneously as step S20a. This preparation method can also be said to be a simple and highly productive method because it can reduce the mixing and heating steps.

[0527] This embodiment mode can be used in combination with other embodiment modes.

[0528] (Embodiment 4) In this embodiment, an example in which a secondary battery which is one embodiment of the present invention is mounted on an electronic device will be described with reference to FIGS.

[0529] 22A to 22G show examples of electronic devices to which the secondary battery having the positive electrode active material described in the above embodiment is mounted. Examples of electronic devices to which the secondary battery is applied include television devices (also called televisions or television receivers), monitors for computers, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game machines, personal digital assistants, audio playback devices, and large game machines such as pachinko machines.

[0530] Furthermore, a secondary battery having a flexible shape can be incorporated along the curved surfaces of the inner or outer walls of a house or building, or the interior or exterior of an automobile.

[0531] 22A shows an example of a mobile phone. A mobile phone 7400 includes a display portion 7402 built into a housing 7401, operation buttons 7403, an external connection port 7404, a speaker 7405, a microphone 7406, and the like. Note that the mobile phone 7400 includes a secondary battery 7407. By using the secondary battery of one embodiment of the present invention as the secondary battery 7407, a lightweight mobile phone with a long life can be provided.

[0532] FIG. 22(B) shows the mobile phone 7400 in a bent state. When the mobile phone 7400 is deformed by an external force and bent as a whole, the secondary battery 7407 provided inside is also bent. FIG. 22(C) shows the bent state of the secondary battery 7407 at that time. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is fixed in a bent state. The secondary battery 7407 has a lead electrode electrically connected to a current collector.

[0533] FIG. 22D shows an example of a bangle-type display device. The portable display device 7100 includes a housing 7101, a display unit 7102, an operation button 7103, and a secondary battery 7104. FIG. 22E shows a bent state of the secondary battery 7104. When the secondary battery 7104 is worn on a user's arm in a bent state, the housing is deformed, and the curvature of the secondary battery 7104 changes in part or in whole. Note that the degree of bending at any point of the curve expressed by the value of the radius of the corresponding circle is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. Specifically, the housing or the main surface of the secondary battery 7104 changes in part or in whole when the radius of curvature is in the range of 40 mm to 150 mm. High reliability can be maintained if the radius of curvature of the main surface of the secondary battery 7104 is in the range of 40 mm to 150 mm. By using the secondary battery of one embodiment of the present invention as the secondary battery 7104, a lightweight portable display device with a long life can be provided.

[0534] 22F shows an example of a wristwatch-type portable information terminal. A portable information terminal 7200 includes a housing 7201, a display portion 7202, a band 7203, a buckle 7204, operation buttons 7205, an input / output terminal 7206, and the like.

[0535] The portable information terminal 7200 can execute various applications such as mobile telephone, e-mail, document browsing and creation, music playback, Internet communication, and computer games.

[0536] The display surface of the display portion 7202 is curved, and display can be performed along the curved display surface. The display portion 7202 is also provided with a touch sensor, and can be operated by touching the screen with a finger, a stylus, or the like. For example, an application can be started by touching an icon 7207 displayed on the display portion 7202.

[0537] The operation button 7205 can have various functions, such as time setting, power on / off operation, wireless communication on / off operation, silent mode activation / cancellation, power saving mode activation / cancellation, etc. For example, the function of the operation button 7205 can be freely set by an operating system built into the mobile information terminal 7200.

[0538] The mobile information terminal 7200 can also perform short-distance wireless communication according to a communication standard. For example, the mobile information terminal 7200 can communicate with a wireless headset to enable hands-free calling.

[0539] The portable information terminal 7200 also includes an input / output terminal 7206, and can directly exchange data with another information terminal via a connector. Charging can also be performed via the input / output terminal 7206. Note that charging may be performed wirelessly without using the input / output terminal 7206.

[0540] The display portion 7202 of the portable information terminal 7200 includes the secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a portable information terminal that is lightweight and has a long life can be provided. For example, the secondary battery 7104 shown in FIG. 22E can be incorporated in a curved state inside the housing 7201 or in a bendable state inside the band 7203.

[0541] The portable information terminal 7200 preferably has a sensor. For example, it is preferable that a fingerprint sensor, a pulse sensor, a human body sensor such as a body temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, or the like is mounted as the sensor.

[0542] 22G illustrates an example of an armband-type display device. The display device 7300 includes a display portion 7304 and a secondary battery of one embodiment of the present invention. The display device 7300 can also include a touch sensor in the display portion 7304 and can function as a portable information terminal.

[0543] The display surface of the display portion 7304 is curved, and display can be performed along the curved display surface. In addition, the display device 7300 can change the display state by short-range wireless communication according to a communication standard.

[0544] The display device 7300 also includes an input / output terminal, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the input / output terminal. Note that charging may be performed wirelessly without using the input / output terminal.

[0545] By using the secondary battery of one embodiment of the present invention as a secondary battery included in the display device 7300, a lightweight display device with a long lifetime can be provided.

[0546] An example in which the secondary battery having good cycle characteristics described in the above embodiment is mounted on an electronic device will be described with reference to FIG.

[0547] By using the secondary battery of one embodiment of the present invention as a secondary battery in daily electronic devices, products that are lightweight and have a long life can be provided. For example, daily electronic devices include electric toothbrushes, electric shavers, and electric beauty devices. For the secondary battery of these products, a stick-shaped secondary battery that is small, lightweight, and has a large discharge capacity is desired in consideration of ease of holding by users.

[0548] FIG. 22(H) is a perspective view of a device also called a tobacco-receiving smoking device (electronic cigarette). In FIG. 22(H), the electronic cigarette 7500 is composed of an atomizer 7501 including a heating element, a secondary battery 7504 that supplies power to the atomizer, and a cartridge 7502 including a liquid supply bottle, a sensor, and the like. To enhance safety, a protection circuit that prevents overcharging and / or overdischarging of the secondary battery 7504 may be electrically connected to the secondary battery 7504. The secondary battery 7504 shown in FIG. 22(H) has an external terminal so that it can be connected to a charging device. Since the secondary battery 7504 is the tip part when held, it is desirable that the total length is short and the weight is light. Since the secondary battery of one embodiment of the present invention has a high discharge capacity and good cycle characteristics, a small and lightweight electronic cigarette 7500 that can be used for a long period of time can be provided.

[0549] Fig. 23(A) shows an example of a wearable device. The wearable device uses a secondary battery as a power source. In addition, when a user uses the device in daily life or outdoors, in order to improve splash-proof performance, water resistance, or dust resistance, there is a demand for a wearable device that can be charged wirelessly as well as by wire with an exposed connector.

[0550] For example, the secondary battery according to one embodiment of the present invention can be mounted on a glasses-type device 4000 as shown in FIG. 23A. The glasses-type device 4000 includes a frame 4000a and a display unit 4000b. By mounting a secondary battery on temples of the curved frame 4000a, the glasses-type device 4000 can be lightweight, well-balanced in weight, and has a long continuous use time. By including the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a smaller housing can be realized.

[0551] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the headset type device 4001. The headset type device 4001 has at least a microphone unit 4001a, a flexible pipe 4001b, and an earphone unit 4001c. The secondary battery can be provided in the flexible pipe 4001b and / or the earphone unit 4001c. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a miniaturized housing can be realized.

[0552] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4002 that can be directly attached to the body. A secondary battery 4002b can be provided in a thin housing 4002a of the device 4002. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0553] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4003 that can be attached to clothing. A secondary battery 4003b can be provided in a thin housing 4003a of the device 4003. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0554] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the belt type device 4006. The belt type device 4006 has a belt portion 4006a and a wireless power receiving portion 4006b, and a secondary battery can be mounted inside the belt portion 4006a. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with miniaturization of the housing can be realized.

[0555] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the wristwatch device 4005. The wristwatch device 4005 has a display portion 4005a and a belt portion 4005b, and the secondary battery can be provided on the display portion 4005a or the belt portion 4005b. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0556] The display unit 4005a can display not only the time but also various other information such as incoming e-mails and phone calls.

[0557] In addition, since the wristwatch type device 4005 is a wearable device that is directly wrapped around the arm, it may be equipped with sensors that measure the user's pulse, blood pressure, etc. Data on the user's amount of exercise and health can be accumulated to manage the user's health.

[0558] FIG. 23(B) shows a perspective view of the wristwatch type device 4005 removed from the wrist.

[0559] 23C shows a side view of the display portion 4005. FIG. 23C shows a state in which a secondary battery 913 is built in the display portion 4005. The secondary battery 913 is the secondary battery described in the above embodiment. The secondary battery 913 is provided at a position overlapping with the display portion 4005a, and is small and lightweight.

[0560] 23(D) shows an example of a wireless earphone. Here, the wireless earphone is illustrated having a pair of main bodies 4100a and 4100b, but this does not necessarily have to be a pair.

[0561] The main bodies 4100a and 4100b each have a driver unit 4101, an antenna 4102, and a secondary battery 4103. They may also have a display unit 4104. They also preferably have a substrate on which a circuit such as a wireless IC is mounted, a charging terminal, and the like. They may also have a microphone.

[0562] The case 4110 has a secondary battery 4111. It is preferable that the case 4110 also has a board on which circuits such as a wireless IC and a charge control IC are mounted, and a charging terminal. It may also have a display unit, buttons, and the like.

[0563] The main bodies 4100a and 4100b can wirelessly communicate with other electronic devices such as smartphones. This allows the main bodies 4100a and 4100b to play back audio data sent from other electronic devices. If the main bodies 4100a and 4100b have a microphone, the audio captured by the microphone can be sent to the other electronic device, and the audio data processed by the electronic device can be sent back to the main bodies 4100a and 4100b for playback. This allows the main bodies 4100a and 4100b to be used as a translator, for example.

[0564] Further, the secondary battery 4103 in the main body 4100a can be charged from the secondary battery 4111 in the case 4110. A coin-type secondary battery, a cylindrical secondary battery, or the like can be used as the secondary battery 4111 and the secondary battery 4103. A secondary battery using the positive electrode active material 100 described in Embodiment 2 or 3 as a positive electrode has high energy density. By using the secondary battery 4103 and the secondary battery 4111 as the positive electrode, a structure that can accommodate space saving associated with miniaturization of wireless earphones can be realized.

[0565] 24A shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 arranged on the top surface of a housing 6301, a plurality of cameras 6303 arranged on the side surface, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, and the like. Although not shown, the cleaning robot 6300 is provided with tires, a suction port, and the like. The cleaning robot 6300 can move by itself, detect dust 6310, and suck up the dust from a suction port arranged on the bottom surface.

[0566] For example, the cleaning robot 6300 can analyze an image captured by the camera 6303 and determine the presence or absence of an obstacle such as a wall, furniture, or a step. When an object that may become entangled in the brush 6304, such as a wire, is detected by image analysis, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 includes a secondary battery 6306 according to one embodiment of the present invention and a semiconductor device or electronic component therein. By using the secondary battery 6306 according to one embodiment of the present invention in the cleaning robot 6300, the cleaning robot 6300 can be an electronic device with long operating time and high reliability.

[0567] Fig. 24(B) shows an example of a robot. The robot 6400 shown in Fig. 24(B) includes a secondary battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0568] The microphone 6402 has a function of detecting the user's voice, environmental sounds, etc. The speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user using the microphone 6402 and the speaker 6404.

[0569] The display unit 6405 has a function of displaying various information. The robot 6400 can display information desired by the user on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may be a removable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer are possible.

[0570] The upper camera 6403 and the lower camera 6406 have a function of capturing images of the surroundings of the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of an obstacle in the moving direction when the robot 6400 moves forward using the moving mechanism 6408. The robot 6400 can recognize the surrounding environment and move safely using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407.

[0571] The robot 6400 includes a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or electronic component inside the robot 6400. By using the secondary battery according to one embodiment of the present invention in the robot 6400, the robot 6400 can be a highly reliable electronic device with a long operating time.

[0572] Fig. 24C shows an example of an aircraft. An aircraft 6500 shown in Fig. 24C includes a propeller 6501, a camera 6502, a secondary battery 6503, and the like, and has a function of autonomous flight.

[0573] For example, image data captured by the camera 6502 is stored in the electronic component 6504. The electronic component 6504 can analyze the image data and detect the presence or absence of an obstacle when moving. The electronic component 6504 can estimate the remaining battery charge from a change in the power storage capacity of the secondary battery 6503. The flying object 6500 includes therein the secondary battery 6503 according to one embodiment of the present invention. By using the secondary battery according to one embodiment of the present invention in the flying object 6500, the flying object 6500 can be an electronic device with a long operating time and high reliability.

[0574] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0575] (Embodiment 5) In this embodiment, an example is described in which a secondary battery including the positive electrode active material of one embodiment of the present invention is mounted on a vehicle.

[0576] By installing secondary batteries in vehicles, next-generation clean energy vehicles such as hybrid vehicles (HVs), electric vehicles (EVs), and plug-in hybrid vehicles (PHVs) can be realized.

[0577] FIG. 25 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. An automobile 8400 illustrated in FIG. 25(A) is an electric automobile using an electric motor as a power source for running. Alternatively, it is a hybrid automobile in which an electric motor and an engine can be appropriately selected and used as a power source for running. By using one embodiment of the present invention, a vehicle with a long cruising distance can be realized. In addition, the automobile 8400 has a secondary battery. For example, secondary battery modules can be arranged on the floor of the vehicle. The secondary battery can not only drive the electric motor 8406 but also supply power to light-emitting devices such as a headlight 8401 and a room light (not shown).

[0578] The secondary battery can also supply power to display devices such as a speedometer and a tachometer included in the automobile 8400. The secondary battery can also supply power to semiconductor devices such as a navigation system included in the automobile 8400.

[0579] The automobile 8500 shown in FIG. 25(B) can charge the secondary battery of the automobile 8500 by receiving power supply from an external charging facility by a plug-in method and / or a non-contact power supply method. FIG. 25(B) shows a state in which a secondary battery 8024 mounted on the automobile 8500 is being charged from a ground-mounted charging device 8021 via a cable 8022. When charging, the charging method and connector standard may be appropriately performed by a predetermined method such as CHAdeMO (registered trademark) or combo. The charging device 8021 may be a charging station installed in a commercial facility or a home power source. For example, the secondary battery 8024 mounted on the automobile 8500 can be charged by an external power supply using plug-in technology. Charging can be performed by converting AC power to DC power via a conversion device such as an ACDC converter.

[0580] Although not shown, a power receiving device may be mounted on a vehicle, and charging may be performed by supplying power contactlessly from a ground power transmitting device. In the case of this contactless power supply method, by incorporating a power transmitting device in the road and / or an exterior wall, charging may be performed not only while the vehicle is stopped but also while it is moving. This contactless power supply method may also be used to transmit and receive power between vehicles. Furthermore, a solar cell may be provided on the exterior of the vehicle, and a secondary battery may be charged while the vehicle is stopped and / or moving. For such contactless power supply, an electromagnetic induction method and / or a magnetic field resonance method may be used.

[0581] 25C is an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. A scooter 8600 shown in FIG. 25C includes a secondary battery 8602, a side mirror 8601, and a turn signal light 8603. The secondary battery 8602 can supply electricity to the turn signal light 8603.

[0582] 25(C) is capable of storing a secondary battery 8602 in the under-seat storage 8604. Even if the under-seat storage 8604 is small, the secondary battery 8602 can be stored in the under-seat storage 8604. The secondary battery 8602 is removable, and when charging, the secondary battery 8602 can be carried indoors, charged, and stored before riding.

[0583] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the discharge capacity of the secondary battery can be increased. Therefore, the secondary battery itself can be made small and lightweight. If the secondary battery itself can be made small and lightweight, it contributes to reducing the weight of the vehicle, and the cruising distance can be improved. In addition, the secondary battery mounted on the vehicle can be used as a power supply source other than the vehicle. In this case, for example, it is possible to avoid using a commercial power source during peak power demand. If it is possible to avoid using a commercial power source during peak power demand, it is possible to contribute to energy conservation and reduction of carbon dioxide emissions. In addition, if the cycle characteristics are good, the secondary battery can be used for a long period of time, and the amount of rare metals used, including cobalt, can be reduced.

[0584] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0585] (Embodiment 6) In this embodiment, an example in which a secondary battery which is one embodiment of the present invention is mounted in space equipment will be described.

[0586] 26A shows an artificial satellite 6800 as an example of space equipment. The artificial satellite 6800 has a body 6801, a solar panel 6802, an antenna 6803, and a secondary battery 6805. The solar panel may be called a solar cell module.

[0587] When the solar panel 6802 is irradiated with sunlight, the power required for the operation of the artificial satellite 6800 is generated. However, for example, in a situation where the solar panel is not irradiated with sunlight or the amount of sunlight irradiated to the solar panel is small, the generated power is small. Therefore, the power required for the operation of the artificial satellite 6800 may not be generated. In order to operate the artificial satellite 6800 even under a situation where the generated power is small, it is preferable to provide a secondary battery 6805 in the artificial satellite 6800. By using the positive electrode active material of the present invention for the secondary battery, it is possible to obtain a secondary battery having a high discharge capacity and excellent cycle characteristics.

[0588] The artificial satellite 6800 can generate a signal. The signal is transmitted via an antenna 6803, and can be received, for example, by a receiver installed on the ground or by another artificial satellite. By receiving the signal transmitted by the artificial satellite 6800, for example, the position of the receiver that received the signal can be measured. As described above, the artificial satellite 6800 can constitute, for example, a satellite positioning system.

[0589] Alternatively, the artificial satellite 6800 can be configured to have a sensor. For example, by configuring the artificial satellite 6800 to have a visible light sensor, the artificial satellite 6800 can have a function of detecting sunlight reflected by an object on the ground. Alternatively, by configuring the artificial satellite 6800 to have a thermal infrared sensor, the artificial satellite 6800 can have a function of detecting thermal infrared rays emitted from the earth's surface. As described above, the artificial satellite 6800 can have a function as, for example, an earth observation satellite.

[0590] FIG. 26(B) shows a probe 6900 having a solar sail (also called a sun sail) as an example of space equipment. The probe 6900 has a body 6901, a solar sail 6902, and a secondary battery 6905. By using the positive electrode active material of the present invention for the secondary battery, it is possible to obtain a secondary battery having a high discharge capacity and excellent cycle characteristics. When a photon emitted from the sun hits the surface of the solar sail 6902, momentum is transferred to the solar sail 6902. Therefore, the surface of the solar sail 6902 preferably has a thin film with high reflectivity, and further preferably faces the sun.

[0591] The solar sail 6902 may also be designed to be folded up small until it leaves the atmosphere, and then deployed into a large sheet outside the Earth's atmosphere (in outer space) as shown in Figure 26(B).

[0592] FIG. 26(C) shows a spacecraft 6910 as an example of space equipment. The spacecraft 6910 has a body 6911, a solar panel 6912, and a secondary battery 6913. By using the positive electrode active material of the present invention for the secondary battery, it is possible to obtain a secondary battery having high discharge capacity and excellent cycle characteristics. The body 6911 can have, for example, a pressurized compartment and a non-pressurized compartment. The pressurized compartment may be designed to accommodate a crew member. Electric power generated by irradiating the solar panel 6912 with sunlight can be charged into the secondary battery 6913.

[0593] 26(D) shows a rover 6920 as an example of space equipment. The rover 6920 includes a body 6921 and a secondary battery 6923. By using the positive electrode active material of the present invention for the secondary battery, the secondary battery can have a high discharge capacity and excellent cycle characteristics. The rover 6920 may include a solar panel 6922.

[0594] The exploration vehicle 6920 may be designed to accommodate a crew member. The secondary battery 6923 may be charged with electricity generated by irradiating the solar panel 6912 with sunlight, or may be charged with electricity generated by other power sources, such as a fuel cell, a radioisotope thermoelectric converter, or the like.

[0595] The content of this embodiment mode can be appropriately combined with the content of other embodiment modes. EXAMPLES

[0596] In this example, the lithium ion battery described in the embodiment mode and the like was manufactured, and the results of obtaining battery characteristics are shown.

[0597] <Preparation of electrodes> Crystalline carbon was prepared as the active material, specifically, spherical natural graphite (FormulaBT 1520, manufactured by Superior Graphite, average particle size 20 μm). In addition, SBR was prepared as the binder, and CMC-Na was prepared as the thickener. Carbon fiber (manufactured by Showa Denko K.K., VGCF (registered trademark)) was prepared as the conductive material. Next, the spherical natural graphite:VGCF:CMC-Na:SBR were mixed in a ratio of 97:1:1:1 (weight ratio) to prepare a slurry. Water was used as the solvent for the slurry.

[0598] After the slurry was applied to the current collector, the solvent was evaporated. An electrode was obtained by the above steps. The amount of active material carried on the electrode was approximately 7.5 mg / cm. 2 The electrodes were circular and had a diameter of 12 mm.

[0599] <Electrolyte> As an electrolyte, LiPF6 and KFSI were dissolved in a mixed solvent containing FEC and MTFP in a ratio of FEC:MTFP=20:80 (volume ratio). Here, LiPF6 was used in an amount of 1 mol / L relative to the mixed solvent of FEC and MTFP. KFSI was used in an amount of 0.2 mol / L relative to the mixed solvent of FEC and MTFP containing LiPF6. In this way, an electrolyte was prepared in the mixed solvent. No additives were used.

[0600] <Coin cell production> A coin cell was produced using the above electrodes, lithium metal foil, a separator, the above electrolyte, a coin cell positive electrode can, and a coin cell negative electrode can. The size of the coin cell was 2032 type (diameter 20 mm, thickness 3.2 mm). Note that a cell using lithium metal foil for the negative electrode as described above is also called a half cell.

[0601] The separator used was a porous polyimide film. Three 23 μm-thick polyimide films were stacked and placed between the electrodes and the lithium metal foil as separators.

[0602] <Initial charging process> As the initial charging process (aging process), discharging and charging were performed at 25°C. As the discharging process, the coin cell was discharged at a constant current (CC discharge) at a current of 0.1C until the voltage of the coin cell reached 0.01V, and then discharged at a constant voltage (CV discharge) until the current reached 0.01C. As the charging process, the coin cell was charged at a constant current of 0.1C until the voltage of the coin cell reached 1.00V. In this embodiment, 1C=372mA / g with respect to the weight of the active material.

[0603] <Temperature characteristic measurement> The temperature characteristics of charging and discharging were measured using the coin cells after the initial charging process.

[0604] The discharge conditions were a constant current discharge at 0.1 C until the coin cell voltage reached 0.01 V, followed by a constant voltage discharge at 0.01 C. The charge conditions were a constant current charge at 0.1 C until the coin cell voltage reached 1.00 V.

[0605] The discharge temperature characteristics and the charge temperature characteristics were measured. The temperature of the measurement environment and the measurement order will be described below.

[0606] [Discharge temperature characteristics] The measurement conditions of the discharge temperature characteristics are explained below. The discharge and charge conditions are as described above. The temperature of the measurement environment and the measurement order were 25°C discharge, 25°C charge, 15°C discharge, 25°C charge, 0°C discharge, 25°C charge, -20°C discharge, 25°C charge, -30°C discharge, 25°C charge, -40°C discharge, and 25°C charge. The discharge capacity at each temperature is shown in FIG. 27(A), and the discharge capacity ratio is shown in FIG. 27(B). The discharge capacity, charge capacity, and discharge capacity ratio are shown in Table 8. The discharge capacity and charge capacity are each capacity per active material weight, and the discharge capacity ratio is the ratio of the discharge capacity at each temperature to the discharge capacity at 25°C expressed as a percentage.

[0607] [Table 8]

[0608] [Charging temperature characteristics] The measurement conditions of the charge temperature characteristics are explained below. T...

Claims

1. The battery has a positive electrode, a negative electrode, an electrolyte, and a separator, The electrolyte and the separator are disposed between the positive electrode and the negative electrode, The negative electrode comprises a carbon material, The battery, wherein the electrolyte contains a lithium salt, a potassium salt, a fluorinated cyclic carbonate, a fluorinated chain carbonate, and at least one anion.

2. In claim 1, The battery, wherein the carbon material comprises graphite.

3. In claim 2, The battery, wherein the graphite comprises natural graphite.

4. In any one of claims 1 to 3, The lithium salt is LiPF 6 having The potassium salt has KFSI, The fluorinated cyclic carbonate comprises fluoroethylene carbonate; The battery, wherein the fluorinated chain carbonate has methyl trifluoropropionate.

5. In claim 4, The battery, wherein the positive electrode comprises lithium cobalt oxide having magnesium, aluminum, and nickel additives.

6. In claim 4, The battery, wherein the positive electrode comprises lithium cobalt oxide having additives of magnesium, aluminum, nickel, and titanium.

Citation Information

Patent Citations

  • Lithium secondary battery and manufacturing method therefor

    JP2005302630A

  • Lithium ion battery

    WO2023073480A1